Anticipatory activity to a daily palatable stimulus is accelerated in free-feeding rats housed in an enriched environment - Olaf Rodríguez-Cruz; Esmeralda Rendón-Candanedo; Diana Angeles-Torres; Alejandro Panes-Castillo; Claudia Juárez-Portilla; Aleph A. Corona-Morales (Behavioural Processes, 2026)

Thriving in the shadows: Functional responses of South American peatmoss Sphagnum magellanicum along a shading gradient - Sebastián A. Reyes; Janice Zúñiga; Isadora Chávez–Poblete; Alfredo Ceballos–Castillo; Paz Aguilera-Opazo; Carolina A. León; Cristian Atala (South African Journal of Botany, 2026)

First record of angiosperm fossil leaf from the Coris Formation (middle Miocene) of the Central Valley, Costa Rica - Marco A. Rubalcava-Knoth; Mario A. Blanco; Rafael Acuña-Castillo; Guillermo E. Alvarado; Luis A. Gamboa; Sergio R.S. Cevallos-Ferriz (Journal of South American Earth Sciences, 2026)

Characterization of microplastics and associated particles in sediments of a coastal wetland in northern Patagonia (Chiloé, Chile) using confocal micro-Raman spectroscopy and their relationship to shellfish aquaculture waste - Fernanda Vargas-Castillo; Benjamín A. Suárez-Isla; Doris Oliva (Marine Pollution Bulletin, 2026)

P145 Uterine microbiome in fertile and subfertile Colombian Creole mares - I.C. Vélez; A. Úsuga; I.L. Jaramillo-Delgado; L.M. Rendón-Ramos; C. Ríos-Usuga; O. Gonzalez; Y. Ramayo-Caldas; V. Castillo-Vanegas; M.P. Paredes-Higuera (Journal of Equine Veterinary Science, 2026)

Responses of Liolaemus lizards to environmental heterogeneity: Linking microhabitat selection and thermal ecology in southern Patagonia - Candela Victorel; Mauro I. Bonavita; Martin C. Castillo; Débora L. Moreno Azocar; María G. Perotti; Félix B. Cruz; Oscar A. Stellatelli (Journal of Thermal Biology, 2026)

High occupancy of non-native carnivores in riparian ecosystems along an urban gradient in Chile - Gisselle A. Castillo-Sandoval; José Infante-Varela; Mauricio R. Soto-Gamboa; Eduardo A. Silva-Rodríguez (Urban Ecosystems, 2026)

Fatty acid composition and blubber stratification in moulting southern elephant seals (Mirounga leonina) from Tierra del Fuego, Southern Patagonia - Antonia Carrasco-Cárdenas; Alicia I. Guerrero; Maritza Sepúlveda; Mauricio F. Landaeta; Josefina Gutiérrez; Sonja Heinrich; Manuel I. Castillo; Andrea Piñones; Luis A. Hückstädt; Fadia Tala; Michael Araya; Carmen Barrios-Guzmán (Marine Biology, 2026)

Reassessing the economic returns of diverse traditional agricultural systems for smallholder farmers: a case study of the milpa in Mexico - Julio Díaz-José; Rogelio Limón-Rivera; Otto R. Leyva-Ovalle; Leticia Myriam Sagarnaga-Villegas; Gregorio Briones-Ruiz; A. Carolina Elizondo-Salas; Hilario García-Martínez; Susana I. Castillo-Martínez; Pablo Andrés-Meza; Oscar Díaz-José; Francisco Guevara-Hernández; Mauricio R. Bellon (Agricultural Systems, 2026)

Climate change vulnerability of the Afrotemperate flora on Africa’s tropical sky islands - Elvira Castillo-Almansa; Rubén G. Mateo; Mercè Galbany-Casals; Carme Blanco-Gavaldà; Lucía D. Moreyra; Cristina Roquet; Christian Brochmann; Abel Gizaw; Desalegn Chala; Alfonso Susanna; Juan A. Calleja (Biodiversity and Conservation, 2026)
Climate change poses a significant threat to the Afrotemperate flora of the Eastern Afromontane Biodiversity Hotspot, particularly to species confined to high-elevation ecosystems such as those found on the African sky islands. This study evaluates the vulnerability of tropical Afroalpine and Afromontane Helichrysum taxa (Compositae) by assessing their climatic niches and predicting future shifts in distribution, range fragmentation, and altitudinal limits under climate change scenarios. Occurrence records for 14 taxa (eight Afroalpine and six Afromontane) were obtained from recent field campaigns, biodiversity databases and herbaria. Ensemble ecological niche models were developed combining Generalized Linear Models, Generalized Boosting Models, and Random Forest. Taxon-specific bioclimatic variables were selected after correlation analyses. The models were calibrated using current climate data and projected using the PSL-CM6A-LR and MRI-ESM2.0 climate models with both low- and high-emission scenarios. The results show that most Afrotemperate taxa currently occupy only a portion of their climatically suitable habitat, often in geographically distant areas. Future projections indicate significant range contractions and increased fragmentation. Afroalpine taxa could lose 50–66% of their suitable habitat, while Afromontane taxa could decline by 53–79%. Suitable areas were estimated to shift upwards in elevation, with limited potential for colonization of new areas, and with no significant latitudinal or longitudinal shifts. These findings represent the first continental-scale assessment of the impact of climate change on the Afrotemperate flora using ecological niche modelling. The projected climate-induced range losses and increased habitat fragmentation, in particular combined with increasing anthropogenic pressure in this region, highlight the urgent need for targeted conservation actions.

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Morphological and physiological responses of vanilla (Vanilla planifolia Jacks. ex Andrews) to chemically synthesized and green-synthesized silver nanoparticles during micropropagation - Marco A. Ramírez-Mosqueda; José Luis Aguirre-Noyola; José Luis Spinoso-Castillo; José Roberto Bautista-Aguilar; Elizabeta Hernández-Domínguez; Carlos A. Cruz-Cruz; Gustavo Cuaxinque-Flores (In Vitro Cellular & Developmental Biology - Plant, 2026)

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Microbial communities and pharmaceutical contaminants in the water-soil–plant continuum of sugarcane crops irrigated with contaminated waters from the Cauca River Valley, Colombia - Juan Ceballos-Castillo; Rodrigo A. Echeverry-Gallego; Diana Martínez-Pachón; Alejandro Moncayo-Lasso; Javier Vanegas (Environmental Science and Pollution Research, 2026)
“Agricultural irrigation with contaminated water poses a major risk to food security and public health. This study examined contaminant transfer across the water–soil–plant continuum in sugarcane crops irrigated with water from the Cauca River, Colombia. Microbial community composition was characterized using 16S rRNA gene sequencing, while pharmaceutical active compounds (PhACs) in irrigation water and sugarcane plants were quantified by UHPLC–MS/MS. Microbial analyses revealed a potential biological pathway of microorganisms from water and soil into plant endophytic tissues. Bacterial diversity decreased markedly, from more than 400 genera identified in water and soil to only 64 genera detected within endophytic tissues. Nine potentially pathogenic genera-including Escherichia–Shigella , Pseudomonas , and Bacillus - were found across all matrices, suggesting microbial internalization. Bioinformatic predictions indicated the presence of genes associated with virulence traits (e.g., antimicrobial resistance and biofilm formation) as well as beneficial functions such as nitrogen fixation and phosphate solubilization. In parallel, high concentrations of PhACs were detected in irrigation water, including valsartan (up to 1309 ng L⁻ 1 ) and diclofenac (up to 969 ng L⁻ 1 ), whereas none or only low concentration detected in sugarcane tissues. Overall, the primary risk to human health appears to stem not from chemical uptake but from microbial infiltration shaped by environmental pressures. Therefore, managing plant-associated microbiomes is essential to mitigate health risks while harnessing biotechnological potential for sustainable agriculture.”

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Life-position succulent Euphorbia L. fossils buried in Pleistocene explosive volcanic deposits from Tenerife, Canary Islands, Spain - M.C. Velasco-Flores; L.M. Sender; C. González-Montelongo; A. Santos; P. Cruzado-Caballero; M.C. Martín-Luis; C. Alfayate; C.A. Góis-Marques; C. Castillo (Review of Palaeobotany and Palynology, 2026)

Phase space analysis of roll dynamics and stability for a semisubmersible near neutral equilibrium - José Carlos Villagómez Rosales; Claudio A. Rodríguez Castillo; Paulo de Tarso Themistocles Esperança (Ocean Engineering, 2026)

Drivers of consumer liking in top- and bottom-fermented beers: Integrating sensometric and chemometric insights - Yaressi G. Rodríguez-Velazco; Arturo A. Mayorga-Martínez; Jorge A. Clorio-Carrillo; Bárbara Lozano-De la Garza; Angela Castillo-Álvarez; Claudia Gonzalez Viejo; Sigfredo Fuentes; Raúl Villarreal-Lara; Carmen Hernández-Brenes (Food Research International, 2026)

Ancient and recent soils as indicators of the genesis and evolution of Salada de Chiprana from middle Pleistocene to present (Ebro Basin, NE Spain) - M. Tierra; C. Castañeda; F.J. Gracia; R. Rodríguez-Ochoa; J.R. Olarieta; A. Medialdea; O. Castillo (CATENA, 2026)

Natural forest conversion to exotic pine plantations induces soil mineralogical and physicochemical changes – implications for soil organic carbon stabilization - P. Castillo; M.F. Albornoz; O. Crovo; A. Atenas; C.I. Czimczik; R. Southard; F. Aburto (CATENA, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

Exploring anti-dengue activity with atomic-weighted vectors, class balancing and machine learning - Yoan Martínez-López; Ansel Y. Rodríguez-Gonzalez; Paulina Phoobane; Pedro Castillo Regalado; Juan A. Castillo-Garit; Noel Enrique Rodríguez-Maya; Oscar Martínez-Santiago; Carlos de Castro Lozano; José Miguel Ramírez Uceda; Pablo Duchowicz (Molecular Diversity, 2026)

LA-COMET group: In vivo application of the comet assay in animal and plant models, including wild species - Gisela L. Poletta; Patricia Mussali-Galante; J. Alfredo Castillo-Ipiña; Guillermo Espinosa-Reyes; Ana Rosa Flores-Márquez; Donaji J. González-Mille; César A. Ilizaliturri-Hernández; Celeste Ruiz de Arcaute; Efraín Tovar-Sánchez; Juliana da Silva; Deidamia Franco; Ana Leticia García; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Bioactive molecules from Agave salmiana bagasse: Study of their antioxidant, prebiotic potential, and cytotoxicity - Isabel Márquez-Rangel; Mario Cruz; Héctor A. Ruiz; Rosa M. Rodríguez-Jasso; Araceli Loredo-Treviño; Guillermo Castillo-Olvera; Ruth Belmares (Food Research International, 2026)

Vaccine strategies for cancer prevention in Lynch syndrome: the potential of dendritic cell-based therapy - Romy N. Kuipers; Mark A. J. Gorris; Cristina Bayó; Tom Hofland; Daniel Benítez Ribas; Georgina Flórez Grau; Nicoline Hoogerbrugge; Joaquin Castillo; Francesc Balaguer; Tanya M. Bisseling; Gerty Schreibelt; I. Jolanda M. de Vries (Familial Cancer, 2026)
Cancer vaccines offer a promising strategy for cancer prevention, particularly in hereditary cancer syndromes such as Lynch syndrome (LS). LS is characterized by a high lifetime risk of developing various malignancies due to defects in DNA mismatch repair, leading to an accumulation of mutations, particularly frameshift insertion/deletions (indels) within microsatellite loci. These indels create shared tumour-specific neoantigens, which are unique to LS and can be recognized by the immune system and trigger cancer cell killing. Importantly, these neoantigens are also present in precancerous lesions, making LS an ideal target for immune-interception strategies aimed at prevention. Over the years, a variety of vaccine designs targeting different antigens along with a range of delivery platforms have been explored for different types of tumours, each with its own advantages and limitations. In this review, we provide an overview of the key antigens and delivery platforms used in cancer preventive vaccine development for LS, evaluate their limited clinical outcomes to date, and explore the future directions of preventive vaccine immunotherapy. A particular focus is placed on the promising potential of dendritic cell vaccination therapy as a future approach in this field.

Subcritical water extraction of Ilex guayusa for regulatory-compliant neuro-metabolic functional ingredients - Vanesa Sánchez-Martín; Minxing Zhang; Lidia Montero; Elena Ibáñez; Jose A. Mendiola; María Dolores del Castillo (Sustainable Chemistry and Pharmacy, 2026)

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

Quantification of aboveground and belowground biomass and associated organic carbon in two olive cultivars (Arbosana and Picual) grown at high density - Milagros Torrús-Castillo; Gema Guzmán; Belén Cárceles; María-Auxiliadora Soriano; Raúl de la Rosa; José A. Gómez (Trees, 2026)
Accurate quantification of biomass and carbon accumulation in olives is crucial for optimizing agronomic management and assessing their role to climate change mitigation. This study, developed destructive and non-destructive methodologies to quantify above- and belowground biomass and carbon content in 7.5-year-old trees of two common olive cultivars ( Arbosana and Picual) under Mediterranean conditions. The approach included the removal of three whole-trees per cultivar and combined assessment of above- and belowground biomass, rarely available for olive trees. Picual tended to accumulate more biomass (36.5 kg tree −1 , on average) than Arbosana (27.5 kg tree −1 ), due to a greater investment in trunk and non-primary branches, whereas Arbosana allocated more biomass to leaves. In both cultivars, around 60% of the root biomass was within the top 25 cm of soil, and over 55% was concentrated in the root ball. Weighted average carbon concentration was 47% in aboveground biomass and 42% in roots. At the orchard scale, soil was the main organic carbon pool, around 76 t C ha −1 , compared to 13–16 t C ha −1 in the tree biomass. Annual carbon accumulation in olive biomass ranged from 1.68 t C ha −1 yr −1 ( Arbosana ) to 2.16 t C ha −1 yr −1 ( Picual ), within the range of C fixation rates in Mediterranean agroecosystems. Destructive sampling better captured cultivar differences in biomass allocation and carbon accumulation, while the non-destructive method proved suitable for large-scale use. These results support integrating biomass allocation and carbon permanence into cultivar selection and management to enhance carbon sequestration and sustainability of olive grove systems.

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Plant-based production of virus-like particles from hepatitis C virus - Laura M. López-Castillo; Rafael Gonzalez-Castro; Lino Sánchez-Segura; Brisia A. Aguilar-Barragán; Miguel A. Gomez Lim (Planta, 2026)
Main conclusion Virus-like particles (VLP) from hepatitis C virus were successfully produced in Nicotiana benthamiana plants for the first time, by co-expressing three viral proteins (Core, E1 and E2) in a polycistron-like arrangement. Abstract Hepatitis C virus (HCV) remains a global health challenge, underscoring the need for a preventive vaccine. Virus-like particles (VLP) offer a safe alternative, as they resemble native virions without infectious genomes. We expressed the HCV structural proteins Core, E1, and E2 in Nicotiana benthamiana using binary and deconstructed viral vector systems. Western blot confirmed expression, with the binary system achieving higher yields. Purified proteins assembled into spherical VLP (40–60 nm) were confirmed by electron microscopy. These findings demonstrate for the first time the feasibility of producing complete HCV-VLP in plants, supporting their potential as a scalable platform for vaccine development.

Community-based water quality in Coronel Chile: addressing environmental sustainability in a labeled sacrifice zone - Mariela A. Yevenes; Robinson Torres; Marcelo Veloso; Natalia Durán; Micaela Castillo; Sofía Castañeda (Environmental Monitoring and Assessment, 2026)

Modulation of the photodynamic activity of a cinnamoyl-coumarin–RGD peptide conjugate via cucurbit[8]uril supramolecular assembly - Benjamín Zúñiga; Paula S. Rivero-Jerez; Sofia Pérez-Del Pino; Francisco Bravo-Cabezas; Francisco Mura; Pablo Barrias; Claudio Acuña-Castillo; Mario A. Faúndez; Alexis Aspeé; Daniel Zúñiga-Núñez; Denis Fuentealba (Journal of Photochemistry and Photobiology B: Biology, 2026)

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Landslides impact and management on human settlements over 3000 years: the case of the Montilla Castle Hill (Córdoba, Spain) - Francisco J. Jiménez-Espejo; Lourdes González-Castillo; Francisco Lamas; Francisco José Martínez-Moreno; Jesús Galindo-Zaldívar; Jon Camuera; Sergio Moyano; José A. Peláez; José Luis Urbano; Mónica Camacho Calderón; Raimundo Ortiz (Natural Hazards, 2026)
In recent decades, global urbanisation has increased dramatically. The study of urbanised areas over the last millennium offers valuable insight into the long-term landslide hazards associated with human settlements. Anthropogenic environmental impact and urbanisation in southern Iberia began around 2200 yr BCE, rendering this region a unique location to examine interactions between building construction and landslide over millennial timescales. The Montilla Castle Hill, in south Spain, was selected for this study due to its clear evidence of landslides and confirmed historical occupation dating back to the Copper Age. This study adopted a multidisciplinary approach, integrating archaeology, geology, geophysics, geotechnical modelling and related disciplines to characterize construction types and pathologies, as well as landslide ages, critical stability threshold values, landslide mechanisms and key features. The obtained data were compared with regional paleoclimate records and earthquakes/tsunamic events in south Iberia. Four landslide activity phases have been dated: from 650–550 BCE, from 400 to 200 BCE, from 1400 to 1450 and along the XVIII to XX centuries. Observations revealed that the presence of major buildings at the summit of the Castle Hill, at the landslide crown, were a key factor in promoting the reactivation of ancient landslides. This study found no evidence linking climate conditions with slope stability, but a correlation with major regional earthquakes was observed, in agreement with the modelled values obtained.

Fungal endophytes and their secondary metabolites for crop protection - Jorge Rojas López-Menchero; Fotios A. Lyssaios; Nicolás Reyes-Castillo; Maria Fe Andres; Azucena González-Coloma; Carmen E. Díaz (Journal of Pest Science, 2026)
Fungal endophytes have emerged as a promising strategy for sustainable crop management, due to their remarkable ability to synthesize a wide array of secondary metabolites with beneficial effects on plants. These microorganisms establish asymptomatic relationships within plant tissues and can produce bioactive compounds with biocidal properties. Despite promising advances, the mechanisms of symbiosis remain unclear and there is a lack of in-depth analysis on the chemical characterization of their metabolites. This review compiles and discusses the current discoveries on 180 metabolites summarized according to their biological activities (insecticidal, antifungal, phytotoxic, nematicidal and antibacterial), highlighting their potential applications as biocontrol agents for integrated crop protection strategies. As a future perspective, the use of next-generation sequencing (NGS) technologies such as metagenomics in endophytic fungi research is emphasized for its promise in elucidating complex plant–microbe interactions and guiding bioprospecting efforts to identify fungal taxa capable of producing agriculturally relevant bioactive compounds. This review aims to summarize recent advances in the field, highlighting the potential uses of endophytic compounds in plant health, disease suppression, and resistance enhancement, while also identifying current limitations and outlining future research directions to further expand this promising area.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Neurobiological effects assessment in wild rodents exposed to mercury in Sierra Gorda Biosphere Reserve, Querétaro, Mexico - S. Vargas-Ruiz; C.G. Castillo; E. Rubio-Hernández; A. Gavilán-García; F. Díaz-Barriga; G. Espinosa-Reyes (Chemosphere, 2026)

Using front face fluorescence for rapid estimation of furosine concentration in heat treated milk: a kinetic study - C. González-Gallardo; N. Ayala; F. Ali; A. Zamora; J. Saldo; M. Castillo (International Dairy Journal, 2026)

Exchange flow structure at two inlets of a multiple-inlet subtropical estuary - Maria F. Gastelu-Barcena; Jorge A. Laurel-Castillo; Maitane Olabarrieta; Christine Angelini; David Fugate; Arnoldo Valle-Levinson (Estuarine, Coastal and Shelf Science, 2026)

Beyond understanding the role of far-field climate in the Gulf of Panama coastal dynamics: an analysis of long-term and seasonal variability of wave systems - Ruby Vallarino-Castillo; José A. A. Antolínez; Vicente Negro-Valdecantos; Jesús Portilla-Yandún (Climate Dynamics, 2026)
Understanding wave systems (WS) dynamics in semi-enclosed tropical basins is challenging due to interactions between remote wave generation and regional climate variability. In the Gulf of Panama, prior studies mainly relied on single-site offshore analyses, limiting characterization of wave energy distribution and its atmospheric and oceanic drivers. This gap in knowledge is particularly consequential for coastal hazard assessments and for deciphering ocean–atmosphere interactions in regions influenced by both long-period swells and low-level wind jets. To address this limitation, we present a comprehensive multi-decadal analysis of the seasonal and long-term variability of significant wave height (Hs) and peak wave period (Tp), based on WS identified applying spectral statistical techniques using the GLOSWAC-5 atlas. To understand the variability and the modulating effect of the Gulf of Panama semi-enclosed morphology, three representative sites at its entrance were selected. Monthly patterns were analyzed by classifying wave trains according to relative orientation (i.e., following, crossing, and opposing) to determine the predominant direction and multimodal activity. Long-term trends were assessed over 17 to 18-year intervals (i.e. 1969–1987, 1988–2005, 2006–2023) using exploratory analysis and quantile regression, with results reported separately for the dry season (December–April) and the wet season (May–November). The analysis revealed five dominant WS, each associated with specific generation mechanisms and geographic origins: WS1, associated with Southern Ocean swells; WS5, originating from Northern Hemisphere swells; WS2, driven by southeasterly trade winds from the subtropical Pacific; and two regionally forced systems, WS3 and WS4, generated by the Panama and Chocó Low-Level Jets, respectively. WS1 shows increases in Hs of about 5–10 cm during 1969–1987 and 1988–2005, and up to ~ 15 cm in 2006–2023, with Tp rising by ~ 0.3–0.6 s over the same intervals. WS2 exhibits small variations, with Hs ranging from − 10 to + 17 cm and Tp fluctuations within ± 0.3 s across the three intervals. WS3 displays the strongest changes, with median Hs increases of 10–30 cm in the first two intervals and extreme values reaching 50–60 cm in 1988–2005 and 2006–2023, together with Tp increments of ~ 0.3–0.5 s. WS4 remains comparatively stable in all periods, with Hs variations within ± 10 cm and Tp changes < 0.4 s. WS5 intensifies mainly in 2006–2023, showing Hs increases of 8–15 cm and Tp rises of ~ 0.2–0.4 s. Monthly mean Hs anomalies (> 0.10 m) at the 50th percentile suggest a relationship with El Niño–Southern Oscillation (ENSO), but analyses using the 95th percentile reveal that only WS2, WS3, and WS4 exhibit a stronger association with ENSO phases.

Evolutionary origin and demographic trajectory of tomato spotted wilt virus (Orthotospovirus tomatomaculae) - José A. Castillo; Lenin Ramírez-Cando (Archives of Virology, 2026)

Physiological and transcriptomic responses to fasting-refeeding in Arapaima gigas: Insights into compensatory growth for aquaculture production - T.H. Delgadin; L.E. Santos-Rojas; D. Medina-Herrera; N.M. Herrera-Castillo; A.M. Alonso; A. Saavedra-Flores; E.A. López-Landavery; J.I. Fernandino; E. Zelada-Mázmela (Aquaculture, 2026)

Light sensing in fish embryonic cells: A circadian analysis of visual and non-visual opsin expression using a seabream embryonic stem cell line - Alba Vergès-Castillo; Patricia Herrera-Pérez; Carlos Pendón; Jaume Pérez-Sánchez; Águeda J. Martín-Robles; José A. Muñoz-Cueto (Aquaculture, 2026)

Microbial consortia in mine water bioremediation: principles, design and practical applications - A. Matu; A. Valverde; E. Cason; A. Gomez-Arias; M. Maleke; J. Castillo (Water Research, 2026)

Revisiting Small‐Scale Aquaculture ( SSA ) - Liliana Sierra Castillo; Halley E. Froehlich; Jono R. Wilson; Jessica A. Gephart; Erendira Aceves‐Bueno; Steven D. Gaines (Reviews in Aquaculture, 2026)
Aquatic foods are a vital source of nutrition, yet growing demand and stagnant wild‐capture fisheries have positioned aquaculture as essential to meeting global food needs. Despite this, aquaculture's diverse forms remain poorly understood, particularly small‐scale aquaculture (SSA). Unlike small‐scale fisheries (SSF), which are widely recognized in policy and research, SSA lacks consistent definitions and is often conflated with SSF or defined narrowly by physical metrics like farm size. This limits its visibility in policy and development efforts, overlooking critical social, economic, and governance dimensions such as ownership, labor, and market orientation. Through a systematic review of 83 studies across 24 countries, we analyze SSA across ecosystems (freshwater, brackish, marine) and species groups (finfish, invertebrates, seaweed) to identify trends in production characteristics, yield reporting, and social dimensions. We find freshwater SSA dominates the literature, while marine SSA, especially mollusk farming, is significantly underrepresented. SSA exhibits wide variation in yields, farm sizes, ownership, and management structures, indicating that existing classification frameworks are insufficient. We propose a context‐sensitive, social‐ecological classification system that integrates production metrics with governance and socioeconomic characteristics. To guide application, we offer two policy frameworks, one for regions with existing SSA definitions, recommending participatory revision and expanded data collection; and one for regions without definitions, advocating for a stepwise approach to characterization. Our findings underscore the need for more inclusive, adaptable classifications to improve SSA's visibility in global food policy and unlock its full contributions to sustainable development, equity, and local livelihoods.

Infrared Emission in the Second Biological Window in LaInO3:Ho3+ Exciting in the First Biological Window - Mauricio A. Vega-Pallauta; Rodrigo Castillo; Kevin Soler-Carracedo; Inocencio R. Martin (Journal of Fluorescence, 2025)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Comparative analysis of the viability of Fasciola hepatica eggs collected from fecal and gallbladder samples in experimentally infected sheep - S. Ortega-Vargas; I. Cruz-Mendoza; J.A. Figueroa-Castillo; A.V. Balderas-Loaeza; A. Villa-Mancera; F. Utrera-Quintana; H. Quiroz-Romero (Veterinary Parasitology, 2025)

Effects of domesticated-to-wild gene flow on the genetic structure and diversity of wild papaya (Carica papaya L.) in its Mesoamerican diversity area - Mauricio Heredia-Pech; Jaime Martínez-Castillo; Daniela A. Martínez-Natarén; Pedro Ruiz-Gil; Mónica I. Jiménez-Rojas; Matilde M. Ortiz-García; Mariana Chávez-Pesqueira (Genetica, 2025)

Seasonal variation in arbuscular mycorrhizal colonization in three Asteraceae species in a temperate secondary forest - Brenda Guerrero-Bautista; Yasmin Vázquez-Santos; Silvia Castillo-Argüero; Yuriana Martínez-Orea; Marco A. Romero-Romero (Acta Oecologica, 2025)

Admixture Increases Genetic Diversity and Adaptive Potential in Australasian Killer Whales - Isabella M. Reeves; John A. Totterdell; Jonathan Sandoval‐Castillo; Emma L. Betty; Karen A. Stockin; Ramari Oliphant Stewart; Muriel Johnstone; Andrew D. Foote (Molecular Ecology, 2025)
Admixture is the exchange of genetic variation between differentiated demes, resulting in ancestry within a population coalescing in multiple ancestral source populations. Low‐latitude killer whales ( Orcinus orca ) populations typically have higher genetic diversity than those in more densely populated, high productivity and high‐latitude regions. This has been hypothesized to be due to episodic admixture between populations with distinct genetic backgrounds. We test this hypothesis by estimating variation in local ancestry of whole genome sequences from three genetically differentiated, low‐latitude killer whale populations and comparing them to global genetic variation. We find ‘Antarctic‐like’ ancestry tracts in the genomes of southwestern Australia (SWA) population including recent (within the last 2–4 generations) admixture. Admixed individuals had, on average, shorter and fewer runs of homozygosity than unadmixed individuals and increased effective population size ( N e ). Thus, connectivity between demes results in the maintenance of N e of relatively small demes at a level comparable to the sum of N e across demes. A subset of the admixed regions was inferred to be evolving under selection in the SWA population, suggesting that this admixed variation may be contributing to the population's adaptive potential. This study provides important and rare empirical evidence that small populations can maintain genetic diversity due to sporadic admixture between different genetic backgrounds and that admixed ancestry can promote the long‐term stability of N e .

Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Martin Calianno; Daniel A. Castillo; Santiago I. Hurtado; Saúl Deluchi; Brenda Garcia; Laura Villar; E. Sebastian Villagra; Marcos H. Easdale (Small Ruminant Research, 2025)

Recovery of strategic elements from mining tailings at La Cienega, Peru, through geochemical and mineralogical assessment: a focus on circular economy policy - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge Chira-Fernandez; Cesar De la Cruz-Poma; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Out in the Cold: The ignored influence of glacial melting on Rhincalanus gigas and R. nasutus (Copepoda, Calanoida) morphology in Antarctic waters - Tamara Segovia-Jara; Hugo A. Benítez; Manuel I. Castillo; Mario La Mesa; Claudia Morales-Garrido; Benjamín Rodríguez-Stepke; César A. Cárdenas; Mauricio F. Landaeta (Marine Environmental Research, 2025)

Bridging yield gaps in rice production through integrated crop and nutrient management with farmer groups - Hasil Sembiring; Setia Sari Girsang; Arif Anshori; Erythrina Erythrina; Pepi Nur Susilawati; Andy Bhermana; Yohanis Ngongo; Sidiq Hanapi; Darojat Prawiranegara; Nuning A. Subekti; Priatna Sasmita; Irish Lorraine B. Pabuayon; et al. (Field Crops Research, 2025)

Effect of a feed additive based on a mix of condense and hydrolysable tannins (ByPro®) on lactating dairy cows milk production performance - Alejandro R. Castillo; Martin Pol; Mónica Gaggiotti; Julio A. Di Rienzo; Damiano Cavallini (Tropical Animal Health and Production, 2025)
The objective of this research was to evaluate the effect of a commercial mix of condensed and hydrolysable tannins feed additive to lactating dairy cows. Two high-scale dairy farm units, similar management and diets were used. All lactating cows in one unit were fed with the mix of tannins (ByPro ® 0.3%DMI), the other unit was the Control. Cows were categorized per DIM, 0 to 30, 31 to 120, 121 to 365, and more. Milk yield and composition was evaluated in all the lactating cows in each dairy unit at time 0, (initial), and after 4 weeks of supplementation (final). A linear model was adjusted for each variable. Estimated DMI and diets were similar in both dairy units, averaging 25.5 kg DMI/cow, as well as feed ingredients, dietary nutrient contents, and milk yield (34 kg milk/cow per day). Milk yield, from 0 to 365 DIM was increased ( P < 0.01) on supplemented cows (+ 2.3 ± 0.33 L milk/cow.d), with no effect on milk fat and protein contents. High data variability was observed on cows with 0–30 DIM, milk fat and protein content were reduced by ByPro without effect on milk yield. Positive responses of ByPro ® on milk, milk fat and protein contents from 31 to 120 and 121–365 DIM were observed, + 3.6 and + 3.2 kg milk/cow.d; +0.27% fat and + 0.21% protein; and + 0.17% fat, + 0.11% protein; respectively. The mix of tannins increased milk lactation performance on cows with more than 30 DIM.

Strategic potential assessment of lanthanum and scandium through geochemical-lithological analysis with unsupervised machine learning in southern Ecuador - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; José A. Guartán; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

A recently identified mass-transport deposit stack in the Guaymas Basin, Gulf of California (México), and its implication in the basin tectonics - A. Piña; J. Stock; D. Lizarralde; S. Hart; K. Marsaglia; C. Gallegos-Castillo; C. Berndt; A. González-Fernández; C. Mortera-Gutiérrez; A. Martín-Barajas (Marine Geology, 2025)

Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge E. Chira-Fernandez; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Journal of Environmental Chemical Engineering, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

The Health Benefits of Probiotic Lactiplantibacillus plantarum: A Systematic Review and Meta-Analysis - Amal Aljohani; Noha Rashwan; Shruti Vasani; Ahmed Alkhawashki; Tong Tong Wu; Xingyi Lu; Daniel A. Castillo; Jin Xiao (Probiotics and Antimicrobial Proteins, 2025)
To ensure effective administration of probiotics in clinical practice, it is crucial to comprehend the specific strains and their association with human health. Therefore, we conducted a systematic review and meta-analysis to evaluate the scientific evidence on the impact of Lactiplantibacillus plantarum probiotic consumption on human health. Out of 11,831 records, 135 studies were assessed qualitatively, and 18 studies were included in the meta-analysis. This systematic review demonstrated that probiotic supplementation with L. plantarum , either alone or in combination, can significantly improve outcomes for patients with specific medical conditions. Meta-analysis revealed notable benefits in periodontal health, evidenced by reduced pocket depth and bleeding on probing ( p < 0.001); in gastroenterological health, marked by significant reductions in abdominal pain ( p < 0.001); and in infectious disease, through a reduction in C-reactive protein levels ( p < 0.001). Cardiovascular benefits included lowered total cholesterol and low-density lipoprotein cholesterol in the L. plantarum intervention group ( p < 0.05). Our study’s clinical significance highlights the importance of considering probiotic strain and their application to specific diseases when planning future studies and clinical interventions, emphasizing the need for further research in this area.

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Security cameras: a tool for reducing risks and increasing selectivity in wildlife trapping - Eduardo A. Silva-Rodríguez; Javiera P. Jara-Díaz; Gisselle A. Castillo; Esteban I. Cortés; José Infante-Varela; Javier Godoy-Guinao (Mammalian Biology, 2025)

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Conservation Arks: Genomic Erosion and Inbreeding in an Abundant Island Population of Koalas - Katie Gates; Jonathan Sandoval‐Castillo; Julian E. Beaman; Karen Burke da Silva; Frédérik Saltré; Katherine Belov; Carolyn J. Hogg; Corey J. A. Bradshaw; Luciano B. Beheregaray (Molecular Ecology, 2025)
The persistence of many threatened species depends on isolated habitat patches such as conservation parks, fenced reserves, and islands. While these ‘conservation arks’ provide refuge from many contemporary threats, they can also pose risks of genetic diversity loss and inbreeding depression, further exacerbating extinction risk. A pertinent example is the Kangaroo Island koala population in South Australia that originated from a few translocated founding individuals in the 1920s but now sustains a large population with a low prevalence of infectious disease. We investigated the extent and consequences of founder effects on genomic diversity, inbreeding, and adaptive potential in Kangaroo Island koalas by comparing them with mainland Australian populations using high‐coverage whole genomes. Our findings support sharp, recent declines in effective population sizes ( N e ) in both mainland and Kangaroo Island populations. However, Kangaroo Island koalas had much lower individual and population‐level diversity. Together with longer and more numerous runs of homozygosity and an increased proportion of homozygous genetic load, these results support the hypothesis that a severe bottleneck has contributed to inbreeding and maladaptation in Kangaroo Island koalas. While Kangaroo Island has the potential to conserve a viable population of koalas, we recommend genetic rescue to restore diversity and mitigate inbreeding depression in this isolated population. Our results emphasise the need for longitudinal genomic monitoring and genetic management to maintain long‐term viability and resilience in potential conservation arks. Understanding the demographic history of such populations will help inform future conservation aimed at preventing genetic erosion and preserving biodiversity.

Population Parameters and Stock Assessment of Mylossoma albiscopum (Characiformes: Serrasalmidae) in the Amazonian Plain of the Putumayo River, Colombia - César A. Bonilla‐Castillo; Edwin Agudelo Córdoba (Fisheries Management and Ecology, 2025)
Mylossoma albiscopum is one of the primary species consumed by humans in the Colombian Amazon, but understanding is limited on its life history traits and the current status. Therefore, the fishery was monitored in the Putumayo River basin between 2016 and 2023 to estimate growth parameters and assess stock status using the data‐limited LB‐SPR method. Asymptotic length ( L ∞ ) was 28.63 cm, natural mortality ( M ) was 0.92, von Bertalanffy growth ( k ) was 0.39, and length at 50% maturity ( L m50 ) was 15.0 cm. The spawning potential ratio (0.39) was similar to the reference point (0.40), so the fishery exploited the population near its optimal level. We recommend that the Colombian fisheries authority consider L m50 as the legal catch length limit and continue annual evaluations of the fishery to ensure its sustainability.

Congregation of cusk‐eels ( Genypterus chilensis , Ophidiiformes) at a deep‐sea methane seep off Chile - Lisa A. Levin; Eulogio Soto; Yerko Castillo; Patricia Esquete; Jeffrey Marlow (Ecology, 2025)

Impacts of heat stress under oceanic climate on fertility and reproductive physiology of dairy cows subjected to hormonal synchronization - E. N. Martínez; C. Castillo; L. Avendaño-Reyes; J. Hernández; J. L. Benedito; A. Rico; P. Garcia; R. Muiño (International Journal of Biometeorology, 2025)
Regions with oceanic climates are experiencing unprecedented climatic changes. This study assesses the presence of heat stress in these regions and its impact on reproductive in Holstein cows using the Temperature-Humidity Index (THI), a measure of thermal stress. Data was collected from 159 Holstein cows across experiments. Cows underwent a modified double-ovsynch synchronization protocol, while 96 cows were inseminated based on observed estrous. Cows were examined for body temperature, follicle and uterus examination, and serum progesterone concentrations to evaluate the impact of heat stress. The results of cows pregnancy rate in double-ovsynch synchronized cows were 48.5% and 43.3% in summer and winter seasons, respectively. While the pregnancy rate in non-synchronized cows were 29.5% and 32.7% in summer and winter season, respectively. Elevated THI levels (THI ≥ 72) have adversely effects on reproductive physiology, reduced estrous expression, decreased uterine blood flow, and altered progesterone concentrations. Mild heat stress during summer months in oceanic climate negatively impacted reproductive efficiency in dairy cows, for adaptive management strategies. The double-ovsynch protocol effectively stabilized fertility across seasons, demonstrating its value in improving reproductive outcomes under varying thermal conditions.

Under threat: Land use change, distribution and conservation of poorly-known endemic microsnails from the coast of Chile - Gonzalo A. Collado; Juan Francisco Araya; Viviana Castillo; Nicolás I. Villalobos (Anthropocene, 2025)

Revealing Speciation Mechanisms Across Endemic Southern Andean Lilies ( Phycella , Hippeastreae, Amaryllidaceae) in the Chilean Biodiversity Hotspot - Nicolás García; Taryn Fuentes‐Castillo; María José Román; Ryan A. Folk (Molecular Ecology, 2025)
Cryptic speciation, an endemic problem in biodiversity hotspots, arises as a result of an uncoupling among three processes: lineage splitting, morphological diversification, and ecological divergence during rapid speciation. We studied speciation processes in Phycella (Amaryllidaceae), a clade mostly restricted to the Chilean Biodiversity Hotspot, aiming to differentiate the relative roles of geographic and ecological speciation as well as the role of secondary gene flow in this radiation. We sampled a total of 137 individuals from 47 populations, including all described taxa throughout the geographic range of the group. Using 884 nuclear genes (1125 exons) and near‐complete plastomes through hybrid capture, we resolved the phylogeny of Phycella with high support and demonstrated substantial phylogenetic resolution at the population level. Analyses of niche overlap among species and nuclear clades suggest that the diversification of Phycella was associated with niche divergence, supporting a predominantly geographic mode of speciation in the group, likely driven by the mountainous landscape characteristic of the central area of the Chilean Biodiversity Hotspot. Phylogenetic network and modelling approaches identified major cytonuclear discord, attributable to proximity‐based secondary gene flow among species, largely restricted to cytoplasmic DNA. Finally, we present a major integrative taxonomic proposal that divides Phycella into 18 species on the basis of molecular, morphological, and ecological data. Overall, our results highlight the relevance of the mountainous landscape of central Chile to promote diversification in Phycella , and ours is among a few studies on speciation for an endemic element of the Chilean Biodiversity Hotspot.

Hydrological seasonality is a major driver of ecosystem metabolism in tropical nonwadeable rivers - María M. Castillo; Amber J. Ulseth; Aarón Jarquín‐Sánchez; Arturo Álvarez‐Merino; Krista A. Capps (Limnology and Oceanography, 2025)
Studies of annual patterns of ecosystem metabolism in rivers have primarily been conducted in temperate ecosystems, and little is known about metabolic regimes of tropical rivers. We estimated ecosystem metabolism in four nonwadeable rivers in southern México that varied in size and the extent of human disturbance. The smaller rivers with limited human disturbance showed reduced gross primary production (GPP; 1.0 and 1.7 g O 2 m −2 d −1 ), ecosystem respiration (ER; − 1.9 g O 2 m −2 d −1 ), and net ecosystem production (NEP) approaching autotrophy (− 0. 8 and − 0.3 g O 2 m −2 d −1 ) relative to rivers draining larger, more disturbed catchments (GPP, 1.2 and 2.7 g O 2 m −2 d −1 ; ER, − 5.7 and − 6.9 g O 2 m −2 d −1 ; NEP, − 3.8 and − 3.7 g O 2 m −2 d −1 ). In all rivers, GPP and ER varied seasonally with discharge. The smaller rivers exhibited a distinct pattern of greater and sustained GPP during periods of low discharge, a seasonal metabolic regime we describe as “flow decline.” In general, process–discharge relationships exhibited thresholds, with an initial decline in GPP and ER, with increasing discharge and an increase in ER at higher flows. Relative to larger and more disturbed watersheds, smaller rivers showed a more constrained metabolic fingerprint. Annual NEP (− 1033 and − 641 g C m −2 yr −1 ) in the larger rivers was more negative than the global average, supporting evidence from other studies that tropical rivers are greater contributors to CO 2 emissions than temperate ecosystems. Our study indicates that hydrological seasonality is a major driver of metabolism in tropical rivers.

Cross-canyon variability in zooplankton backscattering strength in a river-influenced upwelling area - Macarena Díaz-Astudillo; Manuel I. Castillo; Pedro A. Figueroa; Leonardo R. Castro; Ramiro Riquelme-Bugueño; Iván Pérez-Santos; Oscar Pizarro; Gonzalo S. Saldías (Ocean Science, 2025)
Zooplankton are a key component of food webs in upwelling systems. Their distribution is influenced not only by mesoscale and climate dynamics but also by topography and local currents. Submarine canyons that incise the continental shelf can act as conduits, transporting deep, nutrient-rich waters to shallower regions and promoting coastal biological productivity. Consequently, these canyons facilitate the advection and accumulation of zooplankton. We aimed to describe the spatio-temporal variability in zooplankton distribution (using net samples and acoustic data) and their association with local currents in a long, narrow submarine canyon located in the highly productive continental shelf off central Chile. The backscattering strength (Sv), a proxy for zooplankton biomass, was highly variable on both diurnal and spatial scales. Higher Sv and abundances were found at night, following the classic diel vertical migration pattern. Zooplankton were not uniformly distributed within the canyon. In the surface and mid-depth layers, the canyon walls accumulated more zooplankton than the center, particularly during the nighttime. Within the canyon, the currents were asymmetrical and frequently reversed direction. When the positive along-canyon current was stronger on the northern slope, Sv was also higher on that wall. This pattern was especially evident in the section closer to the canyon head. We show that the Biobio Canyon is a highly dynamic environment where oceanographic conditions can rapidly shift. Our findings suggest a feasible mechanism for zooplankton retention driven mainly by along-canyon flow asymmetry and vertical migrations.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Fault interactions and subsurface deformation in the Mexicali Valley: Implications for seismic hazard assessment at the México-USA border - Cristian A. Gallegos-Castillo; Mario González-Escobar; Jaime A. Reyes-López; Joann M. Stock; Sergio M. Arregui-Ojeda; Carlos Simón Reyes-Martínez; Edgar A. Mastache-Román (Tectonophysics, 2025)

Agricultural subsidies augmented tropical deforestation in the state of Campeche, Mexico - Edward A. Ellis; David Chacón Castillo; Irving Uriel Hernández Gómez; Sergio Madrid Zubirán; Sara María Cuervo Vega (Forest Policy and Economics, 2025)

Cadmium removal and indole acetic acid production by ureolytic bacteria isolated from rhizosphere soils - Carlos A. Adarme-Duran; Elianna Castillo; Pedro F. B. Brandão (World Journal of Microbiology and Biotechnology, 2025)
This work reports the isolation of 54 ureolytic bacteria with microbiologically induced carbonate precipitation (MICP) activity from Theobroma cacao L. rhizosphere soils with Cd concentration ranging from 0.49 to 21.29 mg kg − 1 . Analysis of the 16 S rRNA gene showed the isolates belong to the genera Serratia , Pseudomonas , Comamonas , Klebsiella , Bacillus , Citrobacter , Flavobacterium , Delftia , and Stenotrophomonas . They showed ureolytic activity between 0.31 and 1.01 µmol NH 4 + mL − 1 h − 1 and produced the phytohormone indole acetic acid (IAA). Interestingly, Cd was observed to increase ureolytic activity and did not affect the IAA production of various isolates. Cadmium removal in solution ranged from 4.4 to 87.0% after 48 h. Strains Serratia sp. 89a, Klebsiella sp. 76 h, and Stenotrophomonas sp. 67w exhibited the best performance (> 80%). Cadmium removal through MICP by the genera Delftia , Flavobacterium , and Klebsiella is reported for the first time. Results suggest the isolated bacteria have the potential for Cd bioremediation and could be used to alleviate metal-induced stress through IAA production.

Interval resonance analysis (InRA): A versatile tool for automated untargeted 1H NMR fingerprinting – A case study in sugar beet field authentication - Cristian A. Fuentes; David Montoya; Mecit Öztop; Macarena Rojas-Rioseco; Martin Bravo; Francisca González; Rosario del P. Castillo (Analytica Chimica Acta, 2025)

Productivity and nutritional quality of pastures in a silvopastoral system under two harvest intervals in southeastern Mexico - Benito B. Dzib-Castillo; Fernando Casanova-Lugo; Dixan Pozo-Leyva; Ricardo L. D. Costa; Laura Macario-González; Flavia M. A. Gimenes; Luis A. Lara-Pérez; Alfonso J. Chay-Canul (Agroforestry Systems, 2025)

Canine eosinophilic pulmonary granulomatosis: Clinical-pathological diagnosis and physiopathology theories - L.X. Bravo-Coello; E. Carrillo-Castillo; A. Cervantes-Arias; M. Juárez-Ramírez; G. Valero-Elizondo (Journal of Comparative Pathology, 2025)

Persistence of frugivorous bats in fragments of high-andean forests: a model of structural equations - Jairo Pérez-Torres; Dennis Castillo-Figueroa; Jorge A. Ahumada (Mammal Research, 2025)

Herbicides in Argentine Pampas Shallow Lakes and Frequency of Testicular Lesions in the Pejerrey Fish (Odontesthes bonariensis) - Nicolás Torres Martínez; Diego Cristos; Ariadna A. Castillo; Gustavo E. Berasain; Pedro Carriquiriborde; Leandro A. Miranda (Bulletin of Environmental Contamination and Toxicology, 2025)

Exploring alternative methods for producing extracts with antioxidant and antimicrobial properties from Cercis siliquastrum L. and safety assessment - Alexandra Spyrou; Laura Gabriela Elvir-Padilla; Alexandra A. Ioannidi; Didilia Ileana Mendoza-Castillo; Adrián Bonilla-Petriciolet; Samir Santzouk; Maria Papadaki; Maria Antonopoulou (Sustainable Chemistry and Pharmacy, 2025)

Strategies for obtaining value-added aromatic amines via lignin-first biorefinery approaches - Antonio A. Castillo-Garcia; Katalin Barta (Current Opinion in Green and Sustainable Chemistry, 2025)

Comparative study of the physicochemical properties of metal organic frameworks in the adsorption of textile dyes - A. N. Pérez-Jasso; I. A. Aguayo-Villarreal; C. K. Rojas-Mayorga; R. Muñiz-Valencia; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Growth characteristics and drought vulnerability of southwest German spruce and pine - Philipp Römer; Edurne Martínez del Castillo; Frederick Reinig; Max C. A. Torbenson; Oliver Konter; Lara Klippel; Ulf Büntgen; Jan Esper (European Journal of Forest Research, 2025)

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Rewilding shows differential fitness of sympatric Physella acuta (Draparnaud, 1805) snail lineages - Kevin A. McQuirk; Juliana M. DeCore; Maria G. Castillo; Coen M. Adema (Aquatic Ecology, 2025)

Latitudinal propagation and solar wind drivers of Pc5 pulsations during the June 2015 geomagnetic storm - J. A. Lazzús; I. Salfate; M. N. Castillo; J. Lorca-Castillo; C. Olivares-Salazar; A. Rivera-Zepeda (Acta Geodaetica et Geophysica, 2025)

Invasive New and Old World freshwater species in isolated springs of the Atacama Desert: implications for native species - Gonzalo A. Collado; Rebeca Carballo; Nicolás Villalobos; Francisco Gómez; Viviana Castillo; Álvaro Alonso (New Zealand Journal of Marine and Freshwater Research, 2025)
Invasive species can significantly alter invaded ecosystems. In this study, we report the presence of two invasive species, the poeciliid fish Poecilia reticulata and the gastropod Melanoides tuberculata , in three isolated springs from the coast of the Atacama Desert in Antofagasta city, northern Chile. Both species were identified through diagnostic morphological features and phylogenetic analysis. This is the first confirmed record of P. reticulata in natural ecosystems of Chile. The finding of M. tuberculata represents the first record of the species in the Antofagasta Region, and the third in the country. Considering the well‐documented adverse effects of both species on invaded ecosystems and their high potential for spread, we recommend the prompt implementation of mitigation measures. These should focus on the direct mechanical removal of these species, given the relatively straightforward sampling process and the relatively small size of the springs. Such measures would significantly contribute to the preservation of native species, particularly those categorized as vulnerable.

Corrigendum to “Characterization of virulence-related phenotypes of Candida parapsilosis and Rhodotorula mucilaginosa isolated from the International Space Station (ISS)” [Life Sciences in Space Research, Volume 45, May 2025, Pages 16-24] - Lauren Wilson; Kaitlyn Nielsen; Stefani Caspasso-Villanueva; Takara O'Brien; Lily A. Hefner; Paulina Slick; Logan Petty; Riley Dienna; Hugo Castillo; Alba Chavez (Life Sciences in Space Research, 2025)

Characterization of virulence-related phenotypes of Candida parapsilosis and Rhodotorula mucilaginosa isolated from the International Space Station (ISS) - Lauren Wilson; Kaitlyn Nielsen; Stefani Caspasso-Villanueva; Takara O'Brien; Lily A. Hefner; Paulina Slick; Logan Petty; Riley Dienna; Hugo Castillo; Alba Chavez (Life Sciences in Space Research, 2025)

Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Setia Sari Girsang; Rowena L. Castillo; Mahyuddin Syam; Zulkifli Zaini; Sunendar Kartaatmadja; Suyamto; Judith Carla Dela Torre; Irish Lorraine B. Pabuayon; Romalene A. Limpiada; Waluyo; Helmi; Samijan; et al. (Field Crops Research, 2025)

Ecophysiological and biochemical responses to cold and heat waves of native Spartina maritima, alien S. densiflora and their reciprocal hybrids - Rosario Álvarez; Salvador A. Fernandez-Gonzalez; Adrián Perera-Bonaño; Alfonso De Cires; Jesús M. Castillo; Blanca Gallego-Tévar (Planta, 2025)
Main conclusion Spartina hybrids outperform parental species, showing transgressive acclimation to extreme climates. Native S. maritima demonstrates high seasonal adaptability and invasive S. densiflora low physiological impact, suggesting resilience under climate change. Abstract Extreme climatic events, such as cold and heat waves, are becoming more frequent, intense, and prolonged due to climate change. Simultaneously, invasive alien plant species are altering the composition of plant communities. Both climate change and the introduction of alien species pose significant threats to biodiversity. We studied the responses of 25 biochemical and physiological functional traits for native Spartina maritima , alien invasive S. densiflora and their reciprocal hybrids to changing environmental conditions during a cold snap in winter and a heat wave in summer in Guadiana Marshes (Southwest Iberian Peninsula). These four closely related taxa responded differently to seasonal environmental fluctuations. Both hybrid taxa, particularly S. maritima × densiflora , exhibited transgressive responses, allowing them to display a wider range of acclimation responses to air temperature compared to their parental species. Native S. maritima also demonstrated a relatively high acclimation capacity to seasonal meteorological changes. In contrast, alien S. densiflora presented few acclimation responses to seasonal environmental changes, responding primarily to sediment salinity rather than to air temperature. Even so, all four studied Spartina taxa appear to be well-adapted to the occurrence of cold and heat waves in the Gulf of Cadiz. These findings underscore the complexity of plant acclimation strategies in response to extreme climatic events and highlight the potential for hybrid taxa to face the future dynamics of salt marshes under climate change.

Structural and functional dynamics of coralline algal systems under warming scenarios: Insights into vulnerability, and resilience - Andrea Bautista-García; Patricia M. Valdespino-Castillo; Teresa Pi-Puig; Fabio Favoretto; Martín Merino-Ibarra; Javier A. Ceja-Navarro; Silvia Espinosa-Matías; Javier Tadeo León; Anidia Blanco-Jarvio (Aquatic Botany, 2025)

A soundscape approach for a short-term acoustic monitoring of a critically endangered Cuban frog - Mariam Curbelo Cruz; Sergio L. del Castillo Domínguez; Leandro Galano Machado; Alejandro Herrera Rodeiro; Carlos A. Mancina; Roberto Alonso Bosch (Biodiversity and Conservation, 2025)

Occurrence of pharmaceuticals in muscle tissue of red drum (Sciaenops ocellatus) across subtropical estuaries: Comparison to blood plasma and implications for human exposure - W. Ryan James; Nicholas A. Castillo; Andy Distrubell; Shakira Trabelsi; Rolando O. Santos; Daniel Cerveny; Ryan J. Rezek; Ross E. Boucek; Aaron J. Adams; Jerker Fick; Tomas Brodin; Jennifer S. Rehage (Science of The Total Environment, 2025)

Comparative design space exploration of centred and off-centred semisubmersible configurations for floating offshore wind turbines - Claudio A. Rodríguez Castillo; Maurizio Collu; Feargal Brennan (Ocean Engineering, 2025)

Pre and post weaning performance of Columbia sheep under an intensive system of the central Mexico: an alternative to enhance meat production - Gabriela Castillo-Hernández; Sandra González-Luna; Laura Castillo-Hernández; Glafiro Torres-Hernández; Jorge A. Maldonado-Jáquez (Tropical Animal Health and Production, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Assessment of a base-isolated structure with semi-active low-cost viscous fluid dampers through real-time hybrid simulations - S. Vides; B. Castillo; A. Artunduaga; J. Marulanda; P. Thomson (Innovative Infrastructure Solutions, 2025)
The dynamic performance of low-rise buildings under dynamic loads presents significant challenges in structural engineering. Accurate evaluation methods are crucial for ensuring the safety and resilience of these structures, especially in seismic-prone areas. This study focuses on implementing Real-Time Hybrid Simulations (RTHS) for the assessment of structural control systems in low-rise buildings. The research integrates a numerical substructure, which models the dynamic characteristics of the building, with an experimental substructure that consists of physical devices such as base isolators, semi-active fluid viscous dampers, or hybrid control system. The RTHS method provides a sophisticated platform to evaluate the effectiveness of hybrid control systems under seismic excitations. The results demonstrated a marked improvement in predicting structural responses, with the proposed method achieving a 15.0% reduction in error compared to fixed structure. Additionally, the application of hybrid control systems showed a 25.0% increase in energy dissipation capacity compared to individual passive control. These findings contribute to the advancement of resilient design strategies, offering a quantitative framework for optimizing structural control systems in low-rise buildings.

A dynamic capabilities framework for building circular ecosystems by focal firms - Dánika A. Castillo-Ospina; Marta Ormazabal; Leonardo de Vasconcelos Gomes; Aldo Roberto Ometto (Sustainable Production and Consumption, 2025)

Coastal zooplankton in the Palmer Archipelago, Western Antarctica Peninsula: Influence of environmental conditions at short-term scale during austral summer - Benjamín Rodríguez-Stepke; Claudia Morales; Manuel I. Castillo; Ángela Rodríguez; Manuel I. Castillo; César A. Cárdenas; Mario La Mesa; Mathias Hüne; Mauricio F. Landaeta (Journal of Marine Systems, 2025)

Characterization of Surface and Bottom Longline Artisanal Shark Fisheries in the Northern Gulf of Tehuantepec, Mexico - Cristina Celaya-Castillo; Emilio I. Romero-Berny; Felipe Galván-Magaña; Jesús M. López-Vila; Wilfredo A. Matamoros (Thalassas: An International Journal of Marine Sciences, 2025)

Basin Style Variation Along a Transform Fault: Southern Colorado River Delta, Baja California, México - Mario González-Escobar; Carlos Simón Reyes-Martínez; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román (Pure and Applied Geophysics, 2025)

Effect of pH, temperature and adsorbent mass on Cr (VI) adsorption in residues from a coal washing plant - Aime J. Garcia-Lugo; Jorge C. Ríos-Hurtado; Gloria I. Dávila-Pulido; Adrián A. González-Ibarra; Fatima P. Lara-Castillo; Sergio E. Flores-Villaseñor (Environmental Geochemistry and Health, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Discovering Hidden Archaeal and Bacterial Lipid Producers in a Euxinic Marine System - Dina Castillo Boukhchtaber; F. A. Bastiaan von Meijenfeldt; Diana X. Sahonero Canavesi; Denise Dorhout; Nicole J. Bale; Ellen C. Hopmans; Laura Villanueva (Environmental Microbiology, 2025)
Bacterial membrane lipids are typically characterised by fatty acid bilayers linked through ester bonds, whereas those of Archaea are characterised by ether‐linked isoprenoids forming bilayers or monolayers of membrane‐spanning lipids known as isoprenoidal glycerol dialkyl glycerol tetraethers (isoGDGTs). However, this understanding has been reconsidered with the identification of branched GDGTs (brGDGTs), which are membrane‐spanning ether‐bound branched alkyl fatty acids of bacterial origin, though their producers are often unidentified. The limited availability of microbial cultures constrains the understanding of the biological sources of these membrane lipids, thus limiting their use as biomarkers. To address this issue, we identified membrane lipids in the Black Sea using high‐resolution accurate mass/mass spectrometry and inferred their potential producers by targeting lipid biosynthetic pathways encoded on the metagenome, in metagenome‐assembled genomes and unbinned scaffolds. We also identified brGDGTs and highly branched GDGTs in the suboxic and euxinic waters, potentially attributed to Planctomycetota, Cloacimonadota, Desulfobacterota, Chloroflexota, Actinobacteria and Myxococcota—based on their lipid biosynthetic genomic potential. These findings introduce new possibilities for using specific brGDGTs as biomarkers of anoxic conditions in marine environments and highlight the role of these membrane lipids in microbial adaptation.

Widespread contamination of the Pacific upper mantle during the mid-Cretaceous - K. Durkin; P.R. Castillo; S.M. Straub; S. Mallick; A. Saal; J.K. Muller (Marine Geology, 2025)

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

Photoperiod and Light Spectrum Modulate Daily Rhythms and Expression of Genes Involved in Cell Proliferation, DNA Repair, Apoptosis and Oxidative Stress in a Seabream Embryonic Stem Cell Line - Alba Vergès-Castillo; Patricia Herrera-Pérez; Carlos Pendón; Águeda J. Martín-Robles; José A. Muñoz-Cueto (Marine Biotechnology, 2025)
The use of cell lines as alternative models for environmental physiology studies opens a new window of possibilities and is becoming an increasingly used tool in marine research to fulfil the 3R’s rule. In this study, an embryonic monoclonal stem cell line obtained from a marine teleost (gilthead seabream, Sparus aurata ) was employed to assess the effects of photoperiod (light/dark cycles vs constant dark) and light spectrum (white, blue, green, blue/green and red lights) on gene expression and rhythms of cellular markers of proliferation, DNA repair, apoptosis and cellular/oxidative stress by RT-qPCR and cosinor analyses. The results obtained revealed the optimal performance of cells under blue light (LDB), with all the genes analysed showing their highest RNA expression levels and most robust daily variations/rhythms in this condition. Under LDB, the mRNA levels of cell proliferation ( pcna ), DNA repair ( cry5 ), anti-apoptotic ( bcl2 ) and oxidative stress ( prdx2 ) markers peaked at the day-night transition, whereas pro-apoptotic ( bax ) and cell stress ( hsp70 ) markers showed their highest expression at the night-day transition, evidencing the strong synchronisation of the transcription of key genes involved in the cell cycle in this photoregime. The persistence of significant pcna , cry5 , hsp70 and prdx2 rhythms after 3 days in constant darkness reveals the endogenous and circadian nature of these rhythms. Our results highlight the importance of implementing photoperiods with light–dark cycles of blue wavelengths when performing fish cell culture research. These results reinforce and extend our previous studies, confirming the importance of lighting conditions that mimic the natural environment for the proper development of fish embryos and larvae in aquaculture.

Methodological considerations for assessing SmO2 reproducibility and its applications in sports sciences - Alexia Ruiz-Olvera; Alberto Blanco-Salazar; Danna A. Corral-Castillo; Marco A. Hernández-Lepe; Isaac A. Chavez-Guevara (European Journal of Applied Physiology, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Revealing the geochemical factors controlling the distribution of island and archipelago asphaltenes in crude oils through the study of A1 and A2 subfractions - Miguel Orea; María A. Ranaudo; Liliana López; Vicmary Vargas; Jimmy Castillo; Brice Bouyssiere; Sócrates Acevedo (Fuel, 2025)

Multiscale analysis of the M1 MoVNbTeO catalyst for ethylene production via selective ethane oxidation: From atomistic calculations to the industrial reactor - José G. Rivera; Martin A. Purino; José F. Durán; Carlos Alvarado; Alberto Hernandez; Maarten K. Sabbe; Carlos O. Castillo-Araiza (Chemical Engineering Journal, 2025)

Early‐Stage Extratropical Cyclones' Mechanisms Over South America: RCM Added Value and Future Changes in a Warmer Planet - Carolina B. Gramcianinov; Andressa A. Cardoso; Natália P. da Silva; Rosa Luna‐Niño; Natalia Castillo; Tereza Cavazos; Rosmeri P. da Rocha (International Journal of Climatology, 2025)
Regional climate models (RCMs) from the CORDEX enable further investigations of the regional aspects of climate change impacts in South America. Here, we assess the CORDEX‐RCMs' present and future projections of extratropical cyclones, focusing on their frequency, early‐stage synoptic features, and added value relative to the global climate models (GCMs). Cyclones were tracked using a common algorithm in the present (1985–2005) and future RCP8.5 scenarios (2080–2099). ERA5 reanalysis was used as reference data in the present climate. Both GCMs and RCMs can identify the three major cyclone hot spots in South America: Argentina (ARG), La Plata Basin (LPB), and the south‐southeast Brazilian coast (SBR). RCMs improve GCMs' representation of the cyclogenesis frequency, adding value by decreasing the biases (~10%). Early‐stage cyclone synoptic structure also indicates RCMs' improvement of the low‐level fields by presenting mesoscale structures of warm/cold advection and moisture flux convergence/divergence in greater agreement with ERA5 (except for moisture flux divergence for LPB). RCMs and GCMs project a general decrease in cyclogenesis for the end of the century. For the cyclogenesis cores, GCMs' and RCMs' projections agree on the trend signals in SBR, LPB, and ARG in austral winter and disagree in ARG in austral summer. For LPB and SBR cyclogenesis, the RCMs and GCMs suggest a future increase in moisture flux convergence and warm advection at low levels, while a decrease in upper level divergence is projected. This indicates a reinforcement of cyclogenesis (negative sea‐level pressure trend) in the future due to the low‐level features and associated diabatic processes. For ARG, the future trends in the mean structure of cyclogenesis are relatively weak. Following other studies, cyclogenesis frequency may decrease; however, changes could occur in some important physical processes, such as low‐level moisture flux convergence and warm advection, suggesting more intense events in the future.

Small-scale geographic differences in multiple-driver environmental variability can modulate contrasting phenotypic plasticity despite high levels of gene flow - Nicole Castillo; Juan Diego Gaitán-Espitia; Julian F. Quintero-Galvis; Gonzalo S. Saldías; Sebastián I. Martel; Marco A. Lardies; Andrés Mesas; Iván E. Pérez-Santos; Stefan Gelcich; Cristian A. Vargas (Science of The Total Environment, 2024)

Interfacial behaviour of human bile and its substitution for in vitro lipolysis studies - Dorota Dulko; Ilona E. Kłosowska-Chomiczewska; Teresa del Castillo-Santaella; Miguel A. Cabrerizo-Vílchez; Justyna Łuczak; Robert Staroń; Łukasz Krupa; Julia Maldonado-Valderrama; Adam Macierzanka (Food Research International, 2024)

Green coffee extracts microencapsulated by spray freezing into the liquid cryogenic - Jaime López-Domínguez; Maria Teresa González-Arnao; Cesar A. Ortíz-Sánchez; Marisol Castillo-Morales; Martha P. Rascón-Díaz; Ubaldo R. Marin-Castro (Cryobiology, 2024)

Morphospace of lanternfish larvae and their interplay with oceanographic conditions from the southeastern Pacific Ocean - Fernanda S. Orrego; Hugo A. Benítez; Manuel I. Castillo; Nicolás Cumplido; Alejandra Fabres; Yanara Figueroa-González; Claudia Morales; Francisca Zavala-Muñoz; Mauricio F. Landaeta (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

A holistic simulation model of solid-set sprinkler irrigation systems for precision irrigation - M. Morcillo; J. F. Ortega; R. Ballesteros; A. del Castillo; M. A. Moreno (Precision Agriculture, 2024)

Cadmium availability in rhizosphere and non-rhizosphere soils in cacao farms in Santander, Colombia - C. A. Adarme-Duran; J. Ágreda; P. F. B. Brandão; E. Castillo (Environmental Monitoring and Assessment, 2024)
Current research has highlighted the need to understand the factors influencing cadmium (Cd) availability in cacao-growing soils to elucidate its presence in cacao beans (the raw material for chocolate). Although literature about this topic is increasing, few report the importance of rhizosphere soils on Cd dynamics. This study aimed to understand the changes in available Cd and its association with soil properties (pH, pseudo-total Cd, available Cd (Cd-DTPA), Ca, Mg, K, Na, soil organic carbon, P, Zn, urease activity, exchangeable acidity, and cation exchange capacity) considering rhizosphere and non-rhizosphere soils. Both soil types (51 samples of each, 102 in total) were collected from two Colombian cacao farms. The medians of pseudo-total Cd (1.86 mg kg −1 ) and Cd-DTPA (0.76 mg kg −1 ) were, respectively, about threefold and fourfold higher in rhizosphere compared to non-rhizosphere soils. Principal component analysis showed a clear distinction between rhizosphere and non-rhizosphere soils based on differences in soil properties, which explained the observed changes in available Cd when comparing both soil types. Soil organic carbon and Zn were important drivers of available Cd in rhizosphere soils. Spatial distribution analysis revealed a tendency of available Cd to cluster in rhizosphere soils, and indicated hotspots within each farm. These findings highlight the importance of rhizosphere soils for Cd diagnosis and monitoring, and for improving knowledge about Cd dynamics in the soil- Theobroma cacao L. system.

Mechanisms of action of coffee bioactive compounds – a key to unveil the coffee paradox - Fernanda Machado; Manuel A. Coimbra; Maria Dolores del Castillo; Filipe Coreta-Gomes (Critical Reviews in Food Science and Nutrition, 2024)

Interactive impact of residual pyrethroid compounds used in the Chilean salmon farming industry and coastal acidification conditions on the feeding performance of farmed mussels in northern Patagonia - Adonis Conejeros; Valeska A. San Martin; Nicole Castillo; L. Antonio Cuevas; Karen Garcés; Ricardo O. Barra; Victor M. Aguilera; Cristian A. Vargas (Marine Environmental Research, 2024)

Theoretical and experimental study of adsorption and catalytic reactivity of asphaltene fractions A1 and A2 over cubic NiO–PdO/CeO2 nanoparticles - Oscar E. Medina; Ivan Moncayo Riascos; Samira Heidari; Sócrates A. Acevedo; Jimmy Castillo; Farid B. Cortés; Camilo A. Franco (Fuel, 2024)

Contrasting Future Growth of Norway Spruce and Scots Pine Forests Under Warming Climate - Edurne Martinez del Castillo; Max C. A. Torbenson; Frederick Reinig; Ernesto Tejedor; Martín de Luis; Jan Esper (Global Change Biology, 2024)
Forests are essential to climate change mitigation through carbon sequestration, transpiration, and turnover. However, the quantification of climate change impacts on forest growth is uncertain and even contradictory in some regions, which is the result of spatially constrained studies. Here, we use an unprecedented network of 1.5 million tree growth records from 493 Picea abies and Pinus sylvestris stands across Europe to predict species‐specific tree growth variability from 1950 to 2016 ( R 2 > 0.82) and develop 21st‐century gridded projections considering different climate change scenarios. The approach demonstrates overall positive effects of warming temperatures leading to 25% projected conifer growth increases under the SPP370 scenario, but these additional carbon gains are spatially inhomogeneous and associated with geographic climate gradients. Maximum gains are projected for pines in Scandinavia, where growth trajectories indicate 50% increases by 2071–2100. Smaller but significant growth reductions are projected in Mediterranean Europe, where conifer growth shrinks by 25% in response to warmer temperatures. Our results reveal potential mitigating effects via forest carbon sequestration increases in response to global warming and stress the importance of effective forest management.

Influence of coastal oceanography on early life history traits of larval Patagonian sprat, Sprattus fuegensis along southeastern Pacific Ocean - Erika López‐Soto; Gillian Ord; Manuel I. Castillo; Guido Plaza; Mario A. Cáceres; María Teresa González; Maritza Sepúlveda; Alicia I. Guerrero; Andrea Piñones; Mauricio F. Landaeta (Fisheries Oceanography, 2024)
Early life history traits of small pelagic fish are usually affected by environmental conditions. Patagonian sprat, Sprattus fuegensis , is a small pelagic fish that inhabits the continental shelf, fjords and channels of Patagonia. Their larvae are usually exposed to large variations in physical and biological conditions. We evaluated the effects of environmental conditions on early life history traits of this key species encompassing over 20 years of information. The characterization of oceanographic features, larval abundance and distribution was carried out in western Patagonia between 1996 and 2019, while the growth and mortality rates were estimated for the austral spring 2019 between 49°54′S and 53°55′S. Larval abundance decreased three to ten times from 1996 to 1997 to the rest of the study period (2008–2010 and 2014–2019), with larger abundances being found over the shelf. In spring 2019, the growth rate was 0.20 ± 0.05 mm d −1 for larvae between 9 and 19 days after hatching. The growth rate was similar in partially stratified (7–50 J m −3 ) and stratified waters (50–100 J m −3 ), but slower in mixed waters ( −3 ). GAM modelling showed that the faster larval growth occurred in partially stratified waters with temperatures above 7.5°C. Natural mortality rates were higher in partially stratified waters (24% of daily loss), lower in stratified areas (14%) and the lowest in the mixed water column (12%). Accordingly, larvae living in channels had faster growth rates but higher daily mortality, while those that hatched or were advected to water parcels on the continental shelf had slower growth but lower daily mortality. Finally, these latter traits may be an example of an inverse growth‐selective survival strategy.

Extraction of bio-hydroxyapatite from devilfish (Loricariidae) for the fluoride and cadmium adsorption from water and its feasible photocatalytic properties - Hilda G. Cisneros-Ontiveros; Luis F. Zubieta-Otero; Nahum A. Medellín-Castillo; Alfredo I. Flores-Rojas; Mario E. Rodriguez-Garcia (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

New study of the adsorption mechanism of different dye molecules by high porous sludge activated carbon produced from a dairy-treatment effluent plant - Angélica F.M. Streit; Hercules A. Pereira; Jaime Moreno-Pérez; Didilia I. Mendoza-Castillo; Hilda E. Reynel-Ávila; Kátia da Boit Martinello; Luis F.O. Silva; Naushad Ahmad; Sonaimuthu Mohandoss; Adrián Bonilla-Petriciolet; Guilherme L. Dotto (Journal of Environmental Chemical Engineering, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Biodiversity of octopuses in the Americas - Roberto González-Gómez; Otilio Avendaño; Irene de los Angeles Barriga-Sosa; Penélope Bastos; Claudia Caamal-Monsreal; Gabriela Castillo-Estrada; Celso Cedillo-Robles; Adam Daw; Mariana Díaz-Santana-Iturrios; Gabriela Galindo-Cortes; Jürgen Guerrero-Kommritz; Manuel Haimovici; et al. (Marine Biology, 2024)

The influence of seawater pCO2 and temperature on the amino acid composition and aragonite CO3 disorder of coral skeletons - Nicola Allison; Phoebe Ross; Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Celeste Kellock; Catherine Cole; Matthieu Clog; David Evans; Chris Hintz; Ken Hintz; Adrian A. Finch (Coral Reefs, 2024)
Coral skeletons are composites of aragonite and biomolecules. We report the concentrations of 11 amino acids in massive Porites spp. coral skeletons cultured at two temperatures (25 °C and 28 °C) and 3 seawater pCO 2 (180, 400 and 750 µatm). Coral skeletal aspartic acid/asparagine (Asx), glutamic acid/glutamine (Glx), glycine, serine and total amino acid concentrations are significantly higher at 28 °C than at 25 °C. Skeletal Asx, Glx, Gly, Ser, Ala, L-Thr and total amino acid are significantly lower at 180 µatm seawater pCO 2 compared to 400 µatm, and Ser is reduced at 180 µatm compared to 750 µatm. Concentrations of all skeletal amino acids are significantly inversely related to coral calcification rate but not to calcification media pH. Raman spectroscopy of these and additional specimens indicates that CO 3 disorder in the skeletal aragonite lattice is not affected by seawater pCO 2 but decreases at the higher temperature. This is contrary to observations in synthetic aragonite where disorder is positively related to the aragonite precipitation rate mediated by either increasing temperature (this study) or increasing Ω (this study and a previous report) and to the concentration of amino acid in the precipitation media (a previous report). We observe no significant relationship between structural disorder and coral calcification rate or skeletal [amino acid]. Both temperature and seawater pCO 2 can significantly affect skeletal amino acid composition, and further work is required to clarify how environmental change mediates disorder.

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

A functional light-entrainable molecular clock is revealed in gilthead seabream (Sparus aurata) from early developmental stages using an embryonic stem cell line - Alba Vergès-Castillo; José A. Muñoz-Cueto; Javier Durán-Sáez; Carlos Pendon; Águeda J. Martín-Robles (Aquaculture, 2024)

Public policy instruments coherence analysis to address coastal risk in Yucatan, Mexico - L. Vidal-Hernández; A. Cuevas-Jiménez; D. de Yta-Castillo; V.S. Ávila-Foucat; Ileana Espejel (Marine Policy, 2024)

P26-01 Hexagonal boron nitride (hBN) and hBN-reinforced thermoplastic polyurethane composite: an in vitro hazard characterization using human skin and lung cells - M. Carlin; J. Kaur; D.Z. Ciobanu; Z. Song; M. Olsson; T. Totu; G. Gupta; G. Peng; V. Jehová González; I.J. Janica; V. Fuster Pozo; S. Chortarea; et al. (Toxicology Letters, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Enablers for circular ecosystem transformation: A multi-case study of Brazilian circular ecosystems - Leonardo Augusto de Vasconcelos Gomes; Aline Sacchi Homrich; Ana Lucia Figueiredo Facin; Lucas Emmanuel Nascimento Silva; Danika A. Castillo-Ospina; Adriana Hofmann Trevisan; Aldo Roberto Ometto; Janaina Mascarenhas; Marly Monteiro Carvalho (Sustainable Production and Consumption, 2024)

Adsorption of amine surfactants onto kaolinite: A multiscale investigation - J. Lainé; Y. Foucaud; J.W. Hounfodji; P. Pelée de Saint-Maurice; A. Bonilla-Petriciolet; D.I. Mendoza-Castillo; H. Turrer; M. Badawi (Minerals Engineering, 2024)

Diversity and structure of prokaryotic assemblages in a thermally stratified tropical lake - Jesús Torres-Huesca; Jazmín Santillán; Yislem Beltrán; Rafael A. López-Martínez; Miroslav Macek; Luisa I. Falcón; Martín Merino-Ibarra; Patricia M. Valdespino-Castillo; Jesús T. Martínez-Díaz; Javier Alcocer; Rocío J. Alcántara-Hernández (Limnologica, 2024)

Identifying pathways of pharmaceutical exposure in a mesoconsumer marine fish - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; S. Trabelsi; A. Distrubell; M. Sandquist; J. Fick; T. Brodin; et al. (Journal of Hazardous Materials, 2024)

Techno economic and life cycle assessment of olefin production through CO2 hydrogenation within the power-to-X concept - Gabriela A. Cuevas-Castillo; Stavros Michailos; Muhammad Akram; Kevin Hughes; Derek Ingham; Mohamed Pourkashanian (Journal of Cleaner Production, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Myeloid Cell Reservoirs: Role in HIV-Host Interplay and Strategies for Myeloid Reservoir Elimination - Amber A. Castillo; Corbin McElrath; Grace Marshall; Mario Stevenson (Current Clinical Microbiology Reports, 2024)
Purpose of Review Despite host antiviral responses and antiretroviral therapy, HIV-1 continues to persist in myeloid cell reservoirs. Hence, strategies that promote the elimination of myeloid reservoirs are critically needed. Insight into host-HIV interactions is key to achieving a cure. Recent Findings Host antiviral factors are often antagonized by HIV proteins that help establish infection while promoting chronic inflammation and disease in the host. Currently, several methods to eliminate the virus are under investigation including broadly neutralizing antibodies, latency reversal agents, CRISPR platforms, and immune modulation. Compounds that can penetrate the blood brain barrier are also being developed for reservoir cell clearance. Summary Here, we will outline features of myeloid cell biology and host-virus interactions that facilitate HIV persistence. We will also review current therapeutic strategies and potential drug candidates to cure HIV infection of myeloid cells even in difficult-to-treat tissues such as the central nervous system.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

B(OH)4− and CO32− do not compete for incorporation into aragonite in synthetic precipitations at pHtotal 8.20 and 8.41 but do compete at pHtotal 8.59 - Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Adrian A. Finch; Matthieu Clog; Ed Hathorne; Nicola Allison (Geochimica et Cosmochimica Acta, 2024)

Exploring proteasome inhibition using atomic weighted vector indices and machine learning approaches - Yoan Martínez-López; Juan A. Castillo-Garit; Gerardo M. Casanola-Martin; Bakhtiyor Rasulev; Ansel Y. Rodríguez-Gonzalez; Oscar Martínez-Santiago; Stephen J. Barigye (Molecular Diversity, 2024)

Genetic (co)variation for resistance to white spot syndrome virus, acute hepatopancreatic necrosis, and overall pond survival in Litopenaeus vannamei - Reyes López-Ordaz; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Bruno Gómez-Gil; Sonia A. Soto Rodríguez; Alfonso Martínez Ortega; Juan C. Quintana-Casares; Héctor Castillo-Juárez; Gabriel R. Campos-Montes (Aquaculture International, 2024)

Characterizing phenotypic data of Peromyscus leucopus compared to C57BL/6J Mus musculus and diversity outbred (DO) Mus musculus - Lauren A. Wimer; Asia Davis-Castillo; Sofiya Galkina; Serban Ciotlos; Cavan Patterson; Leandro Prado; Maria Castro Munoz; Nicolas Martin; Sharon Epstein; Nicholas Schaum; Simon Melov (GeroScience, 2024)
Translational research is commonly performed in the C57B6/J mouse strain, chosen for its genetic homogeneity and phenotypic uniformity. Here, we evaluate the suitability of the white-footed deer mouse ( Peromyscus leucopus ) as a model organism for aging research, offering a comparative analysis against C57B6/J and diversity outbred (DO) Mus musculus strains. Our study includes comparisons of body composition, skeletal muscle function, and cardiovascular parameters, shedding light on potential applications and limitations of P. leucopus in aging studies. Notably, P. leucopus exhibits distinct body composition characteristics, emphasizing reduced muscle force exertion and a unique metabolism, particularly in fat mass. Cardiovascular assessments showed changes in arterial stiffness, challenging conventional assumptions and highlighting the need for a nuanced interpretation of aging-related phenotypes. Our study also highlights inherent challenges associated with maintaining and phenotyping P. leucopus cohorts. Behavioral considerations, including anxiety-induced responses during handling and phenotyping assessment, pose obstacles in acquiring meaningful data. Moreover, the unique anatomy of P. leucopus necessitates careful adaptation of protocols designed for Mus musculus . While showcasing potential benefits, further extensive analyses across broader age ranges and larger cohorts are necessary to establish the reliability of P. leucopus as a robust and translatable model for aging studies.

Nanoencapsulation of extracts and isolated compounds of plant origin and their cytotoxic effects on breast and cervical cancer treatments: Advantages and new challenges - Gloria A. Guillén-Meléndez; Raymundo A. Pérez-Hernández; Abelardo Chávez-Montes; Uziel Castillo-Velázquez; María de Jesús Loera-Arias; Carlos R. Montes-de-Oca-Saucedo; Humberto Rodríguez-Rocha; Flavio F. Contreras-Torres; Odila Saucedo-Cárdenas; Adolfo Soto-Domínguez (Toxicon, 2024)

Habitat of two threatened short-tailed whip-scorpions (Arachnida: Schizomida) in the tropical Andes of Northern South America - Dennis Castillo-Figueroa; Camilo Castillo-Avila; Jairo A. Moreno-González; Juan M. Posada (Journal of Insect Conservation, 2024)
Aim Schizomids are one of the less-known arachnid groups in terms of their natural history and ecology. However, due to their remarkable short-range endemic distribution, they may be vulnerable to climate change and habitat loss. In Colombia, although the national IUCN red list of threatened invertebrates has categorized species of schizomids as vulnerable (VU), this assessment was based on expert criteria. Therefore, information about the ecology of schizomids is critical for a more accurate reassessment of their conservation status. In this study, we describe the habitat of two species of Surazomus in endangered Andean tropical forests of Colombia after a sampling effort of 15.12 m 2 (n = 168 soil samples) and the collection of 6999 soil fauna individuals from the samples. We analyzed soil fauna communities associated with schizomids as well as different forest and environmental variables from permanent plots installed a decade ago in the Sabana de Bogotá region. Detailed information on climate, plant communities, and forest structure was obtained from these plots. Thus, we provide the first comprehensive habitat description of schizomids including both above- and belowground compartments. We found that each species lives in specific habitats with different soil fauna communities, suggesting a potential association between geographical fidelity and habitat conditions. This result could indicate that schizomids are highly sensitive to dramatic environmental changes, such as those experienced in the Andean region of Colombia. Implications for insect conservation Our study is valuable for the future reassessment of the conservation status of schizomids in the country, particularly considering that the previous categorization was based on expert criteria. Since habitat conditions and soil fauna communities are species-specific, schizomids could be disproportionately vulnerable to climate change and human disturbances in the Colombian Andes.

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

Antioxidant and flexible bioplastics based on microwave-assisted extracted coffee fruit cascara pectic polysaccharides - Gonçalo Oliveira; Sílvia Petronilho; Kamila Kapusniak; Janusz Kapusniak; Maria Dolores del Castillo; Manuel A. Coimbra; Paula Ferreira; Cláudia P. Passos; Idalina Gonçalves (Journal of Cleaner Production, 2024)

Removal of Nitrates in Drinking Water Polluted with Landfill Leachate by an Electrocoagulation System with Mg-Zn - Miriam A. García-Colindres; Brenda Lissette Requena-Alvarez; Luis Antonio Castillo-Suárez; Ivonne Linares-Hernández; Verónica Martínez-Miranda (Water, Air, & Soil Pollution, 2024)

Disseminated cutaneous non-epitheliotropic B-cell lymphoma associated with a fracture site in a cat - M. Saravia-Castro; A. Reyes-Matute; A. Cervantes-Arias; D.d.J. Ruiz-Castillo (Journal of Comparative Pathology, 2024)

Multicentric cutaneous histiocytic proliferation resembling Langerhans cell histiocytosis in a howler monkey (Allouata palliata) - A. Reyes-Matute; Y.A. Basilio-Cornejo; G.Y. Castillo-Mendoza; A.C. Negrete-Philippe (Journal of Comparative Pathology, 2024)

Climate-driven change and conservation of threatened satyrine butterflies in cloud forests of southern Mexico - Laura I. Moguel-Cárdenas; Jorge L. León-Cortés; Oliver Rodríguez-Aguilar; Alfredo Castillo-Vera; Gerald A. Islebe (Journal of Insect Conservation, 2024)

Denim washing wastewater treatment by coupling coagulation–flocculation/Fe-garnet filtration: life cycle assessment and the fertilization with the sludge - Y. Robles-Bueno; L. A. Castillo-Suárez; I. Linares-Hernández; V. Martínez-Miranda; L. Garduño-Pineda; C. Alanis; R. Natividad (International Journal of Environmental Science and Technology, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Optimization of cost-effective enzymatic saccharification using low-cost protic ionic liquid as pretreatment agent in Agave bagasse - Jose A. Pérez-Pimienta; Damián J. Castillo-Preciado; Víctor González-Álvarez; Hugo O. Méndez-Acosta (Waste Management, 2024)

Role of indigenous microbial communities in the mobilization of potentially toxic elements and rare-earth elements from alkaline mine waste - S. Cebekhulu; A. Gómez-Arias; A. Matu; J. Alom; A. Valverde; M.A. Caraballo; O. Ololade; P. Schneider; J. Castillo (Journal of Hazardous Materials, 2024)

The power of on-farm data for improved agronomy - Ignacio Macedo; Cameron M. Pittelkow; José A. Terra; Jesús Castillo; Alvaro Roel (Global Food Security, 2024)

The importance of assets for coping with COVID-19 and other shocks - Julio A. Berdegué; María J. Castillo; Ileana Gómez; Gustavo Gordillo; José Navea; Irvin Rojas; Rodrigo Yáñez (Global Food Security, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

Associations between urban greenspace and depressive symptoms in Mexico's cities using different greenspace metrics - Maryia Bakhtsiyarava; Yang Ju; Mika Moran; Daniel A. Rodríguez; Iryna Dronova; Xavier Delclòs-Alió; Kari Moore; Marianela Castillo-Riquelme; Cecilia Anza-Ramirez (Applied Geography, 2024)

Gravimetric survey and modelling of a tectonic indenter boundary: The Palomares Fault Zone (Betic Cordillera, Iberia) - V. Tendero-Salmerón; G. Ercilla; L. González-Castillo; A. Madarieta-Txurruka; F.J. Martínez-Moreno; F. Estrada; J. Galindo-Zaldivar (Tectonophysics, 2024)

Microplastics on sandy beaches of Chiapas, Mexico - Khirbet López-Velázquez; Kevin G. Duque-Olivera; David A. Santiago-Gordillo; Edwin R. Hoil-Canul; Jorge L. Guzmán-Mar; Minerva Villanueva-Rodríguez; José G. Ronderos-Lara; Cesar Castillo-Quevedo; José L. Cabellos-Quiroz (Regional Studies in Marine Science, 2024)

Ontogeny of interxylary phloem and stem anatomy of the Cuban endemic Henleophytum (Malpighiaceae) - Angélica Quintanar-Castillo; Pedro A. González Gutiérrez; Marcelo R. Pace (Flora, 2024)

Mantle-hosted ophiolitic chromitites from Colombia: implications for petrogenesis and geodynamic evolution - Carlos A. Ramírez-Cárdenas; Núria Pujol-Solà; Joaquín A. Proenza; Marion Weber; Montgarri Castillo-Oliver; Mónica Tobón; Antonio Garcia-Casco (International Geology Review, 2024)

Microplastics as vectors of other contaminants: Analytical determination techniques and remediation methods - Maria Veronica Zambrano-Pinto; Rolando Tinizaray-Castillo; María A. Riera; Naga Raju Maddela; Rafael Luque; Joan Manuel Rodríguez Díaz (Science of The Total Environment, 2024)

The added value of partnerships in implementing the UN sustainable development goals - Walter Leal Filho; Thais Dibbern; Maria Alzira Pimenta Dinis; Evandro Coggo Cristofoletti; Marcellus Forh Mbah; Ashish Mishra; Amelia Clarke; Naima Samuel; Julen Castillo Apraiz; Ismaila Rimi Abubakar; Yusuf A. Aina (Journal of Cleaner Production, 2024)

Insights into the response of coral biomineralisation to environmental change from aragonite precipitations in vitro - Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Adrian A. Finch; Matthieu Clog; Alex Brasier; John Still; Nicola Allison (Geochimica et Cosmochimica Acta, 2024)

A novel approach for improving the spatiotemporal distribution modeling of marine benthic species by coupling a new GIS procedure with machine learning - Iván. F. Benavides Martínez; Mario Rueda; Omar Olimpo Ortíz Ferrin; Javier A. Díaz-Ochoa; Sergio Castillo-Vargasmachuca; John Josephraj Selvaraj (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Ecological indicators and source diagnostic ratios of aliphatic and polyaromatic hydrocarbons in marine sediments of Qatar - Maryam A. Abdulla; Azenith B. Castillo; Christopher Collins; Tom Sizmur (Regional Studies in Marine Science, 2023)

An evaluation of eight global ocean reanalyses for the Northeast U.S. Continental shelf - Alma Carolina Castillo-Trujillo; Young-Oh Kwon; Paula Fratantoni; Ke Chen; Hyodae Seo; Michael A. Alexander; Vincent S. Saba (Progress in Oceanography, 2023)

Effects of dietary supplementation with L-arginine on the endogenous losses of amino acids in growing pigs exposed to heat stress - Adriana Morales; José A. Valle; Gilberto Castillo; Fernanda González; Cecilia Hernández; Néstor Arce; John K. Htoo; Miguel Cervantes (Journal of Thermal Biology, 2023)

Leaching tests reveal fast aluminum fluoride release from ashfall accumulated in La Palma (Canary Islands, Spain) after the 2021 Tajogaite eruption - J. Sánchez-España; M. Pilar Mata; J. Vegas; G. Lozano; J. Mediato; J. Martínez Martínez; I. Galindo; N. Sánchez; B. del Moral; B. Ordóñez; A. de Vergara; A. Nieto; et al. (Journal of Volcanology and Geothermal Research, 2023)

An exploration of customers’ perceptions, preferences, experiences, and feasibility of offering standardized portions in restaurants - Titilola Labisi; Melissa Preciado; Allison Voorhees; Amorette Castillo; Kelly Lopez; Christina Economos; Mary Story; Deborah A. Cohen (International Journal of Gastronomy and Food Science, 2023)

Application of segmented analysis via multivariate curve resolution with alternating least squares to 1H-nuclear magnetic resonance spectroscopy to identify different sugar sources - Cristian A. Fuentes; Mecit Halil Öztop; Macarena Rojas-Rioseco; Martín Bravo; Aylin Özgür Göksu; Marena Manley; Rosario del P. Castillo (Food Chemistry, 2023)

Surface activity of protein extracts from seed oil by-products and wettability of developed bioplastics - Seyedeh Fatemeh Mirpoor; Pablo F. Ibáñez-Ibáñez; C. Valeria L. Giosafatto; Teresa del Castillo-Santaella; Miguel A. Rodríguez-Valverde; Julia Maldonado-Valderrama (Food Hydrocolloids, 2023)

Assessing earlywood-latewood proportion influence on tree-ring stable isotopes - M.C.A. Torbenson; U. Büntgen; P. Römer; O. Urban; M. Trnka; A. Ač; F. Reinig; M. Rybníček; T. Kolář; T. Arosio; E. Martinez del Castillo; E. Koňasová; et al. (Dendrochronologia, 2023)

Decoupling of short-lived radiogenic and helium isotopes in the Marquesas hotspot - M.-T. Herret; B.J. Peters; D. Kim; P.R. Castillo; A. Mundl-Petermeier (Chemical Geology, 2023)

Space-time multi-level modeling for zooplankton abundance employing double data fusion and calibration - Jorge Castillo-Mateo; Alan E. Gelfand; Christine A. Hudak; Charles A. Mayo; Robert S. Schick (Environmental and Ecological Statistics, 2023)
An important objective for marine biologists is to forecast the distribution and abundance of planktivorous marine predators. To do so, it is critically important to understand the spatiotemporal dynamics of their prey. Here, the prey we study are zooplankton and we build a novel space-time hierarchical fusion model to describe the distribution and abundance of zooplankton species in Cape Cod Bay (CCB), MA, USA. The data were collected irregularly in space and time at sites within the first half of the year over a 17 year period, using two different sampling methods. We focus on sea surface zooplankton abundance and incorporate sea surface temperature as a primary driver, also collected with two different sampling methods. So, with two sources for each, we observe true abundance or true sea surface temperature with measurement error. To account for such error, we apply calibrations to align the data sources and use the fusion model to develop a prediction of daily spatial zooplankton abundance surfaces throughout CCB. To infer average abundance on a given day within a given year in CCB, we present a marginalization of the zooplankton abundance surface. We extend the inference to consider abundance averaged to a bi-weekly or annual scale as well as to make an annual comparison of abundance.

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Overview of the tectonic and seismicity in Continental Borderland (offshore) Baja California, México - Mario González Escobar; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román; Carlos S. Reyes-Martínez; Young Ho Aladro-Chio (Journal of South American Earth Sciences, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Salinity effects on the microbiome of a Neotropical water strider - Anakena M. Castillo; Karina A. Chavarria; Kristin Saltonstall; Carlos F. Arias; Luis C. Mejía; Luis F. De León (Hydrobiologia, 2023)

Paleoenvironmental evolution of a Carboniferous marine succession during active volcanism in southern Mexico and its implications in the western Pangea margin configuration - Sandra Guerrero-Moreno; Luigi A. Solari; Juan Carlos Castillo-Reynoso; Miguel A. Torres-Martínez (Journal of South American Earth Sciences, 2023)

A critical review of textile industry wastewater: green technologies for the removal of indigo dyes - L. A. Castillo-Suárez; A. G. Sierra-Sánchez; I. Linares-Hernández; V. Martínez-Miranda; E. A. Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Binary fluoride and As(V) adsorption in water using pleco fish bone chars - Sergio A. Cruz-Briano; Nahum A. Medellin-Castillo; Pablo Delgado-Sanchez; Guillermo J. Castro-Larragoitia; Roberto Leyva-Ramos; Miguel A. Cortina-Rangel; Gladis J. Labrada-Delgado; Diana E. Villela-Martinez; Alfredo I. Flores-Rojas; Lázaro A. Gonzalez-Fernandez; Hilda G. Cisneros-Ontiveros (Environmental Science and Pollution Research, 2023)

An integrated analysis of the Mexican electrical system’s metabolic pattern and industry sector in the energy transition - Miguel A. Morales Mora; Andrea Marín Rovira; Vicente A. Soriano Ramirez; Patricia López Rivera; Omar Guillen Solis; Vincent Pozos Castillo; Gonzalo AngelesOrdoñez; Alejandro Castillo Antonio; Francisco J. Sánchez Ruíz (Environment, Development and Sustainability, 2023)

Bacterial communities shift and influence in an acid mine drainage treatment using barium carbonate disperse alkaline substrate system - J. Castillo; J. Alom; A. Gomez-Arias; S. Cebekhulu; A. Matu; E. Cason; A. Valverde (Science of The Total Environment, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Adaptation measures for asphalt pavements to climate change in China - Tiancheng Liu; Shu Yang; Xia Jiang; Bo Liao; Elvis A. Castillo-Camarena (Journal of Cleaner Production, 2023)

Treatment processes and analysis of rainwater quality for human use and consumption regulations, treatment systems and quality of rainwater - C Morales-Figueroa; L A Castillo-Suárez; I Linares-Hernández; V Martínez-Miranda; E A Teutli-Sequeira (International Journal of Environmental Science and Technology, 2023)

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

Rhizobacterial Isolates from Prosopis limensis Promote the Growth of Raphanus sativus L. Under Salt Stress - Rene Flores Clavo; Esteban Valladolid-Suyón; Karin Reinoza-Farroñan; Cristian Asmat Ortega; Pedro Henrique Riboldi Monteiro; Gladys A. Apaza-Castillo; Gabriel Zuñiga-Valdera; Fabiana Fantinatti Garboggini; Sebastian Iglesias-Osores; Carmen Rosa Carreño-Farfán (Current Microbiology, 2023)
Microbial biotechnology employes techniques that rely based on the natural interactions that occur in ecosystems. Bacteria, including rhizobacteria, play an important role in plant growth, providing agricultural crops with an alternative that can mitigate the negative effects of abiotic stress, such as those caused by saline environments. In this study, bacterial isolates were obtained from soil and roots of Prosopis limensis Bentham from the department of Lambayeque, Peru. This region has high salinity levels, therefore, the collected samples were used to isolate plant growth-promoting rhizobacteria (PGPR), which were identified through morphological, and physical-biochemical characteristics. These salt tolerant bacteria were screened phosphate solubilization, indole acetic acid, deaminase activity and molecular characterization by 16S rDNA sequencing. Eighteen samples from saline soils of the Prosopis limensis plants in the northern coastal desert of San Jose district, Lambayeque, Peru. The bacterial isolates were screened for salt tolerance ranging from 2 to 10%, a total of 78 isolates were found. Isolates 03, 13 and 31 showed maximum salt tolerance at 10%, in vitro ACC production, phosphate solubilization and IAA production. The three isolates were identified by sequencing the amplified 16S rRNA gene and were found to be Pseudomonas sp. 03 (MW604823), Pseudomonas sp. 13 (MW604824) and Bordetella sp. 31 (MW604826). These microorganisms promoted the germination of radish plants and increased the germination rates for treatments T2, T3 and T4 by 129, 124 and 118% respectively. The beneficial effects of salt tolerant PGPR isolates isolated from saline environments can be new species, used to overcome the detrimental effects of salt stress on plants. The biochemical response and inoculation of the three isolates prove the potential of using these strains as a source of products that can be employed for the development of new compounds proving their potential as biofertilizers for saline environments.

Differential activation of neuropeptide FF receptors by gonadotropin-inhibitory hormone peptides in the European sea bass - Bin Wang; José A. Paullada-Salmerón; Alba Vergès-Castillo; José A. Muñoz-Cueto (Frontiers in Marine Science, 2023)
Neuropeptide FF (NPFF) and gonadotropin-inhibitory hormone (GnIH) are thought to be paralogous, and a recent study has revealed that both NPFF and GnIH peptides can activate the GnIH receptor (GnIHR, also called NPFFR1) in the European sea bass ( Dicentrarchus labrax ). However, whether GnIH can bind to the NPFF receptor (NPFFR2) is still yet unknown in this species. Accordingly, we further investigated the potential interactions between GnIH and NPFFR2 (two NPFFR2 forms present in sea bass, namely NPFFR2-1 and NPFFR2-2) on the intracellular signaling pathways. Neither GnIH1 nor GnIH2 had any effect on basal CRE-luc activity, while forskolin-stimulated CRE-luc activity was significantly reduced when COS-7 cells expressing sea bass NPFFR2-1 and NPFFR2-2 were challenged with these two GnIH peptides. NPFF and NPAF also inhibited forskolin-induced CRE-luc activity via their cognate receptors. An evident stimulation of SRE-luc activity was observed when COS-7 cells transfected with NPFFR2-1 and NPFFR2-2 were treated with NPFF and NPAF, whereas GnIH peptides had no effect, except a slight but significant increase elicited by 1000 nM of GnIH1 in COS-7 cells expressing NPFFR2-2. Moreover, only GnIH2 exerted an inhibitory action on NFAT-RE-luc activity in COS-7 cells expressing NPFFR2-1. None of GnIH or NPFF peptides altered ERK phosphorylation levels via NPFFR2 receptors. Our results provide new evidence that sea bass GnIH peptides may exert their functions partially via NPFFR2, and PKA, PKC and Ca 2+ routes are potential mediators.

Molecularly imprinted polymers (MIPs) as efficient catalytic tools for the oxidative degradation of 4-nonylphenol and its by-products - Karla Vargas-Berrones; Raul Ocampo-Perez; Israel Rodríguez-Torres; Nahúm A. Medellín-Castillo; Rogelio Flores-Ramírez (Environmental Science and Pollution Research, 2023)

Morphology of buried volcanic bodies in a sedimentary basin of the Pacific Continental Shelf (Gulf of California, Mexico) - Mario González-Escobar; Abril C. Sánchez-Barra; Cristian A. Gallegos-Castillo; Sergio M. Arregui Ojeda; Edgar A. Mastache-Román (Journal of Volcanology and Geothermal Research, 2023)

Understanding the landscape evolution of El Mogote barrier spit, Baja California Sur, Mexico, using OSL dating, satellite images and a multivariate analysis - A. Valoix; E. Muñoz-Salinas; M. Castillo; D. Sanderson; A. Cresswell (Journal of South American Earth Sciences, 2023)

Phenotypic variation in leaf photosynthetic traits, leaf area index, and carbon discrimination of field-grown wheat genotypes and their relationship with yield performance in Mediterranean environments - Alejandro del Pozo; Ana María Méndez-Espinoza; Miguel Garriga; Félix Estrada; Dalma Castillo; Iván Matus; Gustavo A. Lobos (Planta, 2023)

Alley cropping agroforestry systems change weed community composition and reduce dominant weed species associated with corn in southern Mexico - Fernando Casanova-Lugo; Luis A. Lara-Pérez; Benito Dzib-Castillo; Jesús A. Caamal-Maldonado; Pablo J. Ramírez-Barajas; William R. Cetzal-Ix; Héctor Estrada-Medina (Agriculture, Ecosystems & Environment, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The dynamics of arsenic and copper in solid and aqueous phases in reactive confluences receiving acid drainage: The role of turbidity and particle size - J.A. Díaz; D. Castillo; R. Oyarzún; A. Briso; M. Montecinos; P. Pastén (Environmental Pollution, 2023)

Viability of erythrocytes in canine packed red blood cells stored in CPDA-1 is related to the presence of Mycoplasma haemocanis - Monica A. Camargo Castillo; Bruno Albuquerque de Almeida; Daiani Wissmann; Renata Fagundes Moreira; Felipe Yuki Okano; Felix H.D. Gonzalez; João Fábio Soares; Stella de Faria Valle (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Prioritization of areas for groundwater monitoring using analytic hierarchy process method in Geographic Information Systems: a case of Mexico - J. M. Esquivel-Martínez; J. L. Expósito-Castillo; M. V. Esteller-Alberich; M. A. Gómez-Albores; C. M. Medina-Rivas; C. R. Fonseca-Ortiz (International Journal of Environmental Science and Technology, 2023)

Analysis of the speciation process suggests a dual lifestyle in the plant pathogen Ralstonia solanacearum species complex - José A. Castillo (European Journal of Plant Pathology, 2023)

Sitotroga cerealella-resistant mexican maize races (Zea mays L.), new sources of resistance for commercial maize breeding - Paola Macías-Estrada; Francisco Orozco-González; Gloria Castellanos-Pérez; Adán Castillo-Rosales; Adalberto Ortega-Ortega; Rosa A. Malvar; Daniel Padilla-Chacón; José C. Jiménez-Galindo (Cereal Research Communications, 2023)
Sitotroga cerealella (Oliv.) (Lepidoptera: Gelechiidae) is one of the most important post-harvest pests of maize Zea mays L. Some Mexican maize races ( Z. mays ) could be a novel source of resistance against S. cerealella to improve commercial maize varieties, lines and hybrids. We studied the resistance of Mexican maize races, recollected at Chihuahua State to S. cerealella . We focused on antibiosis and tolerance of maize to S. cerealella . Cristalino-079 maize race shows low level of consumption in grams and percentage, increased larvae mortality before to entering the seed. In addition, Cristalino-079 reduced first adult’s generation and show the largest biological cycle. Due to the small number of emerged adults, there was very little grain weight loss in resistant maize race. The compound that causes high mortality of larvae before to entering the grain is in the pericarp of resistant maize races. The compound that causes longest development time is in the endosperm and embryo. Cristalino-079 show the better level of resistance to S. cerealella infestation in almost all traits studied and this can be used as source of resistance for maize breeding.

Bactericidal activity of silver nanoparticles in drug-resistant bacteria - C. Chapa González; L. I. González García; L. G. Burciaga Jurado; A. Carrillo Castillo (Brazilian Journal of Microbiology, 2023)

Human-induced metals accumulation in sediments of an industrialized bay of northern Chile. An enrichment and ecological risk assessment based on preindustrial values - J. Valdés; Luc Ortlieb; A. Sifeddine; A. Castillo (Marine Pollution Bulletin, 2023)

Non-destructive methods to assess pesticide exposure in free-living bats - Natalia Sandoval-Herrera; Jesusa Paz Castillo; Ma. Enrica Angela Ching; L. Gerardo Herrera M.; Paul A. Faure; Kenneth Welch (Science of The Total Environment, 2023)

Cross-sectional associations of persistent organic pollutants measured in adipose tissue and metabolic syndrome in clinically diagnosed middle-aged adults - Iris Reina-Pérez; Francisco Artacho-Cordón; Vicente Mustieles; Daniel Castellano-Castillo; Fernando Cardona; Inmaculada Jiménez-Díaz; Jose A. López-Medina; Juan Alcaide; Luis Ocaña-Wilhelmi; Luz M. Iribarne-Durán; Juan P. Arrebola; Nicolás Olea; et al. (Environmental Research, 2023)

Surface wind strength and sea surface temperature connections along the south peruvian coast during the last 150 years - F. Briceño-Zuluaga; V. Flores-Aqueveque; J. Nogueira; A. Castillo; J. Cardich; J. Rutllant; S. Caquineau; A. Sifeddine; R. Salvatteci; J. Valdes; D. Gutierrez (Aeolian Research, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Molecular markers for thermo-tolerance are associated with reproductive and physiological traits in Pelibuey ewes raised in a semiarid environment - Candelario A. Castillo-Salas; Guillermo Luna-Nevárez; Javier R. Reyna-Granados; Rosa I. Luna-Ramirez; Sean W. Limesand; Pablo Luna-Nevárez (Journal of Thermal Biology, 2023)

Reaction-front and char characterization from a palm kernel shell – Oil sludge mixture under oxygen lean regimes in a fixed-bed gasifier - York Castillo Santiago; Juan F. Pérez; Leandro A. Sphaier (Fuel, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Lactoferrin gene polymorphisms associated with clinical mastitis in Honduran Holstein inheritance cows - M. Moncada-Laínez; P. A. Valladares-Medina; R. Castillo; X. F. De la Rosa-Reyna; A. M. Sifuentes-Rincón; V. R. Moreno-Medina; A. L. Lara-Rivera; G. M. Parra-Bracamonte (Molecular Biology Reports, 2023)

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Bone appétit: DNA metabarcoding as a non-lethal alternative to morphological dietary assessment in Atlantic bonefish (Albula vulpes) - Lewis J. Campbell; Nicholas A. Castillo; Jonathan Shenker; Leah A. Owens; Rolando O. Santos; Aaron J. Adams; Jennifer S. Rehage; Kate E. Denton; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Using recreational tournament records to construct a 53-year time series of the Florida Keys recreational Bonefish fishery - Ross E. Boucek; Jennifer S. Rehage; Nicholas A. Castillo; Elijah Dwoskin; Steven M. Lombardo; Rolando Santos; Carl Navarre; Michael Larkin; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Effect of bovine oocyte vitrification with EGTA and post-warming recovery with resveratrol on meiotic spindle, mitochondrial function, reactive oxygen species, and developmental competence - Emilio Gutierrez-Castillo; Fabian A. Diaz; Sydney A. Talbot; Kenneth R. Bondioli (Theriogenology, 2023)

Slow and steady hurts the crab: Effects of chronic and acute microplastic exposures on a filter feeder crab - Mauricio A. Urbina; Caroline da Silva Montes; Angela Schäfer; Nicole Castillo; Ángel Urzúa; Marcelo E. Lagos (Science of The Total Environment, 2023)

Exposure to secondhand aerosol from electronic cigarettes at homes: A real-life study in four European countries - Beladenta Amalia; Marcela Fu; Olena Tigova; Montse Ballbè; Blanca Paniello-Castillo; Yolanda Castellano; Vergina K. Vyzikidou; Rachel O'Donnell; Ruaraidh Dobson; Alessandra Lugo; Chiara Veronese; Raúl Pérez-Ortuño; et al. (Science of The Total Environment, 2023)

Petrology, metallogeny and U-Pb geochronology of the paleoproterozoic mafic-ultramafic Hamutenha intrusion, Angolan Shield - Marc Campeny; Joaquín A. Proenza; Montgarri Castillo-Oliver; Lisard Torró; Cristina Villanova-de-Benavent; Joan Carles Melgarejo; Antonio O. Gonçalves; Manuel J. Román-Alpiste; Idael F. Blanco-Quintero; Xavier Llovet; Júlia Farré-de-Pablo (Journal of African Earth Sciences, 2023)

Temporal variability of phytoplankton biomass and net community production in a macrotidal temperate estuary - Africa P. Gomez-Castillo; Anouska Panton; Duncan A. Purdie (Estuarine, Coastal and Shelf Science, 2023)

Molecular diagnostics of the Mediterranean olive cyst nematode, Heterodera mediterranea Vovlas, Inserra & Stone, 1981 using conventional and real-time PCR - Sergei A. Subbotin; Julie Burbridge; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2023)

Integrated evidence‐based extent of occurrence for North American bison ( Bison bison ) since 1500 CE and before - Jeff M. Martin; Rachel A. Short; Glenn E. Plumb; Lauren Markewicz; Dirk H. Van Vuren; Bradly Wehus‐Tow; Erik Otárola‐Castillo; Matthew E. Hill (Ecology, 2023)
Following the near extinction of bison ( Bison bison ) from its historic range across North America in the late 19th century, novel bison conservation efforts in the early 20th century catalyzed a popular widespread conservation movement to protect and restore bison among other species and places. Since Allen's initial delineation (1876) of the historic distribution of North American bison, subsequent attempts have been hampered by knowledge gaps about bison distribution and abundance prior to and following colonial arrival and settlement. For the first time, we applied a multidisciplinary approach to assemble a comprehensive, integrated geographic database and meta‐analysis of bison occurrence over the last 200,000 years, with particular emphasis on the 450 years before present. We combined paleontology, archaeology, and historical ecology data for our database, which totaled 6438 observations. We derived the observations from existing online databases, published literature, and first‐hand exploration journal entries. To illustrate the conservative maximum historical extent of occurrence of bison, we created a concave hull using observations occurring over the last 450 years ( n = 3379 observations), which is the broadly accepted historical benchmark at 1500 CE covering 59% of the North American continent. Although this distribution represents a historic extent of occurrence—merely delineating the maximum margins of the near‐continental distribution—it does not replace a density‐based approach reconstructing potential historical range distributions, which identifies core and marginal ranges. However, we envision the observations contained in this database will contribute to further research in the increasingly evidence‐based disciplines of bison ecology, evolution, rewilding, management, and conservation. There are no copyright or proprietary restrictions on these data, and this data paper should be cited when the data are reused.

Disentangling Environmental, Economic, and Technological Factors Driving Scallop (Argopecten purpuratus) Aquaculture in Chile - José Bakit; Gonzalo Álvarez; Patricio A. Díaz; Eduardo Uribe; Rodrigo Sfeir; Sebastian Villasante; Tomas Gabriel Bas; Germán Lira; Hernán Pérez; Andrés Hurtado; Raúl González-Ávalos; Jose Castillo-Venenciano (Fishes, 2022)
The boom-and-bust trajectory of the Argopecten purpuratus industry in Chile shows the progression from resource extraction (fishing) to production (aquaculture). This paper analyses the effects of environmental, economic, and scientific–technological factors. The influence of each factor on scallop production in Chile was reviewed for the period between the 1980s and 2020. The evaluation of the effects allows the visualisation of the industry’s productive evolution and reveals the current challenges. The occurrence of abrupt environmental disturbances, commercialisation under imperfect market configurations, and public and private efforts in scientific and technological advances have acted favourably on scallop production. However, an industry mainly focused on prices and high production volumes did not devote much effort to develop low-cost climate-resilient technologies. Today, economic challenges must be addressed by helping to reduce production costs and add economic value to products and by-products. Our results show that the industry must focus on low-cost technologies, the use of renewable energy, and the circularity of its processes. The environment ensures the capture of natural seeds and their adaptation to climate change. These challenges must not lose sight of the emerging effects of the COVID-19 pandemic.

Assessing Conservation Easement Landowners Adoption of Thinning - Ana Gutierrez-Castillo; Shaun M Tanger; Jerrod Penn; Michael A Blazier (Forest Science, 2022)
The Natural Resources Conservation Service has overseen several conservation easement programs in the Lower Mississippi Alluvial Valley (LMAV), which have the primary objective to protect, restore, and enhance wetlands functions and to protect conservation values, such as wildlife habitat. Promotion of thinning in forests reaching or past canopy closure improves habitat conditions in forests under conservation easement. This study explicitly explores determinants that influence easement landowner voluntary adoption of thinning and characterizes landowners who are unwilling to thin in terms of management concerns, objective interference, and other reasons. The willingness-to-thin models demonstrated that membership in conservation organizations, different income expectations from thinning, and investment objectives positively influence landowners’ willingness to thin, whereas being an original easement grantor decreases the likelihood to thin such that subsequent landowners who will inherit or purchase the easement will be more willing to conduct thinning. Study results also indicated that landowners who had recreation as an ownership objective are less likely to adopt thinning, having important long-term implications for managing the forest in the easements. Findings from this study could be used to improve efforts to design and conduct educational interventions that promote forest health and wildlife habitat needs in the LMAV easements.

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

Structure and activity of microbial communities in response to environmental, operational, and design factors in constructed wetlands - M. Verduzo Garibay; A. Fernández del Castillo; J. de Anda; C. Senés-Guerrero; M. S. Gradilla-Hernández (International Journal of Environmental Science and Technology, 2022)

Molecular insights into the invasion dynamics of Carcinus crabs in South Africa - Clova A. Mabin; Tamara B. Robinson; John R. U. Wilson; Heidi Hirsch; Maria L. Castillo; Michelle Jooste; Johannes J. Le Roux (Biological Invasions, 2022)
Knowledge of the introduction history and spread dynamics of invasive species can provide important insights for management (Ens et al. in Environ Rev (in press), 2022), however such information is often unavailable for accidental introductions. Here we infer how the European shore crab, Carcinus maenas , and its congener, the Mediterranean shore crab, C. aestuarii , were introduced to and spread within South Africa. We do this using nuclear microsatellite data and Bayesian assignment tests and Approximate Bayesian Computation (ABC) modelling that included samples from the native and other invasive ranges of these two species. We also compared the genetic diversity and structure of one of the South African populations during and after intensive management, with that of another, unmanaged, population. South African populations had higher genetic diversity than invasive Carcinus populations from elsewhere in the world. Moreover, the ABC analyses suggest that South African populations originated from an admixture event between individuals of C. maenas from a population in the native range and an invasive population from Canada. We also identified instances of hybridisation between Carcinus maenas and C. aestuarii in South Africa. South African populations showed no genetic structure, suggesting either extensive migration between them or that populations arose from the same initial introduction. Management of Carcinus did not affect genetic diversity or structure, and we suspect that the management duration was insufficient to target a full generation of crabs. Together these results suggest multiple introductions and/or high propagule pressure to South Africa, crab (larval or adult) movement between existing populations, and some hybridisation. For eradication from South Africa to be achieved, management would need to concurrently target all known invasive populations and clearly establish that new introductions could be prevented.

Predicted threats to a native squirrel from two invading species based on citizen science data - Theodore T. Tran; Benjamin E. Carter; Jessica A. Castillo Vardaro (Biological Invasions, 2022)

Title: Present status and management of coastal lagoons in the Sabana–Camagüey Archipelago I: environmental baseline at lagoons of Cayo Sabinal - R. González-De; Zayas; M. Merino-Ibarra; J. A. Lestayo González; F. S Castillo – Sandoval (Thalassas: An International Journal of Marine Sciences, 2022)

A novel series of pyrazole derivatives toward biological applications: experimental and conceptual DFT characterization - Pedro D. Ortiz; Judith Castillo-Rodriguez; Jorge Tapia; Ximena Zarate; Gabriel A. Vallejos; Vanesa Roa; Elies Molins; Carlos Bustos; Eduardo Schott (Molecular Diversity, 2022)

Identification of Microcrustaceans as Potential Bioindicators of Arsenic in Tropical Water Bodies - Yadira J. Mendoza-Chávez; José L. Uc-Castillo; Martha A. Gutiérrez-Aguirre; Adrián Cervantes-Martínez; Nadia Martínez-Villegas (Archives of Environmental Contamination and Toxicology, 2022)

Spatio-temporal analysis of the extent of an extreme heat event - Ana C. Cebrián; Jesús Asín; Alan E. Gelfand; Erin M. Schliep; Jorge Castillo-Mateo; María A. Beamonte; Jesús Abaurrea (Stochastic Environmental Research and Risk Assessment, 2022)
Evidence of global warming induced from the increasing concentration of greenhouse gases in the atmosphere suggests more frequent warm days and heat waves. The concept of an extreme heat event (EHE), defined locally based on exceedance of a suitable local threshold, enables us to capture the notion of a period of persistent extremely high temperatures. Modeling for extreme heat events is customarily implemented using time series of temperatures collected at a set of locations. Since spatial dependence is anticipated in the occurrence of EHE’s, a joint model for the time series, incorporating spatial dependence is needed. Recent work by Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) develops a space-time model based on a point-referenced collection of temperature time series that enables the prediction of both the incidence and characteristics of EHE’s occurring at any location in a study region. The contribution here is to introduce a formal definition of the notion of the spatial extent of an extreme heat event and then to employ output from the Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) modeling work to illustrate the notion. For a specified region and a given day, the definition takes the form of a block average of indicator functions over the region. Our risk assessment examines extents for the Comunidad Autónoma de Aragón in northeastern Spain. We calculate daily, seasonal and decadal averages of the extents for two subregions in this comunidad. We generalize our definition to capture extents of persistence of extreme heat and make comparisons across decades to reveal evidence of increasing extent over time.

Contrasting Effects of Nitrogen and Labile Carbon Addition on N2O Emissions from Andosols in Costa Rica and Chile Under Controlled Conditions - C. Chinchilla-Soto; M. A. Alfaro; F. Bertsch; A. G. Perez-Castillo (Journal of Soil Science and Plant Nutrition, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Physicochemical Control of Caribbean Coral Calcification Linked to Host and Symbiont Responses to Varying pCO2 and Temperature - Robert A. Eagle; Maxence Guillermic; Illian De Corte; Blanca Alvarez Caraveo; Colleen B. Bove; Sambuddha Misra; Louise P. Cameron; Karl D. Castillo; Justin B. Ries (Journal of Marine Science and Engineering, 2022)
It is thought that the active physiological regulation of the chemistry of a parent fluid is an important process in the biomineralization of scleractinian corals. Biological regulation of calcification fluid pH (pHCF) and other carbonate chemistry parameters ([CO32−]CF, DICCF, and ΩCF) may be challenged by CO2 driven acidification and temperature. Here, we examine the combined influence of changing temperature and CO2 on calcifying fluid regulation in four common Caribbean coral species—Porites astreoides, Pseudodiploria strigosa, Undaria tenuifolia, and Siderastrea siderea. We utilize skeletal boron geochemistry (B/Ca and δ11B) to probe the pHCF, [CO32−]CF, and DICCF regulation in these corals, and δ13C to track changes in the sources of carbon for calcification. Temperature was found to not influence pHCF regulation across all pCO2 treatments in these corals, in contrast to recent studies on Indo-Pacific pocilloporid corals. We find that [DIC]CF is significantly lower at higher temperatures in all the corals, and that the higher temperature was associated with depletion of host energy reserves, suggesting [DIC]CF reductions may result from reduced input of respired CO2 to the DIC pool for calcification. In addition, δ13C data suggest that under high temperature and CO2 conditions, algal symbiont photosynthesis continues to influence the calcification pool and is associated with low [DIC]CF in P. strigosa and P. astreoides. In P. astreoides this effect is also associated with an increase in chlorophyll a concentration in coral tissues at higher temperatures. These observations collectively support the assertion that physicochemical control over coral calcifying fluid chemistry is coupled to host and symbiont physiological responses to environmental change, and reveals interspecific differences in the extent and nature of this coupling.

Different exercise training modalities similarly improve heart rate variability in sedentary middle-aged adults: the FIT-AGEING randomized controlled trial - Ginés Navarro-Lomas; Manuel Dote-Montero; Juan M. A. Alcantara; Abel Plaza-Florido; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2022)
Purpose This study aimed to investigate the influence of different exercise training modalities on heart rate variability (HRV) in sedentary middle-aged adults; and to study whether changes in health-related outcomes (i.e., body composition and cardiometabolic risk) are associated with those hypothetical HRV changes in sedentary middle-aged adults. Methods A total of 66 middle-aged adults (53.6 ± 4.4 years old; 50% women) were enrolled in the FIT-AGEING study. We conducted a 12-week randomized controlled trial. The participants were randomly assigned to 4 groups: (a) a control group (no exercise); (b) a physical activity recommendation from the World Health Organization group (PAR); (c) a high-intensity interval training group (HIIT); and (d) a high-intensity interval training group adding whole-body electromyostimulation (HIIT + EMS). Results All exercise training modalities induced changes in HRV parameters (all P ≤ 0.001) without statistical differences between them (all P > 0.05). We found associations between changes in body composition and cardiometabolic risk and exercise-related changes in HRV. Conclusion Our results suggest that different exercise interventions (i.e., PAR, HIIT and HIIT + EMS) induced an enhancement of HRV in sedentary middle-aged adults. Our findings support the notion that exercise-related changes in HRV are associated with changes in body composition and cardiometabolic risk after the intervention program Clinical trial registry NCT03334357 (ClinicalTrials.gov). November 7, 2017 retrospectively registered.

Vaginal Microbiota Is Stable and Mainly Dominated by Lactobacillus at Third Trimester of Pregnancy and Active Childbirth: A Longitudinal Study of Ten Mexican Women - Antonio González-Sánchez; José J. Reyes-Lagos; Miguel A. Peña-Castillo; Khemlal Nirmalkar; Jaime García-Mena; Gustavo Pacheco-López (Current Microbiology, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Machine learning approach to discovery of small molecules with potential inhibitory action against vasoactive metalloproteases - Yudith Cañizares-Carmenate; Karel Mena-Ulecia; Desmond MacLeod Carey; Yunier Perera-Sardiña; Erix W. Hernández-Rodríguez; Yovani Marrero-Ponce; Francisco Torrens; Juan A. Castillo-Garit (Molecular Diversity, 2022)

Biology of Acerophagus texanus (Howard, 1898) (Hymenoptera: Encyrtidae), a parasitoid of Ferrisia virgata Cockerell (Hemiptera: Pseudococcidae) - Sergio A. Mejía-Ortíz; John S. Noyes; Francisco Infante; Juan Cisneros-Hernández; Alfredo Castillo-Vera (International Journal of Tropical Insect Science, 2022)

Design and application of molecularly imprinted polymers for adsorption and environmental assessment of anti-inflammatory drugs in wastewater samples - Jessica Meléndez-Marmolejo; Lorena Díaz de León-Martínez; Vanessa Galván-Romero; Samantha Villarreal-Lucio; Raúl Ocampo-Pérez; Nahum A. Medellín-Castillo; Erika Padilla-Ortega; Israel Rodríguez-Torres; Rogelio Flores-Ramírez (Environmental Science and Pollution Research, 2022)

Genetic etiology of non-syndromic hearing loss in Europe - Ignacio del Castillo; Matías Morín; María Domínguez-Ruiz; Miguel A. Moreno-Pelayo (Human Genetics, 2022)

Genome-scale Solanum spp.-Ralstonia solanacearum interactome reveals candidate determinants for host specificity and environmental adaptation - Katlheen N. Sarmiento; José A. Castillo (European Journal of Plant Pathology, 2022)

Seascape genomics of coastal bottlenose dolphins along strong gradients of temperature and salinity - Eleanor A. L. Pratt; Luciano B. Beheregaray; Kerstin Bilgmann; Nikki Zanardo; Fernando Diaz‐Aguirre; Chris Brauer; Jonathan Sandoval‐Castillo; Luciana M. Möller (Molecular Ecology, 2022)
Heterogeneous seascapes and strong environmental gradients in coastal waters are expected to influence adaptive divergence, particularly in species with large population sizes where selection is expected to be highly efficient. However, these influences might also extend to species characterized by strong social structure, natal philopatry and small home ranges. We implemented a seascape genomic study to test this hypothesis in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) distributed along the environmentally heterogeneous coast of southern Australia. The data sets included oceanographic and environmental variables thought to be good predictors of local adaptation in dolphins and 8081 filtered single nucleotide polymorphisms (SNPs) genotyped for individuals sampled from seven different bioregions. From a neutral perspective, population structure and connectivity of the dolphins were generally influenced by habitat type and social structuring. Genotype‐environment association analysis identified 241 candidate adaptive loci and revealed that sea surface temperature and salinity gradients influenced adaptive divergence in these animals at both large‐ (1000 km) and fine‐scales (

Stable inversion clines in a grasshopper species group despite complex geographical history - Noelia V. Guzmán; Petri Kemppainen; Daniela Monti; Elio R. D. Castillo; Marcela S. Rodriguero; Andrés F. Sánchez‐Restrepo; Maria Marta Cigliano; Viviana A. Confalonieri (Molecular Ecology, 2022)
Chromosomal inversions are known to play roles in adaptation and differentiation in many species. They involve clusters of correlated genes (i.e., loci in linkage disequilibrium, LD) possibly associated with environmental variables. The grasshopper “species complex” Trimerotropis pallidipennis comprises several genetic lineages distributed from North to South America in arid and semi‐arid high‐altitude environments. The southernmost lineage, Trimerotropis sp., segregates for four to seven putative inversions that display clinal variation, possibly through adaptation to temperate environments. We analysed chromosomal, mitochondrial and genome‐wide single nucleotide polymorphism data in 19 Trimerotropis sp. populations mainly distributed along two altitudinal gradients (MS and Ju). Populations across Argentina comprise two main chromosomally and genetically differentiated lineages: one distributed across the southernmost border of the “Andes Centrales,” adding evidence for a differentiation hotspot in this area; and the other widely distributed in Argentina. Within the latter, network analytical approaches to LD found three clusters of correlated loci (LD‐clusters), with inversion karyotypes explaining >79% of the genetic variation. Outlier loci associated with environmental variables mapped to two of these LD‐clusters. Furthermore, despite the complex geographical history indicated by population genetic analyses, the clines in inversion karyotypes have remained stable for more than 20 generations, implicating their role in adaptation and differentiation within this lineage. We hypothesize that these clines could be the consequence of a coupling between extrinsic postzygotic barriers and spatially varying selection along environmental gradients resulting in a hybrid zone. These results provide a framework for future investigations about candidate genes implicated in rapid adaptation to new environments.

Giant Toads (Rhinella marina) From the Industrial Zones of Low Basin of the Coatzacoalcos River (Veracruz, MX) Presents Genotoxicity in Erythrocytes - Omar Cruz-Santiago; Claudia G. Castillo; Guillermo Espinosa-Reyes; Iván N. Pérez-Maldonado; Donaji J. González-Mille; María del Carmen Cuevas-Díaz; César A. Ilizaliturri-Hernández (Bulletin of Environmental Contamination and Toxicology, 2022)

Population genomic structure of killer whales ( Orcinus orca ) in Australian and New Zealand waters - Isabella M. Reeves; John A. Totterdell; Andrea Barceló; Jonathan Sandoval‐Castillo; Kimberley C. Batley; Karen A. Stockin; Emma L. Betty; David M. Donnelly; Rebecca Wellard; Luciano B. Beheregaray; Luciana M. Möller (Marine Mammal Science, 2022)
Population genomic data sets have enhanced power to detect cryptic and complex population structure and generate valuable information for the conservation and management of wildlife species. Globally, killer whales ( Orcinus orca ) are considered to have a complex population structure due to their ability to specialize in a variety of ecological niches. In the Australasian region, they are found year round in New Zealand waters and are sighted in all Australian waters, with seasonal aggregations in the northwest (NWA) and southwest (SWA). Regionally, there is some knowledge regarding killer whale abundance, diet, acoustics, and social structure, but limited information about their population structure. Here, we present a population structure assessment of Australasian killer whales using 17,491 high quality genome‐wide single nucleotide polymorphisms (SNPs), combined with sequences of the mitochondrial DNA control region. The results indicate a minimum of three populations: New Zealand, NWA, and SWA. These populations present moderate levels of genomic diversity, negligible levels of inbreeding, small effective population sizes, and low contemporary migration rates among them. Mitochondrial DNA analysis elucidated five closely related haplotypes, suggestive of matrilineal societies, consistent with killer whales elsewhere. This information will assist conservation management of killer whales in the Australasian region.

Genetic variation of Batrachochytrium dendrobatidis is linked to skin bacterial diversity in the Pacific treefrog Hyliola regilla ( hypochondriaca ) - María Delia Basanta; Eria A. Rebollar; Mirna G. García‐Castillo; Erica Bree Rosenblum; Allison Q. Byrne; Jonah Piovia‐Scott; Gabriela Parra‐Olea (Environmental Microbiology, 2022)
Summary Symbiotic bacterial communities are crucial to combating infections and contribute to host health. The amphibian skin microbiome plays an important role in protecting their hosts against pathogens such as Batrachochytrium dendrobatidis ( Bd ), one of the causative agents of chytridiomycosis, which is responsible for dramatic amphibian population declines worldwide. Although symbiotic skin bacteria are known to inhibit Bd growth, an understanding of the relationship between Bd genetic variability, environmental conditions, and skin bacterial communities is limited. Therefore, we examined the associations between Bd infection load, Bd genetic diversity and skin bacterial communities in five populations of Hyliola regilla ( hypochondriaca ) from environmentally contrasting sites in Baja California, Mexico. We observed differences in Bd genetics and infection load among sites and environments. Genetic analysis of Bd isolates revealed patterns of spatial structure corresponding to the five sites sampled. Amphibian skin bacterial diversity and community structure differed among environments and sites. Bacterial community composition was correlated with Bd genetic differences and infection load, with specific bacterial taxa enriched on infected and un‐infected frogs. Our results indicate that skin‐associated bacteria and Bd strains likely interact on the host skin, with consequences for microbial community structure and Bd infection intensity.

Autosomal Recessive Cerebellar Ataxia 1: First Case Report Depicting a Variant in SYNE1 Gene in a Chilean Patient - J Valentina Castillo; S Catherine Díaz; María Leonor Bustamante; Matheus Gomes Ferreira; Hélio A. G. Teive; Marcelo Miranda (The Cerebellum, 2021)

NFĸB Targeting in Bone Marrow Mesenchymal Stem Cell-Mediated Support of Age-Linked Hematological Malignancies - Lauren S. Sherman; Shyam A. Patel; Marianne D. Castillo; Rachel Unkovic; Marcelo Taborga; Marina Gergues; Shaun Patterson; Jean-Pierre Etchegaray; Mohammed Jaloudi; Anupama Hooda-Nehra; Joshua Kra; Darling P. Rojas; et al. (Stem Cell Reviews and Reports, 2021)

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Expanding the chemical space of aryloxy-naphthoquinones as potential anti-Chagasic agents: synthesis and trypanosomicidal activity - Nohemí A. Becerra; Christian Espinosa-Bustos; Karina Vázquez; Gildardo Rivera; Margot Paulino; Jorge Cantero; Benjamín Nogueda; Fabiola Chacón-Vargas; Uziel Castillo-Velazquez; Ana F. Elizondo Rodríguez; Sofía Toledo; Adriana Moreno-Rodríguez; et al. (Medicinal Chemistry Research, 2021)

Ecological Drawbacks of Nanomaterials Produced on an Industrial Scale: Collateral Effect on Human and Environmental Health - H. Pérez-Hernández; A. Pérez-Moreno; C. R. Sarabia-Castillo; S. García-Mayagoitia; G. Medina-Pérez; F. López-Valdez; R. G. Campos-Montiel; P. Jayanta-Kumar; F. Fernández-Luqueño (Water, Air, & Soil Pollution, 2021)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

The virus–host interface: Molecular interactions of Alphacoronavirus‐1 variants from wild and domestic hosts with mammalian aminopeptidase N - Ximena A. Olarte‐Castillo; Joana F. dos Remédios; Felix Heeger; Heribert Hofer; Stephan Karl; Alex D. Greenwood; Marion L. East (Molecular Ecology, 2021)
The Alphacoronavirus ‐ 1 species include viruses that infect numerous mammalian species. To better understand the wide host range of these viruses, better knowledge on the molecular determinants of virus–host cell entry mechanisms in wildlife hosts is essential. We investigated Alphacoronavirus ‐ 1 infection in carnivores using long‐term data on Serengeti spotted hyenas ( Crocuta crocuta ) and molecular analyses guided by the tertiary structure of the viral spike (S) attachment protein's interface with the host receptor aminopeptidase N (APN). We sequenced the complete 3′‐end region of the genome of nine variants from wild African carnivores, plus the APN gene of 15 wild carnivore species. Our results revealed two outbreaks of Alphacoronavirus ‐ 1 infection in spotted hyenas associated with genetically distinct canine coronavirus type II (CCoVII) variants. Within the receptor binding domain (RBD) of the S gene the residues that directly bind to the APN receptor were conserved in all variants studied, even those infecting phylogenetically diverse host taxa. We identified a variable region within RBD located next to a region that directly interacts with the APN receptor. Two residues within this variable region were under positive selection in hyena variants, indicating that both sites were associated with adaptation of CCoVII to spotted hyena APN. Analysis of APN sequences revealed that most residues that interact with the S protein are conserved in wild carnivores, whereas some adjacent residues are highly variable. Of the variable residues, four that are critical for virus–host binding were under positive selection and may modulate the efficiency of virus attachment to carnivore APN.

Study of a coupled adsorption/electro-oxidation process as a tertiary treatment for tequila industry wastewater - Jesús Castillo-Monroy; Luis A. Godínez; Irma Robles; Arturo Estrada-Vargas (Environmental Science and Pollution Research, 2021)

A novel vieuvirus from multidrug-resistant Acinetobacter baumannii - Gamaliel López-Leal; Alejandro Reyes-Muñoz; Rosa Isela Santamaria; Miguel A. Cevallos; Carlos Pérez-Monter; Santiago Castillo-Ramírez (Archives of Virology, 2021)

Estimating carbon isotope discrimination and grain yield of bread wheat grown under water-limited and full irrigation conditions by hyperspectral canopy reflectance and multilinear regression analysis - Miguel Garriga; Sebastián Romero-Bravo; Félix Estrada; Ana M. Méndez-Espinoza; Luis González-Martínez; Iván A. Matus; Dalma Castillo; Gustavo A. Lobos; Alejandro Del Pozo (International Journal of Remote Sensing, 2021)

Streptomyces sp. M54: an actinobacteria associated with a neotropical social wasp with high potential for antibiotic production - Bernal Matarrita-Carranza; Catalina Murillo-Cruz; Roberto Avendaño; María Isabel Ríos; Max Chavarría; María Luisa Gómez-Calvo; Giselle Tamayo-Castillo; Juan J. Araya; Adrián A. Pinto-Tomás (Antonie van Leeuwenhoek, 2021)

Potential distribution of the dinoflagellate Peridinium quadridentatum and its blooms in continental shelves globally: an environmental and geographic approach - Carlos F. Rodríguez-Gómez; Gabriela Vázquez; Carlos A. Maya-Lastra; José A. Aké-Castillo; Christine J. Band-Schmidt; Patricia Moreno-Casasola; Octavio Rojas-Soto (Marine Biology, 2021)

A Matter of Scale: Population Genomic Structure and Connectivity of Fisheries At-Risk Common Dolphins (Delphinus delphis) From Australasia - Andrea Barceló; Jonathan Sandoval-Castillo; Karen A. Stockin; Kerstin Bilgmann; Catherine R. M. Attard; Nikki Zanardo; Guido J. Parra; Krista Hupman; Isabella M. Reeves; Emma L. Betty; Gabriela Tezanos-Pinto; Luciano B. Beheregaray; et al. (Frontiers in Marine Science, 2021)
An understanding of population structure and connectivity at multiple spatial scales is required to assist wildlife conservation and management. This is particularly critical for widely distributed and highly mobile marine mammals subject to fisheries by-catch. Here, we present a population genomic assessment of a near-top predator, the common dolphin ( Delphinus delphis ), which is incidentally caught in multiple fisheries across the Australasian region. The study was carried out using 14,799 ddRAD sequenced genome-wide markers genotyped for 478 individuals sampled at multiple spatial scales across Australasia. A complex hierarchical metapopulation structure was identified, with three highly distinct and genetically diverse regional populations at large spatial scales (>1,500 km). The populations inhabit the southern coast of Australia, the eastern coast of Australia, New Zealand, and Tasmania, with the latter also showing a considerable level of admixture to Australia's east coast. Each of these regional populations contained two to four nested local populations (i.e., subpopulations) at finer spatial scales, with most of the gene flow occurring within distances of 50 to 400 km. Estimates of contemporary migration rates between adjacent subpopulations ranged from 6 to 25%. Overall, our findings identified complex common dolphin population structure and connectivity across state and international jurisdictions, including migration and gene flow across the Tasman Sea. The results indicate that inter-jurisdictional collaboration is required to implement conservation management strategies and mitigate fisheries interactions of common dolphins across multiple spatial scales in the Australasian region.

The macroecology of fish migration - Dominique Alò; Shaw Nozaki Lacy; Andrea Castillo; Horacio A. Samaniego; Pablo A. Marquet (Global Ecology and Biogeography, 2021)
Aim We still lack a consensus on the main variables driving changes in migratory strategies. Different hypotheses have been proposed: productivity, energy, environmental heterogeneity, and genetic predisposition. This work takes an integrative view and analyses migrations from a macroecological perspective estimating the extent to which different environmental variables and historic factors influence migratory life histories. Location Global. Time period Current. Major taxa studied Actinopterygian fishes. Methods Using public domain museum records, global repositories, and global measures of temperature, productivity, precipitation and heterogeneity, we spatially analysed the distribution of anadromous, catadromous, amphidromous, potamodromous and oceanodromous migratory fish using 1,676 species and compared it to 1,616 non‐migratory fishes. After analysing the individual roles of productivity and temperature in shaping biodiversity, we conducted path analyses including several environmental variables and principal coordinates of phylogenetic structure (PCPS). Results The different migratory strategies are not evenly distributed around the globe and phylogeny is a relevant variable in shaping current patterns. Productivity is positively related to species richness, except for anadromy and potamodromy, for which we observed a unimodal curve. Temperature significantly drives migratory species richness (except for anadromy). The role of environmental heterogeneity, measured as temperature seasonality and annual range, is strongest for anadromous species, which helps explain their skewed distribution towards higher latitudes and why the kinetic energy hypothesis fails in explaining their richness patterns. Main conclusions Overall, migratory fish richness can be explained by the interaction of multiple variables, such as productivity, temperature, environmental heterogeneity, and the role of phylogeny, but these variables interact differentially in each strategy, diverging most for the anomalous anadromous fishes. Integrating these results into a global framework to better understand the evolutionary and ecological dynamics of migration will help with predicting responses to anthropogenic climate change.

Machine Learning Based Predictions of Dissolved Oxygen in a Small Coastal Embayment - Manuel Valera; Ryan K. Walter; Barbara A. Bailey; Jose E. Castillo (Journal of Marine Science and Engineering, 2020)
Coastal dissolved oxygen (DO) concentrations have a profound impact on nearshore ecosystems and, in recent years, there has been an increased prevalance of low DO hypoxic events that negatively impact nearshore organisms. Even with advanced numerical models, accurate prediction of coastal DO variability is challenging and computationally expensive. Here, we apply machine learning techniques in order to reconstruct and predict nearshore DO concentrations in a small coastal embayment while using a comprehensive set of nearshore and offshore measurements and easily measured input (training) parameters. We show that both random forest regression (RFR) and support vector regression (SVR) models accurately reproduce both the offshore DO and nearshore DO with extremely high accuracy. In general, RFR consistently peformed slightly better than SVR, the latter of which was more difficult to tune and took longer to train. Although each of the nearshore datasets were able to accurately predict DO values using training data from the same site, the model only had moderate success when using training data from one site to predict DO at another site, which was likely due to the the complexities in the underlying dynamics across the sites. We also show that high accuracy can be achieved with relatively little training data, highlighting a potential application for correcting time series with missing DO data due to quality control or sensor issues. This work establishes the ability of machine learning models to accurately reproduce DO concentrations in both offshore and nearshore coastal waters, with important implications for the ability to detect and indirectly measure coastal hypoxic events in near real-time. Future work should explore the ability of machine learning models in order to accurately forecast hypoxic events.

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of standardized heavy rainfall profiles for Barcelona city: clustering, rain amounts and intensity peaks - X. Lana; R. Rodríguez-Solà; M. D. Martínez; M. C. Casas-Castillo; C. Serra; A. Burgueño (Theoretical and Applied Climatology, 2020)

Development of nuclear microsatellite markers to facilitate germplasm conservation and population genetics studies of five groups of tropical perennial plants with edible fruits and shoots: rambutan (Nephelium lappaceum L.), sapodilla (Manilkara zapota (L.) P. Royen), lychee (Litchi chinensis Sonn.), mangosteen (Garcinia mangostana Linn. and Garcinia cochinchinensis (Lour.) Choisy) and bamboo (Bambusa vulgaris Schrad. ex J.C. Wendl and Guadua angustifolia Kunth) - Renée S. Arias; Linda L. Ballard; Mary V. Duke; Sheron A. Simpson; Xiaofen F. Liu; Valerie A. Orner; Victor S. Sobolev; Brian E. Scheffler; Jaime Martinez-Castillo (Genetic Resources and Crop Evolution, 2020)

Size-Fractionated Contribution of Microbial Biomass to Suspended Organic Matter in the Eastern Tropical South Pacific Oxygen Minimum Zone - Sebastian I. Cantarero; Carlos Henríquez-Castillo; Nadia Dildar; Cristian A. Vargas; Peter von Dassow; Marcela Cornejo-D’Ottone; Julio Sepúlveda (Frontiers in Marine Science, 2020)

Diffusible and volatile organic compounds produced by avocado rhizobacteria exhibit antifungal effects against Fusarium kuroshium - Edgar Guevara-Avendaño; Karla R. Bravo-Castillo; Juan L. Monribot-Villanueva; Ana L. Kiel-Martínez; Mónica Ramírez-Vázquez; José A. Guerrero-Analco; Frédérique Reverchon (Brazilian Journal of Microbiology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

A New Species of Moth Lacewing from the Mesoamerican Genus Adamsiana Penny 1996 (Neuroptera: Ithonidae) - A. Ardila-Camacho; R. Castillo-Argaez; J. I. Martínez (Neotropical Entomology, 2020)

Effectiveness of the Sex Pheromone for Monitoring Stenoma catenifer (Lepidoptera: Elachistidae) in Avocado Orchards - L. Cruz-López; M. A. Vázquez; A. Castillo (Neotropical Entomology, 2020)

Heavy metals (lead, cadmium and zinc) from street dust in Monterrey, Mexico: ecological risk index - D. Castillo-Nava; M. Elias-Santos; U. J. López-Chuken; A. Valdés-González; L. G. de la Riva-Solís; M. P. Vargas-Pérez; L. J. Galán-Wong; H. A. Luna-Olvera (International Journal of Environmental Science and Technology, 2020)

White-Faced Capuchin, Cebus capucinus imitator, Hammerstone and Anvil Tool Use in Riparian Habitats on Coiba Island, Panama - Claudio M. Monteza-Moreno; Tamara Dogandžić; Kevin A. McLean; Pedro L. Castillo-Caballero; Zarluis Mijango-Ramos; Evelyn Del Rosario-Vargas; Margaret C. Crofoot; Brendan J. Barrett (International Journal of Primatology, 2020)

Could Alternaria solani IA300 be a plant growth-promoting fungus? - Jorge A. Mauricio-Castillo; Silvia Salas-Muñoz; Luis R. Reveles-Torres; Miguel A. Salas-Luevano; Fatima B. Salazar-Badillo (European Journal of Plant Pathology, 2020)

Photobacterium lucens sp. nov., Isolated from a Cultured Shrimp Penaeus vannamei. - Julissa Enciso-Ibarra; Adrián González-Castillo; Sonia A. Soto-Rodriguez; Karen Enciso-Ibarra; Carmen Bolán-Mejia; Bruno Gomez-Gil (Current Microbiology, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Computational approach to the discovery of potential neprilysin inhibitors compounds for cardiovascular diseases treatment - Yudith Cañizares-Carmenate; Adriana Alcántara Cárdenas; Viviana Roche Llerena; Francisco Torrens; Juan A. Castillo-Garit (Medicinal Chemistry Research, 2020)

Seasonal shifts of arbuscular mycorrhizal fungi in Cocos nucifera roots in Yucatan, Mexico - Luis A. Lara-Pérez; Iván Oros-Ortega; Iván Córdova-Lara; Héctor Estrada-Medina; Aileen O’Connor-Sánchez; Elsa Góngora-Castillo; Luis Sáenz-Carbonell (Mycorrhiza, 2020)

Disease-mediated piglet mortality prevents wild boar population growth in fenced overabundant settings - Jose A. Barasona; María A. Risalde; Jose A. Ortíz; David Gonzalez-Barrio; Azlan Che-Amat; Marta Pérez-Sancho; Laura Vargas-Castillo; Anastasios Xeidakis; Estefanía Jurado-Tarifa; Christian Gortázar (European Journal of Wildlife Research, 2020)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Combining Isotopic Techniques to Assess Historical Sediment Delivery in a Forest Catchment in Central Chile - C. Bravo-Linares; P. Schuller; A. Castillo; A. Salinas-Curinao; L. Ovando-Fuentealba; E. Muñoz-Arcos; A. Swales; M. Gibbs; G. Dercon (Journal of Soil Science and Plant Nutrition, 2020)

Update of the population size and breeding performance of gentoo penguins (Pygoscelis papua) at Stranger Point/Cabo Funes, South Shetland Islands - Mariana A. Juáres; Ricardo Casaux; Javier Negrete; Ayelen Rios; Martín Castillo; Néstor R. Coria; Mercedes M. Santos (Polar Biology, 2020)

Phosphodiesterase 7 Regulation in Cellular and Rodent Models of Parkinson’s Disease - Jose A. Morales-Garcia; Sandra Alonso-Gil; Ángel Santos; Ana Perez-Castillo (Molecular Neurobiology, 2020)

Clinical isolates of Escherichia coli are resistant both to antibiotics and organotin compounds - M. Aguilar-Santelises; J. Castillo-Vera; R. Gonzalez-Molina; A. Garcia del Valle; M. Cruz Millan; L. Aguilar-Santelises (Folia Microbiologica, 2020)

Atacama Database: a platform of the microbiome of the Atacama Desert - Carolina A. Contador; Luis Veas-Castillo; Emilio Tapia; Marcela Antipán; Noemi Miranda; Benjamín Ruiz-Tagle; Jonathan García-Araya; Barbara A. Andrews; Mauricio Marin; Cristina Dorador; Juan A. Asenjo (Antonie van Leeuwenhoek, 2020)

Breakthrough Invasive Fungal Infections in Patients with Acute Myeloid Leukemia - Anastasia Wasylyshyn; Kathleen A. Linder; Caroline G. Castillo; Shiwei Zhou; Carol A. Kauffman; Marisa H. Miceli (Mycopathologia, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Utilization of naproxen by Amycolatopsis sp. Poz 14 and detection of the enzymes involved in the degradation metabolic pathway - B. M. Alanis-Sánchez; S. M. Pérez-Tapia; S. Vázquez-Leyva; I. Mejía-Calvo; Z. Macías-Palacios; L. Vallejo-Castillo; C. M. Flores-Ortiz; C. Guerrero-Barajas; J. A. Cruz-Maya; J. Jan-Roblero (World Journal of Microbiology and Biotechnology, 2019)

Field Performance of Two Methods for Detection of Poliovirus in Wastewater Samples, Mexico 2016–2017 - Concepción F. Estívariz; Elda E. Pérez-Sánchez; Anita Bahena; Cara C. Burns; Howard E. Gary; Herlinda García-Lozano; Gloria Rey-Benito; Silvia Peñaranda; Katy V. Castillo-Montufar; Raúl S. Nava-Acosta; John Scott Meschke; M. Steven Oberste; et al. (Food and Environmental Virology, 2019)

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

Availability of copper in mine tailings with humic substance addition and uptake by Atriplex halimus - Y. Tapia; M. Casanova; B. Castillo; E. Acuña; J. Covarrubias; M. Antilén; A. Masaguer (Environmental Monitoring and Assessment, 2019)

The effects of commonly used anaesthetics on colour measurements across body regions in the poeciliid fish, Girardinus metallicus - Erin M. Wojan; Nalana C. Carreiro; David A. Clendenen; Heather M. Neldner; Crystal Castillo; Susan M. Bertram; Gita R. Kolluru (Journal of Fish Biology, 2019)
The effects of common anaesthetics on the hue, saturation and brightness measurements of the poeciliid fish Girardinus metallicus were investigated in two experiments. For both experiments the coloration of four body regions was measured from digital images of the same males obtained under three conditions: (1) control (in a water‐filled chamber); (2) anaesthetised with MS‐222; and (3) anaesthetised with eugenol (clove oil). In experiment 1 anaesthetised fish were photographed out of water. In experiment 2 all photographs were taken in a water‐filled chamber. Anaesthetics altered coloration in both experiments. In the more methodologically consistent experiment 2 we found significantly different hue, increased saturation and decreased brightness in anaesthetic v . control conditions, consistent with darkening caused by the anaesthetics. The body regions differed in coloration consistent with countershading but did not differentially change in response to anaesthesia. These findings suggest that photographing fish in a water‐filled chamber without anaesthetic is preferable for obtaining digital images for colour analysis and that multiple body regions of fish should be measured when assessing coloration patterns meaningful in behavioural contexts, to account for the gradients caused by countershading. We are encouraged that some researchers employ such methods already and caution against using anaesthetics except when absolutely necessary for immobilisation.

Nearshore coral growth declining on the Mesoamerican Barrier Reef System - Justin H. Baumann; Justin B. Ries; John P. Rippe; Travis A. Courtney; Hannah E. Aichelman; Isaac Westfield; Karl D. Castillo (Global Change Biology, 2019)
Anthropogenic global change and local stressors are impacting coral growth and survival worldwide, altering the structure and function of coral reef ecosystems. Here, we show that skeletal extension rates of nearshore colonies of two abundant and widespread Caribbean corals ( Siderastrea siderea , Pseudodiploria strigosa ) declined across the Belize Mesoamerican Barrier Reef System (MBRS) over the past century, while offshore coral conspecifics exhibited relatively stable extension rates over the same temporal interval. This decline has caused nearshore coral extension rates to converge with those of their historically slower growing offshore coral counterparts. For both species, individual mass coral bleaching events were correlated with low rates of skeletal extension within specific reef environments, but no single bleaching event was correlated with low skeletal extension rates across all reef environments. We postulate that the decline in skeletal extension rates for nearshore corals is driven primarily by the combined effects of long‐term ocean warming and increasing exposure to higher levels of land‐based anthropogenic stressors, with acute thermally induced bleaching events playing a lesser role. If these declining trends in skeletal growth of nearshore S. siderea and P. strigosa continue into the future, the structure and function of these critical nearshore MBRS coral reef systems is likely to be severely impaired.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Deep reef fishes in the world’s epicenter of marine biodiversity - Hudson T. Pinheiro; Bart Shepherd; Cristina Castillo; Rene A. Abesamis; Joshua M. Copus; Richard L. Pyle; Brian D. Greene; Richard R. Coleman; Robert K. Whitton; Emma Thillainath; Abner A. Bucol; Matthew Birt; et al. (Coral Reefs, 2019)

A physiologically-motivated model of cystic fibrosis liquid and solute transport dynamics across primary human nasal epithelia - Florencio Serrano Castillo; Carol A. Bertrand; Michael M. Myerburg; Monica E. Shapiro; Timothy E. Corcoran; Robert S. Parker (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Dopamine Neurotransmission in the Ventral Tegmental Area Promotes Active Forgetting of Cocaine-Associated Memory - Fernando Castillo Díaz; Micaela A. Hernandez; Tomas Capellá; Jorge H. Medina (Molecular Neurobiology, 2019)

Transgenerational effects of inter-ploidy cross direction on reproduction and F2 seed development of Arabidopsis thaliana F1 hybrid triploids - Dorota Duszynska; Bjarni Vilhjalmsson; Rosa Castillo Bravo; Sandesh Swamidatta; Thomas E. Juenger; Mark T. A. Donoghue; Aurélie Comte; Magnus Nordborg; Timothy F. Sharbel; Galina Brychkova; Peter C. McKeown; Charles Spillane (Plant Reproduction, 2019)

ENSO and NAO affect long‐term leaf litter dynamics and stoichiometry of Scots pine and European beech mixedwoods - Ester González de Andrés; Juan A. Blanco; J. Bosco Imbert; Biing T. Guan; Yueh‐Hsin Lo; Federico J. Castillo (Global Change Biology, 2019)
Litterfall dynamics (production, seasonality and nutrient composition) are key factors influencing nutrient cycling. Leaf litter characteristics are modified by species composition, site conditions and water availability. However, significant evidence on how large‐scale, global circulation patterns affect ecophysiological processes at tree and ecosystem level remains scarce due to the difficulty in separating the combined influence of different factors on local climate and tree phenology. To fill this gap, we studied links between leaf litter dynamics with climate and other forest processes, such as tree‐ring width (TRW) and intrinsic water‐use efficiency (iWUE) in two mixtures of Scots pine ( Pinus sylvestris L.) and European beech ( Fagus sylvatica L.) in the south‐western Pyrenees. Temporal series (18 years) of litterfall production and elemental chemical composition were decomposed following the ensemble empirical mode decomposition method and relationships with local climate, large‐scale climatic indices, TRW and Scots pine's iWUE were assessed. Temporal trends in N:P ratios indicated increasing P limitation of soil microbes, thus affecting nutrient availability, as the ecological succession from a pine‐dominated to a beech‐dominated forest took place. A significant influence of large‐scale patterns on tree‐level ecophysiology was explained through the impact of the North Atlantic Oscillation (NAO) and El Niño–Southern Oscillation (ENSO) on water availability. Positive NAO and negative ENSO were related to dry conditions and, consequently, to early needle shedding and increased N:P ratio of both species. Autumn storm activity appears to be related to premature leaf abscission of European beech. Significant cascading effects from large‐scale patterns on local weather influenced pine TRW and iWUE. These variables also responded to leaf stoichiometry fallen 3 years prior to tree‐ring formation. Our results provide evidence of the cascading effect that variability in global climate circulation patterns can have on ecophysiological processes and stand dynamics in mixed forests.

Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Alastair J. M. Lough; Douglas P. Connelly; William B. Homoky; Jeffrey A. Hawkes; Valerie Chavagnac; Alain Castillo; Majid Kazemian; Ko-ichi Nakamura; Tohru Araki; Burkhard Kaulich; Rachel A. Mills (Frontiers in Marine Science, 2019)

Synchrotron micro-X-ray fluorescence shows sulfur accumulation in the middle cortex of N2-fixing legume nodules - Camille Rivard; Laurie Amenc; Samia Benlahrech; Bouchra Makoudi; Mustapha Teffahi; Hiram A. Castillo-Michel; Marine Cotte; Benedikt Lassalle-Kaiser; Jean-Jacques Drevon (Protoplasma, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Neuroprotective effect of Mayan medicinal plant extracts against glutamate-induced toxicity - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Jorge A. Rangel-Méndez; Sergio R. Peraza-Sánchez; Daniel Cortés; Iván Velasco; Rosa E. Moo-Puc (Journal of Natural Medicines, 2019)

The BeWo cell line derived from a human placental choriocarcinoma is permissive for respiratory syncytial virus infection - M. A. Velázquez-Cervantes; M. Martínez-Castillo; L. D. González-García; T. A. Vargas-Pavía; M. G. Martínez-Salazar; I. Mancilla-Herrera; G. León-Reyes; J. García-Cordero; A. C. Helguera-Repetto; M. León-Juárez (Virus Genes, 2019)

Leading by listening, learning by doing: modeling democratic approaches to conservation leadership in graduate education - Karen A. Kainer; Citlalli López Binnqüist; Jonathan L. Dain; Belinda Contreras Jaimes; Patricia Negreros Castillo; Roldan Gonzalez Basulto; Edward A. Ellis; Hannah H. Covert; Rodrigo López Rodríguez; Irving Uriel Hernández Gómez; Fernando Melchor Contreras (Journal of Environmental Studies and Sciences, 2019)

Ladenbergia siranensis (Rubiaceae: Cinchoneae), a new species from the Sira Mountains, Eastern Andes of Central Peru, and the identity of Ladenbergia acutifolia - Eder A. Chilquillo Torres; André Olmos Simões; Joaquina Albán Castillo (Brittonia, 2019)

Antiretroviral Hydrophobic Core Graft-Copolymer Nanoparticles: The Effectiveness against Mutant HIV-1 Strains and in Vivo Distribution after Topical Application - Anita Leporati; Suresh Gupta; Elijah Bolotin; Gerardo Castillo; Joshua Alfaro; Marina B. Gottikh; Alexei A. Bogdanov Jr (Pharmaceutical Research, 2019)

Design, synthesis and in vitro evaluation of a Dopa-organoboron compound that acts as a bladder relaxant through non-catecholamine receptors - Ana L. Ocampo-Néstor; Ruth M. López-Mayorga; Enrique F. Castillo-Henkel; Itzia I. Padilla-Martínez; José G. Trujillo-Ferrara; Marvin A. Soriano-Ursúa (Molecular Diversity, 2019)

Accuracy of the BD MAX™ vaginal panel in the diagnosis of infectious vaginitis - Amaia Aguirre-Quiñonero; I. Sáez de Castillo-Sedano; F. Calvo-Muro; A. Canut-Blasco (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Molecular characterization of a new botybirnavirus that infects Botrytis cinerea - Luis Cottet; Christiaan A. Potgieter; Miguel E. Castro; Antonio Castillo (Archives of Virology, 2019)

Determination of ractopamine residue in tissues and urine from pig fed meat and bone meal - Carolina N. Aroeira; Vivian Feddern; Vanessa Gressler; Luciano Molognoni; Heitor Daguer; Osmar A. Dalla Costa; Gustavo J.M.M. de Lima; Carmen J. Contreras-Castillo (Food Additives & Contaminants: Part A, 2019)

Return period curves for extreme 5-min rainfall amounts at the Barcelona urban network - X. Lana; M. C. Casas-Castillo; C. Serra; R. Rodríguez-Solà; A. Redaño; A. Burgueño; M. D. Martínez (Theoretical and Applied Climatology, 2019)

Selection criteria for high-value biomass: seasonal and morphological variation of polyphenolic content and antioxidant capacity in two brown macroalgae - Angelo Beratto-Ramos; Rosario del P. Castillo-Felices; Nicolás A. Troncoso-Leon; Andrés Agurto-Muñoz; Cristian Agurto-Muñoz (Journal of Applied Phycology, 2019)

Performance of Bi2O3/TiO2 prepared by sol-gel on p-Cresol degradation under solar and visible light - Héctor H. Vigil-Castillo; Aracely Hernández-Ramírez; Jorge L. Guzmán-Mar; Norma A. Ramos-Delgado; Minerva Villanueva-Rodríguez (Environmental Science and Pollution Research, 2019)

New Features for Neuron Classification - Leonardo A. Hernández-Pérez; Duniel Delgado-Castillo; Rainer Martín-Pérez; Rubén Orozco-Morales; Juan V. Lorenzo-Ginori (Neuroinformatics, 2019)

UCYN‐A3, a newly characterized open ocean sublineage of the symbiotic N 2 ‐fixing cyanobacterium Candidatus Atelocyanobacterium thalassa - Francisco M. Cornejo‐Castillo; Maria del Carmen Muñoz‐Marín; Kendra A. Turk‐Kubo; Marta Royo‐Llonch; Hanna Farnelid; Silvia G. Acinas; Jonathan P. Zehr (Environmental Microbiology, 2019)
Summary The symbiotic unicellular cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN‐A) is one of the most abundant and widespread nitrogen (N 2 )‐fixing cyanobacteria in the ocean. Although it remains uncultivated, multiple sublineages have been detected based on partial nitrogenase ( nifH ) gene sequences, including the four most commonly detected sublineages UCYN‐A1, UCYN‐A2, UCYN‐A3 and UCYN‐A4. However, very little is known about UCYN‐A3 beyond the nifH sequences from nifH gene diversity surveys. In this study, single cell sorting, DNA sequencing, qPCR and CARD‐FISH assays revealed discrepancies involving the identification of sublineages, which led to new information on the diversity of the UCYN‐A symbiosis. 16S rRNA and nifH gene sequencing on single sorted cells allowed us to identify the 16S rRNA gene of the uncharacterized UCYN‐A3 sublineage. We designed new CARD‐FISH probes that allowed us to distinguish and observe UCYN‐A2 in a coastal location (SIO Pier; San Diego) and UCYN‐A3 in an open ocean location (Station ALOHA; Hawaii). Moreover, we reconstructed about 13% of the UCYN‐A3 genome from Tara Oceans metagenomic data. Finally, our findings unveil the UCYN‐A3 symbiosis in open ocean waters suggesting that the different UCYN‐A sublineages are distributed along different size fractions of the plankton defined by the cell‐size ranges of their prymnesiophyte hosts.

Peroxicoagulation and Solar Peroxicoagulation for Landfill Leachate Treatment Using a Cu–Fe System - Luis A. Castillo-Suárez; Francisco Bruno-Severo; Violeta Lugo-Lugo; Mario Esparza-Soto; Verónica Martínez-Miranda; Ivonne Linares-Hernández (Water, Air, & Soil Pollution, 2018)

Logging Pattern and Landscape Change in Southern Mexico: Identifying Potential Weaknesses and Strengthening Conservation in Community-Based Management Programs through Landscape Analysis - J A Ascanio-Lárraga; J L León-Cortés; M A Castillo-Santiago; E Ramírez-Segura (Journal of Forestry, 2018)

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

Rainfall intensity patterns derived from the urban network of Barcelona (NE Spain) - Xavier Lana; C. Serra; M. C. Casas-Castillo; R. Rodríguez-Solà; A. Redaño; A. Burgueño (Theoretical and Applied Climatology, 2018)

Secondary metabolites from two Hispaniola Ageratina species and their cytotoxic activity - José Luis Eiroa; Jorge Triana; Francisco J. Pérez; Quírico A. Castillo; Ignacio Brouard; José Quintana; Francisco Estévez; Francisco León (Medicinal Chemistry Research, 2018)

Synthesis, antimicrobial activity, and molecular docking study of fluorine-substituted indole-based imidazolines - Humberto L. Mendoza-Figueroa; Maria Trinidad Serrano-Alva; Gerardo Aparicio-Ozores; Gelacio Martínez-Gudiño; Oscar R. Suárez-Castillo; Nadia A. Pérez-Rojas; Martha S. Morales-Ríos (Medicinal Chemistry Research, 2018)

Dynamic fuzzy neural network for simulating the fixed-bed adsorption of cadmium, nickel, and zinc on bone char - F. A. Gordillo-Ruíz; F. J. Sánchez-Ruíz; D. I. Mendoza-Castillo; H. E. Reynel-Ávila; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2018)

Environmental risk assessment of pesticides in the River Madre de Dios, Costa Rica using PERPEST, SSD, and msPAF models - Robert A. Rämö; Paul J. van den Brink; Clemens Ruepert; Luisa E. Castillo; Jonas S. Gunnarsson (Environmental Science and Pollution Research, 2018)

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Single-cell PCR amplification of thecate dinoflagellates: a case study of Tripos (Dinophyceae) - A. Hernández-Rosas; M. E. Meave del Castillo; J. Díaz-Larrea; F. Rodríguez (Journal of Applied Phycology, 2018)

Molecular and morphological characterization of the spiral nematode Helicotylenchus oleae Inserra, Vovlas & Golden, 1979 (Nematoda: Hoplolaimidae) in the Mediterranean Basin - Juan E. Palomares-Rius; Carolina Cantalapiedra-Navarrete; Antonio Archidona-Yuste; Nicola Vovlas; Emmanuel A. Tzortzakakis; Pablo Castillo (European Journal of Plant Pathology, 2018)

Seascape genomics reveals adaptive divergence in a connected and commercially important mollusc, the greenlip abalone ( Haliotis laevigata ), along a longitudinal environmental gradient - Jonathan Sandoval‐Castillo; Nick A. Robinson; Anthony M. Hart; Lachlan W. S. Strain; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations of broadcast spawning marine organisms often have large sizes and are exposed to reduced genetic drift. Under such scenarios, strong selection associated with spatial environmental heterogeneity is expected to drive localized adaptive divergence, even in the face of connectivity. We tested this hypothesis using a seascape genomics approach in the commercially important greenlip abalone ( Haliotis laevigata ). We assessed how its population structure has been influenced by environmental heterogeneity along a zonal coastal boundary in southern Australia linked by strong oceanographic connectivity. Our data sets include 9,109 filtered SNP s for 371 abalones from 13 localities and environmental mapping across ~800 km. Genotype–environment association analyses and outlier tests defined 8,786 putatively neutral and 323 candidate adaptive loci. From a neutral perspective, the species is better represented by a metapopulation with very low differentiation (global F ST = 0.0081) and weak isolation by distance following a stepping‐stone model. For the candidate adaptive loci, however, model‐based and model‐free approaches indicated five divergent population clusters. After controlling for spatial distance, the distribution of putatively adaptive variation was strongly correlated to selection linked to minimum sea surface temperature and oxygen concentration. Around 80 candidates were annotated to genes with functions related to high temperature and/or low oxygen tolerance, including genes that influence the resilience of abalone species found in other biogeographic regions. Our study includes a documented example about the uptake of genomic information in fisheries management and supports the hypothesis of adaptive divergence due to coastal environmental heterogeneity in a connected metapopulation of a broadcast spawner.

Atom based linear index descriptors in QSAR-machine learning classifiers for the prediction of ubiquitin-proteasome pathway activity - Gerardo M. Casañola-Martin; Hai Pham-The; Juan A. Castillo-Garit; Huong Le-Thi-Thu (Medicinal Chemistry Research, 2018)

Impact of activated sludge acclimation on the biodegradation of toluene absorbed in a hydrophobic ionic liquid - A. S. Rodriguez Castillo; S. Guihéneuf; P.-F. Biard; L. Paquin; A. Amrane; A. Couvert (International Journal of Environmental Science and Technology, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Glycemic response after glucose oral administration of wild juvenile red grouper Epinephelus morio fed two different diets - A. Castillo; A. Alvarez; G. Cuzon; J. Suárez; G. Gaxiola (Fish Physiology and Biochemistry, 2018)

Prevalence and molecular diversity of reniform nematodes of the genus Rotylenchulus (Nematoda: Rotylenchulinae) in the Mediterranean Basin - Juan E. Palomares-Rius; Carolina Cantalapiedra-Navarrete; Antonio Archidona-Yuste; Emmanuel A. Tzortzakakis; Ioannis G. Birmpilis; Nicola Vovlas; Sergei A. Subbotin; Pablo Castillo (European Journal of Plant Pathology, 2018)

Complete genome sequence of datura leaf curl virus, a novel begomovirus infecting Datura innoxia in Sudan, related to begomoviruses causing tomato yellow leaf curl disease - Heyam S. Mohammed; Marmar A. El Siddig; Adil A. El Hussein; Jesús Navas-Castillo; Elvira Fiallo-Olivé (Archives of Virology, 2018)

Monitoring of landslide displacements using UAS and control methods based on lines - A. T. Mozas-Calvache; J. L. Pérez-García; T. Fernández-del Castillo (Landslides, 2017)

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department - J. González del Castillo; A. Julian-Jiménez; F. González-Martínez; J. Álvarez-Manzanares; P. Piñera; C. Navarro-Bustos; M. Martinez-Ortiz de Zarate; F. Llopis-Roca; M. Debán Fernández; J. Gamazo-Del Rio; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Oceanographic and lunar forcing affects nearshore larval fish assemblages from temperate rocky reefs - Macarena Díaz-Astudillo; Manuel I. Castillo; Mario A. Cáceres; Guido Plaza; Mauricio F. Landaeta (Marine Biology Research, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Comparative assessment of Vibrio virulence in marine fish larvae - A Rønneseth; D Castillo; P D'Alvise; Ø Tønnesen; G Haugland; T Grotkjær; K Engell‐Sørensen; L Nørremark; Ø Bergh; H I Wergeland; L Gram (Journal of Fish Diseases, 2017)
Vibrionaceae infections are a major obstacle for marine larviculture; however, little is known about virulence differences of Vibrio strains. The virulence of Vibrio strains, mostly isolated from vibriosis outbreaks in farmed fish, was tested in larval challenge trials with cod ( Gadus morhua ), turbot ( Scophthalmus maximus ) and halibut ( Hippoglossus hippoglossus ) using a multiwell dish assays with single‐egg/larvae cultures. The strains differed significantly in virulence as some caused a high mortality of larva reaching 100% mortality after a few days, while others had no or only marginal effects on survival. Some Vibrio strains were pathogenic in all of the larva species, while some caused disease only in one of the species. Twenty‐nine of the Vibrio anguillarum strains increased the mortality of larvae from at least one fish species; however, pathogenicity of the strains differed markedly. Other Vibrio species had no or less pronounced effects on larval mortalities. Iron uptake has been related to V. anguillarum virulence; however, the presence or absence of the plasmid pJM 1 encoding anguibactin did not correlate with virulence. The genomes of V. anguillarum were compared (D. Castillo, P.W. D'Alvise, M. Middelboe & L. Gram, unpublished data) and most of the high‐virulent strains had acquired virulence genes from other pathogenic Vibrio .

Study of the Ultrastructure of Eucalyptus globulus Wood Substrates Subjected to Auto-Hydrolysis and Diluted Acid Hydrolysis Pre-treatments and Its Influence on Enzymatic Hydrolysis - Cristian Arévalo; Juanita Freer; Pamela A. Naulin; Nelson P. Barrera; Eduardo Troncoso; Juan Araya; Carlos Peña-Farfal; Rosario del P. Castillo (BioEnergy Research, 2017)

Semaphorin 7A as a Potential Therapeutic Target for Multiple Sclerosis - Ana Gutiérrez-Franco; Herena Eixarch; Carme Costa; Vanessa Gil; Mireia Castillo; Laura Calvo-Barreiro; Xavier Montalban; José A. Del Río; Carmen Espejo (Molecular Neurobiology, 2017)

Isotopic evidence for intersexual foraging variation in northern elephant seals from Baja California, Mexico - Miriam A. Velázquez-Castillo; Fernando R. Elorriaga-Verplancken (Marine Biology, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Prevalence, geographic distribution and phenotypic differences of Piscirickettsia salmonis EM ‐90‐like isolates - J Saavedra; N Hernandez; A Osses; A Castillo; A Cancino; H Grothusen; E Navas; P Henriquez; H Bohle; F Bustamante; P Bustos; M Mancilla (Journal of Fish Diseases, 2017)
Early reports accounted for two main genotypes of Piscirickettsia salmonis , a fish pathogen and causative agent of piscirickettsiosis, placing the single isolate EM ‐90 apart from the prototypic LF ‐89 and related isolates. In this study, we provide evidence that, contrary to what has been supposed, the EM ‐90‐like isolates are highly prevalent and disseminated across Chilean marine farms. Molecular analysis of 507 P. salmonis field isolates derived from main rearing areas, diverse hosts and collected over 6 years, revealed that nearly 50% of the entire collection were indeed typed as EM ‐90‐like. Interestingly, these isolates showed a marked host preference, being recovered exclusively from Atlantic salmon ( Salmo salar ) samples. Although both strains produce undistinguishable pathological outcomes, differences regarding growth kinetics and susceptibility to the antibiotics and bactericidal action of serum could be identified. In sum, our results allow to conclude that the EM ‐90‐like isolates represent an epidemiologically relevant group in the current situation of piscirickettsiosis. Based on the consistency between genotype and phenotype exhibited by this strain, we point out the need for genotypic studies that may be as important for the Chilean salmon industry as the continuous surveillance of antimicrobial susceptibility patterns.

Molecular characterization of pseudomonodelphic dagger nematodes of the genus Xiphinema Cobb, 1913 (Nematoda: Longidoridae) in Costa Rica, with notes on Xiphinema setariae Tarjan, 1964 - Walter Peraza-Padilla; Antonio Archidona-Yuste; Howard Ferris; Tatiana Zamora-Araya; Carolina Cantalapiedra-Navarrete; Juan E. Palomares-Rius; Sergei A. Subbotin; Pablo Castillo (European Journal of Plant Pathology, 2017)

Expression Changes in Metal-Resistance Genes in Microbacterium liquefaciens Under Nickel and Vanadium Exposure - Grisel Fierros-Romero; José A. Wrosek-Cabrera; Marlenne Gómez-Ramírez; Reynaldo C. Pless; A. M. Rivas-Castillo; Norma G. Rojas-Avelizapa (Current Microbiology, 2017)

Expression of typical osteoclast markers by PBMCs after PEG-induced fusion as a model for studying osteoclast differentiation - Luz M. Castillo; Carlos A. Guerrero; Orlando Acosta (Journal of Molecular Histology, 2017)

Antimicrobial and hormetic effects of silver nanoparticles on in vitro regeneration of vanilla (Vanilla planifolia Jacks. ex Andrews) using a temporary immersion system - J. L. Spinoso-Castillo; R. A. Chavez-Santoscoy; Nina Bogdanchikova; J. A. Pérez-Sato; V. Morales-Ramos; J. J. Bello-Bello (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Ideal cardiovascular health and liver enzyme levels in European adolescents; the HELENA study - Idoia Labayen; Jonatan R. Ruiz; Inge Huybrechts; Francisco B. Ortega; Manuel Castillo; Michael Sjöstrom; Marcela González-Gross; Yannis Manios; Kurt Widhalm; Anthony Kafatos; Christina Breidenassel; Gerardo Rodríguez; et al. (Journal of Physiology and Biochemistry, 2017)

Effects of feeding ground pods of Enterolobium cyclocarpum Jacq. Griseb on dry matter intake, rumen fermentation, and enteric methane production by Pelibuey sheep fed tropical grass - S. Albores-Moreno; J. A. Alayón-Gamboa; A. J. Ayala-Burgos; F. J. Solorio-Sánchez; C. F. Aguilar-Pérez; L. Olivera-Castillo; J. C. Ku-Vera (Tropical Animal Health and Production, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Geochemistry of deep-sea sediments in two cores retrieved at the mouth of the Coatzacoalcos River delta, western Gulf of Mexico, Mexico - Mayla A. Ramos-Vázquez; John S. Armstrong-Altrin; Leticia Rosales-Hoz; María L. Machain-Castillo; Arturo Carranza-Edwards (Arabian Journal of Geosciences, 2017)

Effects of cryopreservation on mitochondria of fish spermatozoa - Elías Figueroa; Iván Valdebenito; Andrea B. Zepeda; Carolina A. Figueroa; Kelly Dumorné; Rodrigo L. Castillo; Jorge G. Farias (Reviews in Aquaculture, 2017)
The development of sperm cryopreservation has enabled transcendental changes to occur in the reproductive biotechnology of both mammals and fish; it has become a basic tool for animal improvement. Nevertheless, these protocols cause damage to cell structure and physiology, altering sperm functioning due to cryo‐injuries during freezing and thawing. However, studies of the effects on the structural, functional and genomic stability of the mitochondria in fish spermatozoa during cryopreservation are still lacking. The object of this review was to analyse the effect of cryopreservation on mitochondrial metabolic pathways in fish spermatozoa. This effect is related with the bioenergy mechanism for flagellar movement during the activation of sperm motility. In teleost fish, the mitochondria may be cylindrical, spherical or irregular in shape and adhere in a helicoidal or conical pattern to the middle piece. The salmonidae have only a single mitochondrion, but this may vary in other species; the mitochondria provide the flagellum with energy during sperm motility, when sperm respiration is essential. The effects of cryopreservation can induce structural damage to the mitochondria, altering the biochemical process involved in ATP production and thus causing a reduction in sperm motility. Fragmentation damage to nuclear DNA and diminution in sperm motility is mainly associated with damage to the structure and metabolic functioning of the mitochondrion. A direct correlation exists between the mitochondrial membrane potential (transmembrane integrity, ∆ Ψ m ) and the motility and fertilizing capacity of the cryopreserved spermatozoa, confirming that this organelle is the energy nucleus of the spermatozoon and that the cessation or prolongation of motility and successful fertilization depend on the availability of ATP in the spermatozoa. Further works are need to incorporate biotechnology studies, at cell and molecular level, of the possible effects of cryopreservation on mitochondrial DNA , enzymatic or metabolic modifications of the citric acid cycle, and the oxidative phosphorylation process in the inner membrane, as well as studies of the mitochondrial ultrastructure. Thus, mitochondrial dynamics could be established as a potential target for therapeutic strategies.

New sources of resistance to Septoria tritici blotch in wheat seedlings - María Rosa Simón; Nadia S. Castillo; Cristina A. Cordo (European Journal of Plant Pathology, 2016)

Extreme 15N Depletion in Seagrasses - M. E. M. Walton; I. Al-Maslamani; N. Haddaway; H. Kennedy; A. Castillo; E. S. Al-Ansari; I. Al-Shaikh; M. Abdel-Moati; M. A. A. Al-Yafei; L. Le Vay (Estuaries and Coasts, 2016)

Carboxyl terminus-truncated α1D-adrenoceptors inhibit the ERK pathway - Marco A. Alfonzo-Méndez; Jean A. Castillo-Badillo; M. Teresa Romero-Ávila; Richard Rivera; Jerold Chun; J. Adolfo García-Sáinz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Manganese and Mercury Levels in Water, Sediments, and Children Living Near Gold-Mining Areas of the Nangaritza River Basin, Ecuadorian Amazon - Max V. González-Merizalde; José A. Menezes-Filho; Claudia Teresa Cruz-Erazo; Santos Amable Bermeo-Flores; María Obdulia Sánchez-Castillo; David Hernández-Bonilla; Abrahan Mora (Archives of Environmental Contamination and Toxicology, 2016)

Drivers of fluorescent dissolved organic matter in the global epipelagic ocean - T. S. Catalá; X. A. Álvarez‐Salgado; J. Otero; F. Iuculano; B. Companys; B. Horstkotte; C. Romera‐Castillo; M. Nieto‐Cid; M. Latasa; X. A. G. Morán; J. M. Gasol; C. Marrasé; et al. (Limnology and Oceanography, 2016)
Fluorescent dissolved organic matter (FDOM) in open surface waters ( 70%) than for the amino acid‐like components ( a . Positive non‐linear relationships between both predictor variables and the two humic‐like PARAFAC components suggest that their distribution are biologically controlled. Compared with the dark ocean (> 200 m), the relationships of C1 and C2 with AOU indicate a higher C1/AOU and C2/AOU ratios of the humic‐like substances in the dark ocean than in the surface ocean where a net effect of photobleaching is also detected. C3 (tryptophan‐like) and C4 (tyrosine‐like) variability was mostly dictated by salinity ( S ), by means of positive non‐linear relationships, suggesting a primary physical control of their distributions at the global surface ocean scale that could be related to the changing evaporation‐precipitation regime. Remarkably, bacterial biomass (BB) only contributed to explain a minor part of the variability of C1 and C4.

Application of a multi-criteria decision model to select of design choices for WWTPs - M. Garrido-Baserba; R. Reif; M. Molinos-Senante; L. Larrea; A. Castillo; M. Verdaguer; M. Poch (Clean Technologies and Environmental Policy, 2016)

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

Antioxidant and toxicological evaluation of a Tamarindus indica L. leaf fluid extract - J.C. Escalona-Arranz; R. Perez-Rosés; J. Rodríguez-Amado; H.J. Morris-Quevedo; L.B. Mwasi; O. Cabrera-Sotomayor; R. Machado-García; O. Fong-Lórez; A. Alfonso-Castillo; E. Puente-Zapata (Natural Product Research, 2016)

Rotylenchus cretensis n. sp. and R. cypriensis Antoniou 1980 (Nematoda: Hoplolaimidae) recovered from the rhizosphere of olive at Crete (Greece) with a molecular phylogeny of the genus - Emmanuel A. Tzortzakakis; Antonio Archidona-Yuste; Gracia Liébanas; Ioannis G. Birmpilis; Carolina Cantalapiedra-Navarrete; Juan A. Navas-Cortés; Pablo Castillo; Juan E. Palomares-Rius (European Journal of Plant Pathology, 2016)

Seasonality in marine ecosystems: Peruvian seabirds, anchovy, and oceanographic conditions - Giannina Passuni; Christophe Barbraud; Alexis Chaigneau; Hervé Demarcq; Jesus Ledesma; Arnaud Bertrand; Ramiro Castillo; Angel Perea; Julio Mori; Vincent A. Viblanc; Jose Torres‐Maita; Sophie Bertrand (Ecology, 2016)
In fluctuating environments, matching breeding timing to periods of high resource availability is crucial for the fitness of many vertebrate species, and may have major consequences on population health. Yet, our understanding of the proximate environmental cues driving seasonal breeding is limited. This is particularly the case in marine ecosystems, where key environmental factors and prey abundance and availability are seldom quantified. The Northern Humboldt Current System ( NHCS ) is a highly productive, low‐latitude ecosystem of moderate seasonality. In this ecosystem, three tropical seabird species (the Guanay Cormorant Phalacrocorax bougainvillii , the Peruvian Booby Sula variegata , and the Peruvian Pelican Pelecanus thagus ) live in sympatry and prey almost exclusively on anchovy, Engraulis ringens . From January 2003 to December 2012, we monitored 31 breeding sites along the Peruvian coast to investigate the breeding cycle of these species. We tested for relationships between breeding timing, oceanographic conditions, and prey availability using occupancy models. We found that all three seabird species exhibited seasonal breeding patterns, with marked interspecific differences. Whereas breeding mainly started during the austral winter/early spring and ended in summer/early fall, this pattern was stronger in boobies and pelicans than in cormorants. Breeding onset mainly occurred when upwelling was intense but ecosystem productivity was below its annual maxima, and when anchovy were less available and in poor physiological condition. Conversely, the abundance and availability of anchovy improved during chick rearing and peaked around the time of fledging. These results suggest that breeding timing is adjusted so that fledging may occur under optimal environmental conditions, rather than being constrained by nutritional requirements during egg laying. Adjusting breeding time so that fledglings meet optimal conditions at independence is unique compared with other upwelling ecosystems and could be explained by the relatively high abundances of anchovy occurring throughout the year in the NHCS .

Parasitism effects on white clover by root-knot and cyst nematodes and molecular separation of Heterodera daverti from H. trifolii - Nicola Vovlas; Alessio Vovlas; Paola Leonetti; Gracia Liébanas; Pablo Castillo; Sergei A. Subbotin; Juan E. Palomares Rius (European Journal of Plant Pathology, 2015)

Nonlinear relationship between waist to hip ratio, weight and strength in elders: is gender the key? - Carmen Castillo; José A. Carnicero; Mari Ángeles de la Torre; Solange Amor; Amelia Guadalupe-Grau; Leocadio Rodríguez-Mañas; Francisco J. García-García (Biogerontology, 2015)

A Study on the Knowledge, Perception, and Use of Breast Cancer Screening Methods and Quality of Care Among Women from Central Mexico - Andrea B. Cruz-Castillo; María A. Hernández-Valero; Shelly R. Hovick; Martha Elva Campuzano-González; Miguel Angel Karam-Calderón; L. Patricia Bustamante-Montes (Journal of Cancer Education, 2015)

Chemical modification of Byrsonima crassifolia with citric acid for the competitive sorption of heavy metals from water - J. Monroy-Figueroa; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet; M. A. Pérez-Cruz (International Journal of Environmental Science and Technology, 2015)

Host reaction of Aloe vera infected by Meloidogyne incognita and M. javanica in Crete Island (Greece) - Juan E. Palomares-Rius; Pablo Castillo; Hava Rapoport; Antonio Archidona-Yuste; Emmanuel A. Tzortzakakis (European Journal of Plant Pathology, 2015)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state - H. M. González-Sánchez; A. Monsiváis-Urenda; C. A. Salazar-Aldrete; A. Hernández-Salinas; D. E. Noyola; M. E. Jiménez-Capdeville; A. Martínez-Serrano; C. G. Castillo (Journal of NeuroVirology, 2015)

Spinal cord toxoplasmosis in human immunodeficiency virus infection/acquired immunodeficiency syndrome - Concepción García-García; Federico Castillo-Álvarez; José M. Azcona-Gutiérrez; María J. Herraiz; Valvanera Ibarra; José A. Oteo (Infectious Diseases, 2015)

Removal of heavy metals and arsenic from aqueous solution using textile wastes from denim industry - D. I. Mendoza-Castillo; C. K. Rojas-Mayorga; I. P. García-Martínez; M. A. Pérez-Cruz; V. Hernández-Montoya; A. Bonilla-Petriciolet; M. A. Montes-Morán (International Journal of Environmental Science and Technology, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Aspects of soil lichen biodiversity and aggregation interact to influence subsurface microbial function - Andrea P. Castillo-Monroy; Matthew A. Bowker; Pablo García-Palacios; Fernando T. Maestre (Plant and Soil, 2015)

Secretion of biologically active human interleukin 22 (IL-22) by Lactococcus lactis - María J. Loera-Arias; Julio Villatoro-Hernández; Miguel A. Parga-Castillo; Alejandro Salcido-Montenegro; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Roberto Montes-de-Oca-Luna; Odila Saucedo-Cárdenas (Biotechnology Letters, 2014)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Study of the vegetation in the Multiple Use Natural Reserve of Monterrico (Guatemala) - A. García-Fuentes; F.J. Castillo-Cabrera; C.V. Dávila-Pérez; A.S. Morales; C. Salazar-Mendías; M.L. Lendínez-Barriga; J.A. Torres-Cordero; L. Ruiz-Valenzuela (Plant Biosystems, 2014)

Integrative diagnosis and molecular phylogeny of dagger and needle nematodes of olives and grapevines in the island of Crete, Greece, with description of Xiphinema cretense n. sp. (Nematoda, Longidoridae) - Emmanuel A. Tzortzakakis; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Eleni Nasiou; Maria S. Lazanaki; Emmanouil M. Kabourakis; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2014)

Biodiversity and indigenous management of the endangered non-toxic germplasm of Jatropha curcas L. in the Totonacapan (Mexico), and the implications for its conservation - Yolanda B. Vera-Castillo; Jesús A. Cuevas; Ana G. Valenzuela-Zapata; Beatriz Urbano; Fernando González-Andrés (Genetic Resources and Crop Evolution, 2014)

Community metabolism in a deep (stratified) tropical reservoir during a period of high water-level fluctuations - Patricia M. Valdespino-Castillo; Martín Merino-Ibarra; Jorge Jiménez-Contreras; Fermín S. Castillo-Sandoval; Jorge A. Ramírez-Zierold (Environmental Monitoring and Assessment, 2014)

Decadal trends in the pollinator assemblage of Eucryphia cordifolia in Chilean rainforests - Cecilia Smith-Ramírez; Rodrigo Ramos-Jiliberto; Fernanda S. Valdovinos; Paula Martínez; Jessica A. Castillo; Juan J. Armesto (Oecologia, 2014)

Metal ion remediation by polyamidoamine dendrimers: a comparison of metal ion, oxidation state, and titania immobilization - V. A. Castillo; M. A. Barakat; M. H. Ramadan; H. L. Woodcock; J. N. Kuhn (International Journal of Environmental Science and Technology, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

A novel begomovirus isolated from sida contains putative cis- and trans-acting replication specificity determinants that have evolved independently in several geographical lineages - J. A. Mauricio-Castillo; S. I. Torres-Herrera; Y. Cárdenas-Conejo; G. Pastor-Palacios; J. Méndez-Lozano; G. R. Argüello-Astorga (Archives of Virology, 2014)

Begomovirus diversity in tomato crops and weeds in Ecuador and the detection of a recombinant isolate of rhynchosia golden mosaic Yucatan virus infecting tomato - Lenin C. Paz-Carrasco; Gloria P. Castillo-Urquiza; Alison T. M. Lima; Cesar A. D. Xavier; Leticia M. Vivas-Vivas; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2014)

Effects of n-butanol on barley microspore embryogenesis - A. M. Castillo; N. H. Nielsen; A. Jensen; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Biological soil crusts (biocrusts) as a model system in community, landscape and ecosystem ecology - Matthew A. Bowker; Fernando T. Maestre; David Eldridge; Jayne Belnap; Andrea Castillo-Monroy; Cristina Escolar; Santiago Soliveres (Biodiversity and Conservation, 2014)

Spatial patterns of neutral and functional genetic variations reveal patterns of local adaptation in raccoon ( P rocyon lotor ) populations exposed to raccoon rabies - Christopher J. Kyle; Yessica Rico; Sarrah Castillo; Vythegi Srithayakumar; Catherine I. Cullingham; Bradley N. White; Bruce A. Pond (Molecular Ecology, 2014)
Local adaptation is necessary for population survival and depends on the interplay between responses to selective forces and demographic processes that introduce or retain adaptive and maladaptive attributes. Host–parasite systems are dynamic, varying in space and time, where both host and parasites must adapt to their ever‐changing environment in order to survive. We investigated patterns of local adaptation in raccoon populations with varying temporal exposure to the raccoon rabies virus ( RRV ). RRV infects approximately 85% of the population when epizootic and has been presumed to be completely lethal once contracted; however, disease challenge experiments and varying spatial patterns of RRV spread suggest some level of immunity may exist. We first assessed patterns of local adaptation in raccoon populations along the eastern seaboard of N orth A merica by contrasting spatial patterns of neutral (microsatellite loci) and functional, major histocompatibility complex ( MHC ) genetic diversity and structure. We explored variation of MHC allele frequencies in the light of temporal population exposure to RRV (0–60 years) and specific RRV strains in infected raccoons. Our results revealed high levels of MHC variation (66 DRB exon 2 alleles) and pronounced genetic structure relative to neutral microsatellite loci, indicative of local adaptation. We found a positive association linking MHC genetic diversity and temporal RRV exposure, but no association with susceptibility and resistance to RRV strains. These results have implications for landscape epidemiology studies seeking to predict the spread of RRV and present an example of how population demographics influence the degree to which populations adapt to local selective pressures.

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Microbial diversity in Los Azufres geothermal field (Michoacán, Mexico) and isolation of representative sulfate and sulfur reducers - Elcia M. S. Brito; Norberto Villegas-Negrete; Irene A. Sotelo-González; César A. Caretta; Marisol Goñi-Urriza; Claire Gassie; Florence Hakil; Yannick Colin; Robert Duran; Felix Gutiérrez-Corona; Hilda A. Piñón-Castillo; Germán Cuevas-Rodríguez; et al. (Extremophiles, 2014)

Changes in gene expression patterns associated with microspore embryogenesis in hexaploid triticale (×Triticosecale Wittm.) - I. Żur; E. Dubas; M. Krzewska; R. A. Sánchez-Díaz; A. M. Castillo; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Landscape effects on gene flow for a climate‐sensitive montane species, the A merican pika - Jessica A. Castillo; Clinton W. Epps; Anne R. Davis; Samuel A. Cushman (Molecular Ecology, 2014)
Climate change is arguably the greatest challenge to conservation of our time. Most vulnerability assessments rely on past and current species distributions to predict future persistence but ignore species' abilities to disperse through landscapes, which may be particularly important in fragmented habitats and crucial for long‐term persistence in changing environments. Landscape genetic approaches explore the interactions between landscape features and gene flow and can clarify how organisms move among suitable habitats, but have suffered from methodological uncertainties. We used a landscape genetic approach to determine how landscape and climate‐related features influence gene flow for A merican pikas ( O chotona princeps ) in C rater Lake National Park. Pikas are heat intolerant and restricted to cool microclimates; thus, range contractions have been predicted as climate changes. We evaluated the correlation between landscape variables and genetic distance using partial Mantel tests in a causal modelling framework, and used spatially explicit simulations to evaluate methods of model optimization including a novel approach based on relative support and reciprocal causal modelling. We found that gene flow was primarily restricted by topographic relief, water and west‐facing aspects, suggesting that physical restrictions related to small body size and mode of locomotion, as well as exposure to relatively high temperatures, limit pika dispersal in this alpine habitat. Our model optimization successfully identified landscape features influencing resistance in the simulated data for this landscape, but underestimated the magnitude of resistance. This is the first landscape genetic study to address the fundamental question of what limits dispersal and gene flow in the A merican pika.

Analysis of the scallop microbiota by means of 16S rRNA gene pyrosequencing - Lasa Aide; Mira Alex; Camelo-Castillo A; Belda-Ferre P.; Romalde Jesus (Frontiers in Marine Science, 2014)

Omeprazole and PGC-Formulated Heparin Binding Epidermal Growth Factor Normalizes Fasting Blood Glucose and Suppresses Insulitis in Multiple Low Dose Streptozotocin Diabetes Model - Gerardo M. Castillo; Akiko Nishimoto-Ashfield; Aryamitra A. Banerjee; Jennifer A. Landolfi; Alexander V. Lyubimov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

Regional signatures of plant response to drought and elevated temperature across a desert ecosystem - Seth M. Munson; Esteban H. Muldavin; Jayne Belnap; Debra P. C. Peters; John P. Anderson; M. Hildegard Reiser; Kirsten Gallo; Alicia Melgoza-Castillo; Jeffrey E. Herrick; Tim A. Christiansen (Ecology, 2013)
The performance of many desert plant species in North America may decline with the warmer and drier conditions predicted by climate change models, thereby accelerating land degradation and reducing ecosystem productivity. We paired repeat measurements of plant canopy cover with climate at multiple sites across the Chihuahuan Desert over the last century to determine which plant species and functional types may be the most sensitive to climate change. We found that the dominant perennial grass, Bouteloua eriopoda , and species richness had nonlinear responses to summer precipitation, decreasing more in dry summers than increasing with wet summers. Dominant shrub species responded differently to the seasonality of precipitation and drought, but winter precipitation best explained changes in the cover of woody vegetation in upland grasslands and may contribute to woody‐plant encroachment that is widespread throughout the southwestern United States and northern Mexico. Temperature explained additional variability of changes in cover of dominant and subdominant plant species. Using a novel empirically based approach we identified “climate pivot points” that were indicative of shifts from increasing to decreasing plant cover over a range of climatic conditions. Reductions in cover of annual and several perennial plant species, in addition to declines in species richness below the long‐term summer precipitation mean across plant communities, indicate a decrease in the productivity for all but the most drought‐tolerant perennial grasses and shrubs in the Chihuahuan Desert. Overall, our regional synthesis of long‐term data provides a robust foundation for forecasting future shifts in the composition and structure of plant assemblages in the largest North American warm desert.

Axonal regeneration after spinal cord injury in zebrafish and mammals: differences, similarities, translation - Katarina Vajn; Jeffery A. Plunkett; Alexis Tapanes-Castillo; Martin Oudega (Neuroscience Bulletin, 2013)

The PsbO homolog from Symbiodinium kawagutii (Dinophyceae) characterized using biochemical and molecular methods - Raúl E. Castillo-Medina; Tania Islas-Flores; Patricia E. Thomé; Roberto Iglesias-Prieto; Senjie Lin; Huan Zhang; Marco A. Villanueva (Photosynthesis Research, 2013)

The Missing Skill Set in Community Management of Tropical Forests - MIGUEL N. ALEXIADES; CHARLES M. PETERS; SARAH A. LAIRD; CITLALLI LÓPEZ BINNQÜIST; PATRICIA NEGREROS CASTILLO (Conservation Biology, 2013)

Effect of rice polishing and phytase supplementation in diets on productive behavior of broilers - Jaime Salinas-Chavira; Zaira N. Montoya-Chávez; Jose Castañeda-Licón; Lorenzo A. Duran-Meléndez; David López-Cantú; Fidel Infante-Rodríguez; Jose O. Jasso-Obregón; Martin F. Montano-Gomez; Ramón F. García-Castillo (Tropical Animal Health and Production, 2013)

Association between individual genetic diversity of two oak host species and canopy arthropod community structure - E. Tovar-Sánchez; L. Valencia-Cuevas; E. Castillo-Mendoza; P. Mussali-Galante; R. V. Pérez-Ruiz; A. Mendoza (European Journal of Forest Research, 2013)

Population structure, habitat features and genetic structure of managed red deer populations - J. Pérez-González; A. C. Frantz; J. Torres-Porras; L. Castillo; J. Carranza (European Journal of Wildlife Research, 2012)

Tagging the next generation: validation of trans-generational chemical tagging for an endangered fish - James A. Hobbs; Gonzalo Castillo; Galen Tigan; Joan Lindberg; Naoaki Ikemiyagi; Georgia Ramos (Environmental Biology of Fishes, 2012)

Identification and origin of host-associated volatiles attractive to Prorops nasuta, a parasitoid of the coffee berry borer - Ariana K. Román-Ruíz; Edi A. Malo; Graciela Huerta; Alfredo Castillo; Juan F. Barrera; Julio C. Rojas (Arthropod-Plant Interactions, 2012)

The Mexican Sugarcane Industry: Overview, Constraints, Current Status and Long-Term Trends - N. Aguilar-Rivera; D. A. Rodríguez L.; V. Enríquez R.; A. Castillo M.; A. Herrera S. (Sugar Tech, 2012)

Time to positivity of blood culture association with clinical presentation, prognosis and ESBL-production in Escherichia coli bacteremia - R. Álvarez; L. Viñas-Castillo; J. A. Lepe-Jiménez; E. García-Cabrera; J. M. Cisneros-Herreros (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A new strain of tomato severe leaf curl virus and a unique variant of tomato yellow leaf curl virus from Mexico - B. Bañuelos-Hernández; J. A. Mauricio-Castillo; Y. Cardenas-Conejo; R. G. Guevara-González; G. R. Arguello-Astorga (Archives of Virology, 2012)

Evaluation of an immunochromatographic dip strip test for simultaneous detection of Cryptosporidium spp, Giardia duodenalis, and Entamoeba histolytica antigens in human faecal samples - P. Goñi; B. Martín; M. Villacampa; A. García; C. Seral; F. J. Castillo; A. Clavel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Palm use and social values in rural communities on the coastal plains of Veracruz, Mexico - R. M. González-Marín; P. Moreno-Casasola; R. Orellana; A. Castillo (Environment, Development and Sustainability, 2012)

How to cheat when you cannot lie? Deceit pollination in Begonia gracilis - Reyna A. Castillo; Helga Caballero; Karina Boege; Juan Fornoni; César A. Domínguez (Oecologia, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Research on arbuscular mycorrhizae in Mexico: an historical synthesis and future prospects - Noé Manuel Montaño; Alejandro Alarcón; Sara Lucía Camargo-Ricalde; Laura Verónica Hernández-Cuevas; Javier Álvarez-Sánchez; Ma. del Carmen A. González-Chávez; Mayra E. Gavito; Irene Sánchez-Gallen; José Ramos-Zapata; Patricia Guadarrama; Ignacio E. Maldonado-Mendoza; Silvia Castillo-Argüero; et al. (Symbiosis, 2012)

The second sodium pump: from the function to the gene - Miguel A. Rocafull; Luz E. Thomas; Jesús R. del Castillo (Pflügers Archiv - European Journal of Physiology, 2012)

Colloidal carbon stimulation of Kupffer cells triggers Nrf2 activation in the isolated perfused rat liver - Bárbara Núñez; Romina Vargas; Iván Castillo; Luis A. Videla (Journal of Molecular Histology, 2012)

Simultaneous detection of the IPN and ISA viruses in outbreaks of clinical disease and mortality in farmed Atlantic salmon, Salmo salar L., in Chile - M Cortez‐San Martin; A Rivas‐Aravena; S Guajardo; M T Castillo; M Jashes; A M Sandino; E Spencer (Journal of Fish Diseases, 2012)

Potentially pathogenic nontuberculous mycobacteria found in aquatic systems. Analysis from a reclaimed water and water distribution system in Mexico City - A. I. Castillo-Rodal; M. Mazari-Hiriart; L. T. Lloret-Sánchez; B. Sachman-Ruiz; P. Vinuesa; Y. López-Vidal (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of wild barley (Hordeum chilense)-derived DArT markers and their use into genetic and physical mapping - C. Rodríguez-Suárez; M. J. Giménez; N. Gutiérrez; C. M. Ávila; A. Machado; E. Huttner; M. C. Ramírez; A. C. Martín; A. Castillo; A. Kilian; A. Martín; S. G. Atienza (Theoretical and Applied Genetics, 2012)

Detection and characterization of a ST6 clone of vanB2-Enterococcus faecalis from three different hospitals in Spain - M. López; A. Rezusta; C. Seral; C. Aspiroz; C. Marne; M. J. Aldea; I. Ferrer; M. J. Revillo; F. J. Castillo; C. Torres (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Inexorable spread: inexorable death? The fate of neo-XY chromosomes of grasshoppers - CLAUDIO J. BIDAU; DARDO A. MARTÍ; ELIO R. CASTILLO (Journal of Genetics, 2011)

Biology of Eretmocerus sudanensis n. sp. Zolnerowich and Rose, parasitoid of Bemisia tabaci Gennadius - José A. Castillo; Philip A. Stansly (BioControl, 2011)

High genetic variability and recombination in a begomovirus population infecting the ubiquitous weed Cleome affinis in northeastern Brazil - Sarah J. C. da Silva; Gloria P. Castillo-Urquiza; Braz T. Hora Júnior; Iraildes P. Assunção; Gaus S. A. Lima; Gilvan Pio-Ribeiro; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2011)

Seismic risk analysis of urban non-engineered buildings: application to an informal settlement in Mérida, Venezuela - A. Castillo; F. López-Almansa; L. G. Pujades (Natural Hazards, 2011)

Effect of fitness and physical activity on bone mass in adolescents: the HELENA Study - L. Gracia-Marco; G. Vicente-Rodríguez; J. A. Casajús; D. Molnar; M. J. Castillo; L. A. Moreno (European Journal of Applied Physiology, 2011)

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Algal assemblages and their relationship with water quality in tropical Mexican streams with different land uses - G. Vázquez; J. A. Aké-Castillo; M. E. Favila (Hydrobiologia, 2011)

Four years of vertebrate monitoring on an upper Amazonian river - Nigel C. A. Pitman; Darren Norris; Jerry Martínez Gonzalez; Eriberto Torres; Fernando Pinto; Hernán Collado; Wilberth Concha; Raúl Thupa; Edwin Quispe; Jorge Pérez; Juan Carlos Flores del Castillo (Biodiversity and Conservation, 2011)

Seasonal changes in body size, sexual size dimorphism and sex ratio in relation to mating system in an adult odonate community - Jesús Wong-Muñoz; Alex Córdoba-Aguilar; Raúl Cueva del Castillo; Martín A. Serrano-Meneses; John Payne (Evolutionary Ecology, 2011)

Microsatellite loci for the blue swimming crab (Callinectes bellicosus) (Crustacea: Portunidae) from the Gulf of California, Mexico - A. Munguia-Vega; J. Torre; A. Castillo-Lopez; T. Pfister; R. Cudney-Bueno (Conservation Genetics Resources, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Influence of nutrients, submerged macrophytes and zooplankton grazing on phytoplankton biomass and diversity along a latitudinal gradient in Europe - Koenraad Muylaert; Carmen Pérez-Martínez; Pedro Sánchez-Castillo; Torben L. Lauridsen; Maarten Vanderstukken; Steven A. J. Declerck; Katleen Van der Gucht; José-Maria Conde-Porcuna; Erik Jeppesen; Luc De Meester; Wim Vyverman (Hydrobiologia, 2010)

Sleep patterns in Spanish adolescents: associations with TV watching and leisure-time physical activity - Francisco B. Ortega; Palma Chillón; Jonatan R. Ruiz; Manuel Delgado; Ulrike Albers; Jesús L. Álvarez-Granda; Ascensión Marcos; Luis A. Moreno; Manuel J. Castillo (European Journal of Applied Physiology, 2010)

Control of volume-sensitive chloride channel inactivation by the coupled action of intracellular chloride and extracellular protons - Carmen Y. Hernández-Carballo; José A. De Santiago-Castillo; Teresa Rosales-Saavedra; Patricia Pérez-Cornejo; Jorge Arreola (Pflügers Archiv - European Journal of Physiology, 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Neo-sex chromosome diversity in Neotropical melanopline grasshoppers (Melanoplinae, Acrididae) - Elio R. D. Castillo; Claudio J. Bidau; Dardo A. Martí (Genetica, 2010)

Coral reefs of the Pacific coast of Nicaragua - J. J. Alvarado; H. Reyes-Bonilla; F. Buitrago; J. Aguirre-Rubí; P. A. Álvarez del Castillo Cardenas (Coral Reefs, 2010)

Cytotoxicity and enzymatic activity inhibition in cell lines treated with novel iminosugar derivatives - Mercè Padró; José A. Castillo; Livia Gómez; Jesús Joglar; Pere Clapés; Carme de Bolós (Glycoconjugate Journal, 2010)

Females of a viviparous fish (Skiffia multipunctata) reject males with black colouration - A. Moyaho; P. Guevara-Fiore; E. Beristain-Castillo; C. Macías Garcia (Journal of Ethology, 2010)

Shrub encroachment can reverse desertification in semi‐arid Mediterranean grasslands - Fernando T. Maestre; Matthew A. Bowker; María D. Puche; M. Belén Hinojosa; Isabel Martínez; Pablo García‐Palacios; Andrea P. Castillo; Santiago Soliveres; Arántzazu L. Luzuriaga; Ana M. Sánchez; José A. Carreira; Antonio Gallardo; et al. (Ecology Letters, 2009)
The worldwide phenomenon of shrub encroachment in grass‐dominated dryland ecosystems is commonly associated with desertification. Studies of the purported desertification effects associated with shrub encroachment are often restricted to relatively few study areas, and document a narrow range of possible impacts upon biota and ecosystem processes. We conducted a study in degraded Mediterranean grasslands dominated by Stipa tenacissima to simultaneously evaluate the effects of shrub encroachment on the structure and composition of multiple biotic community components, and on various indicators of ecosystem function. Shrub encroachment enhanced vascular plant richness, biomass of fungi, actinomycetes and other bacteria, and was linked with greater soil fertility and N mineralization rates. While shrub encroachment may be a widespread phenomenon in drylands, an interpretation that this is an expression of desertification is not universal. Our results suggest that shrub establishment may be an important step in the reversal of desertification processes in the Mediterranean region.

Microspore embryogenesis: assignment of genes to embryo formation and green vs. albino plant production - M. Muñoz-Amatriaín; J. T. Svensson; A. M. Castillo; T. J. Close; M. P. Vallés (Functional & Integrative Genomics, 2009)

Inhibition of mammary tumor growth and metastases to bone and liver by dietary grape polyphenols - Linette Castillo-Pichardo; Michelle M. Martínez-Montemayor; Joel E. Martínez; Kristin M. Wall; Luis A. Cubano; Suranganie Dharmawardhane (Clinical & Experimental Metastasis, 2009)

The hemiplegic migraine-associated Y1245C mutation in CACNA1A results in a gain of channel function due to its effect on the voltage sensor and G-protein-mediated inhibition - Selma A. Serra; Noèlia Fernàndez-Castillo; Alfons Macaya; Bru Cormand; Miguel A. Valverde; José M. Fernández-Fernández (Pflügers Archiv - European Journal of Physiology, 2009)

Effect of exogenous arginine on sugarcane (Saccharum sp.) somatic embryogenesis, free polyamines and the contents of the soluble proteins and proline - N. Nieves; F. Sagarra; R. González; Y. Lezcano; M. Cid; M. A. Blanco; R. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning - M. D. Pérez-Cárceles; A. Sibón; M. L. Gil del Castillo; M. A. Vizcaya; E. Osuna; T. Casas; J. L. Romero; A. Luna (Biological Trace Element Research, 2008)

Six novel begomoviruses infecting tomato and associated weeds in Southeastern Brazil - Gloria P. Castillo-Urquiza; José Evando A. Beserra; Fernanda P. Bruckner; Alison T. M. Lima; Arvind Varsani; Poliane Alfenas-Zerbini; F. Murilo Zerbini (Archives of Virology, 2008)

Immunological changes after a single bout of moderate-intensity exercise in a hot environment - J. Romeo; D. Jiménez-Pavón; M. Cervantes-Borunda; J. Wärnberg; S. Gómez-Martínez; M. J. Castillo; A. Marcos (Journal of Physiology and Biochemistry, 2008)

Molecular phylogeny of the genus Rotylenchus (Nematoda, Tylenchida) and description of a new species - Nicola Vovlas; Sergei A. Subbotin; Alberto Troccoli; Gracia Liébanas; Pablo Castillo (Zoologica Scripta, 2008)
A description of a new species of plant parasitic nematodes of the genus Rotylenchus from the family Hoplolaimidae is given and a recognition of Rotylenchus jaeni comb. n., previously known as subspecies R. magnus jaeni, as separate species is proposed. Rotylenchus montanus sp. n. is characterized by a hemispherical lip region with six rarely seven annuli, stylet 33–37 µm, female tail rounded, regularly annulated tip with 12–18 annuli and phasmid located 2–9 annuli anterior to anus. Rotylenchus montanus sp. n. is close to species of the monosexual group R. arsenjevi , R. corsicus , R. fragaricus , R. helicus , R. indorobustus and R. neorobustus , by a number of specific characteristics resulting from its specific matrix code: A5, B1, C1, D4, E2, F2, G3, H2, I2, J2, K2. Molecular characterization of R. montanus sp. n. and other Rotylenchus species are provided using D2–D3 expansion segments of 28S and the ITS1 of rRNA genes. The D2–D3 of 28S rRNA and the ITS1–rRNA sequences of R. montanus sp. n. differed in one nucleotide and in 16–20 nucleotides from those of an unidentified Rotylenchus species from Russia, respectively. Molecular analysis of populations of R. magnus and R. jaeni comb. n. demonstrated differences in the D2–D3 and the ITS1–rRNA sequences. These genetic differences together with some minor morphological characters support that both subspecies should be considered as two cryptic sibling species and warranted their elevation to species rank. The result of phylogenetic analysis of Hoplolaimidae for 45 sequences of the D2 and D3 expansion regions of 28S rRNA gene using Bayesian inference analysis under the complex model is presented. Phylogenetic tree of Rotylenchus species represents seven moderate to highly supported lineages. Grouping of Rotylenchus species within other hoplolaimids and analysis of phylogenetic relationships within the genus Rotylenchus using the ITS1 of rRNA gene sequences are also discussed.

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Arrarás (Immunogenetics, 2008)

Enhanced induction of microspore embryogenesis after n-butanol treatment in wheat (Triticum aestivum L.) anther culture - M. Soriano; L. Cistué; A. M. Castillo (Plant Cell Reports, 2008)

Changes in chromium distribution during the electrodialytic remediation of a Cr (VI)-contaminated soil - Ana M. Nieto Castillo; Juan José Soriano; Rafael A. García-Delgado (Environmental Geochemistry and Health, 2008)

Immune-related genes associated with intestinal tissue in the sea cucumber Holothuria glaberrima - Francisco Ramírez-Gómez; Pablo A. Ortíz-Pineda; Carmencita Rojas-Cartagena; Edna C. Suárez-Castillo; José E. García-Ararrás (Immunogenetics, 2008)

Correlation between the presence of symptoms and the Giardia duodenalis genotype - J. Sahagún; A. Clavel; P. Goñi; C. Seral; M. T. Llorente; F. J. Castillo; S. Capilla; A. Arias; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Ca2+ store determines gating of store operated calcium entry in mammalian skeletal muscle - Adom A. González Narváez; A. Castillo (Journal of Muscle Research and Cell Motility, 2007)

Digestive responses of two omnivorous rodents (Peromyscus maniculatus and P. alstoni) feeding on epigeous fungus (Russula occidentalis) - T. D’Alva; C. Lara; A. Estrada-Torres; C. Castillo-Guevara (Journal of Comparative Physiology B, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon emissions from land-use change: an analysis of causal factors in Chiapas, Mexico - M. A. Castillo-Santiago; A. Hellier; R. Tipper; B. H. J. de Jong (Mitigation and Adaptation Strategies for Global Change, 2007)

Contrasting strategies to cope with drought by invasive and endemic species of Lantana in Galapagos - Jesús M. Castillo; Pablo Leira-Doce; Jorge Carrión-Tacuri; Edison Muñoz-Guacho; Aída Arroyo-Solís; Guillermo Curado; David Doblas; Alfredo E. Rubio-Casal; Antonio A. Álvarez-López; Susana Redondo-Gómez; Regina Berjano; Giovanny Guerrero; et al. (Biodiversity and Conservation, 2007)

Introgression in the genus Salmo via allotriploids - A. G. F. CASTILLO; E. BEALL; P. MORAN; J. L. MARTINEZ; F. AYLLON; E. GARCIA‐VAZQUEZ (Molecular Ecology, 2007)
Hybridization between sympatric species is not uncommon in the wild. Wild allotriploids (individuals with two chromosome sets from a species + one chromosome set from another species) are generally the result of a backcross between interspecific hybrids that produce unreduced gametes and one of the parental species. In animals, allotriploids are commonly sterile, except for some vertebrate species complexes in which allotriploids reproduce by parthenogenesis, gynogenesis and/or hybridogenesis, producing generally clonal or hemiclonal gametes; nuclear DNA introgression between hybridizing species is considered to be extremely rare. Employing species‐specific molecular markers, we show genetic introgression between the chromosomally well‐differentiated salmonids Atlantic salmon (2n = 58) and brown trout (2 n = 80) through spontaneous bisexual reproduction of allotriploids leading to salmon‐like offspring bearing some brown trout genes. Although introgression between these Salmo species can occur via allotriploids, we hypothesize that extinction of parental species can be discarded based on very low survival of allotriploid offspring.

Cinnamtannin B-1 from bay wood exhibits antiapoptotic effects in human platelets - A. Bouaziz; C. Romera-Castillo; S. Salido; P. J. Linares-Palomino; J. Altarejos; A. Bartegi; J. A. Rosado; G. M. Salido (Apoptosis, 2007)

Influence of Fe concentration in the medium on multicellular pollen grains and haploid plants induced by mannitol pretreatment in barley (Hordeum vulgare L.) - A. Pulido; F. Bakos; A. Castillo; M. P. Vallés; B. Barnabás; A. Olmedilla (Protoplasma, 2006)

Mitochondrial Genome Dynamics in Plants and Animals: Convergent Gene Fusions of a MutS Homologue - Ricardo V. Abdelnoor; Alan C. Christensen; Saleem Mohammed; Bryan Munoz-Castillo; Hideaki Moriyama; Sally A. Mackenzie (Journal of Molecular Evolution, 2006)

Production of doubled haploids in durum wheat (Triticum turgidum L.) through isolated microspore culture - L. Cistué; M. Soriano; A. M. Castillo; M. P. Vallés; J. M. Sanz; B. Echávarri (Plant Cell Reports, 2006)

Effect of S-adenosylmethionine on Age-induced Hepatocyte Damage in Old Wistar Rats - Carmen Castillo; Veronica Salazar; Carmen Ariznavarreta; Mariana Fossati; Jesus A. F. Tresguerres; Elena Vara (Biogerontology, 2005)

Effect of Recombinant Human Growth Hormone Administration on Body Composition and Vascular Function and Structure in Old Male Wistar Rats - Carmen Castillo; Mar Cruzado; Carmen Ariznavarreta; Pablo Gil-Loyzaga; Vicente Lahera; Victoria Cachofeiro; Jesús A. F. Tresguerres (Biogerontology, 2005)

Organization of phenylalanine ammonia lyase (PAL), acidic PR-5 and osmotin-like (OSM) defence-response gene families in the potato genome - Rosa A. Castillo Ruiz; Carmen Herrera; Marc Ghislain; Christiane Gebhardt (Molecular Genetics and Genomics, 2005)

Kinetic Study of the Release of Lead in a Mine-Impacted Tropical River - F. Arcega-Cabrera; S. E. Castillo-Blum; M. A. Armienta (Bulletin of Environmental Contamination and Toxicology, 2005)

18th International Mouse Genome Conference - Amy C. Lossie; Thomas P. Meehan; Andrew Castillo; Lihua Zheng; Keith C. Weiser; Mark A. Strivens; Monica J. Justice (Mammalian Genome, 2005)

Application of the ‘Climafor’ Approach to Estimate Baseline Carbon Emissions of a Forest Conservation Project in the Selva Lacandona, Chiapas, Mexico - B. H. J. De Jong; A. Hellier; M. A. Castillo-Santiago; R. Tipper (Mitigation and Adaptation Strategies for Global Change, 2005)

Short-term responses to salinity of an invasive cordgrass - Jesús M. Castillo; Alfredo E. Rubio-Casal; Susana Redondo; Antonio A. Álvarez-López; Teresa Luque; Carlos Luque; Francisco J. Nieva; Eloy M. Castellanos; Manuel E. Figueroa (Biological Invasions, 2005)

Effects of ovariectomy and growth hormone administration on body composition and vascular function and structure in old female rats - C. Castillo; M. Cruzado C. Ariznavarreta; V. Lahera; V. Cachofeiro; P. Gil-Loyzaga; Jess A. F. Tresguerres (Biogerontology, 2005)

Growing more rice with less water: Research findings from a study in China - Randoph Barker; To Phuc Tuong; Yuanhua Li; E. G. Castillo; B. A. M. Bouman (Paddy and Water Environment, 2004)

Effect of irrigation method and N-fertilizer management on rice yield, water productivity and nutrient-use efficiencies in typical lowland rice conditions in China - Romeo J. Cabangon; To Phuc Tuong; Ernesto G. Castillo; Lang Xing Bao; Guoan Lu; Guangho Wang; Yuanlai Cui; Bas A. M. Bouman; Yuanhua Li; Chongde Chen; Jianzhang Wang (Paddy and Water Environment, 2004)

Cryptic isolation of Gulf of California shovelnose guitarfish evidenced by mitochondrial DNA - J. Sandoval-Castillo; A. Rocha-Olivares; C. Villavicencio-Garayzar; E. Balart (Marine Biology, 2004)

A new species, Herbertia crosae (Iridaceae), from Uruguay - G. G. Roitman; A. Castillo (Brittonia, 2004)

Observations on Some Species of Chaetoceros (Bacillariophyceae) with Reduced Number of Setae from a Tropical Coastal Lagoon - José Antolí; n Aké-Castillo; Sandra Luz Guerra-Martí; nez; Marí; a Eugenia Zamudio-Reséndiz (Hydrobiologia, 2004)

Acidophilic granulocytes of the marine fish gilthead seabream ( Sparus aurata L.) produce interleukin-1 following infection with Vibrio anguillarum - Elena Chaves-Pozo; Pablo Pelegrn; Jess Garca-Castillo; Alfonsa Garca-Ayala; Victoriano Mulero; Jos Meseguer (Cell and Tissue Research, 2004)

Ten-Year Viability Study on Natural Populations of Drosophila Sibling Species from Laguna Verde, Veracruz, México - E. Pimentel; M. P. Cruces; V. M. Salceda; M. E. de la Rosa; L. Levine; J. A. Castillo (Archives of Environmental Contamination and Toxicology, 2004)

Changes with ageing in several leukocyte functions of male and female rats - Mnica De La Fuente; Isabel Baeza; Noelia Guayerbas; Marta Puerto; Carmen Castillo; Veronica Salazar; Carmen Ariznavarreta; Jesus A. F-tresguerres (Biogerontology, 2004)

Biological and molecular characterization of P101 isolate, a tobamoviral pepper strain from Bulgaria - M. Ruz del Pino; A. Moreno; M. Garca de Lacoba; S. Castillo-Lluva; P. Gilardi; M. T. Serra; I. Garca-Luque (Archives of Virology, 2003)

Biochemical characterization of embryogenic and non-embryogenic calluses of sugarcane - Nadina Neves; Magdalena Segura-Nieto; María A. Blanco; Margelys Sánchez; Alfredo González; Justo L. González; Ramiro Castillo (In Vitro Cellular & Developmental Biology - Plant, 2003)

Insights into Insulin and Glucagon Responses in Fish - I. Navarro; P. Rojas; E. Capilla; A. Albalat; J. Castillo; N. Montserrat; M. Codina; J. Gutiérrez (Fish Physiology and Biochemistry, 2002)

Evaluation of an Immunochromatographic Dip-Strip Test for the Detection of Cryptosporidium Oocysts in Stool Specimens - M. Llorente; A. Clavel; M. Varea; S. Olivera; F. Castillo; J. Sahagún; M. Rubio; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Penicillin-Susceptible and Erythromycin-Resistant Streptococcus pneumoniae in Children with Acute Mastoiditis - F. del Castillo; F. Ledesma; A. García-Perea (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Multispectral in situ measurements of organic matter and chlorophyll fluorescence in seawater: Documenting the intrusion of the Mississippi River plume in the West Florida Shelf - Carlos E. Del Castillo; Paula G. Coble; Robyn N. Conmy; Frank E. Müller‐Karger; Lisa Vanderbloemen; Gabriel A. Vargo (Limnology and Oceanography, 2001)
We performed multispectral, in situ fluorescence measurements of detrital colored organic matter (COM) and chlorophyll a (Chl a) in surface waters of the West Florida Shelf using the Wet Labs spectral absorption and fluorescence instrument (SAFIre). Continuous underway measurements allowed simultaneous mapping of the dispersal pattern of riverine organic material and Chl a on the shelf. We used two fluorescence emission ratios to differentiate between riverine and marine COM. The data showed unusually high concentrations of COM offshore. These were attributed to an offshore extension of the Mississippi River plume. Comparisons between in situ Chl a concentrations measured with the SAFIre and Chl a values obtained from the sea‐viewing wide field‐of‐view sensor (SeaWiFS) satellite data using OC4 and MODIS algorithms showed that, although both algorithms overestimated Chl a, MODIS performed better than OC4, particularly in areas with high COM concentrations. Analysis of the relationship between Chl a and COM concentrations within the study area showed regional variability probably caused by differences in river source.

Effect of abscisic acid and jasmonic acid on partial desiccation of encapsulated somatic embryos of sugarcane - Nadina Nieves; M. E. Martínez; R. Castillo; María A. Blanco; J. L. González-Olmedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Efficient production of androgenic doubled-haploid mutants in barley by the application of sodium azide to anther and microspore cultures - A. M. Castillo; L. Cistué; M. P. Vallés; J. M. Sanz; I. Romagosa; J. L. Molina-Cano (Plant Cell Reports, 2001)

Polymorphism of the 5′ terminal region of Citrus tristeza virus (CTV) RNA: Incidence of three sequence types in isolates of different origin and pathogenicity - M. A. Ayllón; C. López; J. Navas-Castillo; S. M. Garnsey; J. Guerri; R. Flores; P. Moreno (Archives of Virology, 2001)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Liver injury caused by ebrotidine: a new example of the utility of the postmarketing surveillance - J. R. Castillo; J. Torelló; A. Hernandez (European Journal of Clinical Pharmacology, 2000)

Plant species of traditional Mayan homegardens of Mexico as analogs for multistrata agroforests - F. A. J. De Clerck; P. Negreros-Castillo (Agroforestry Systems, 2000)

In situ localization of anion exchanger-2 in the human kidney - Jos E. Castillo; Eduardo Martnez-Ans; Raquel Malumbres; Enrique De Alava; Carmen Garca; Juan F. Medina; Jess Prieto (Cell and Tissue Research, 2000)

Storage proteins in sugarcane: An interesting exception in monocots - Maria A. de los Blanco; Magdalena Segura-Nieto; Ramiro Castillo; Nadina Nieves (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Dietary fish oil reduces cholesterol and arachidonic acid levels in chick plasma and very low density lipoprotein - Mercedes Castillo; Fatima Amalik; Ana Linares; Eduardo Garciacute; a-Peregrín (Molecular and Cellular Biochemistry, 1999)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Desiccated doubled-haploid embryos obtained from microspore culture of barley cv. Igri - A. B. Ryan; A. M. Castillo; M. P. Vallés; J. M. Sanz; L. Cistué (Plant Cell Reports, 1999)

Influence of anther pretreatment and culture medium composition on the production of barley doubled haploids from model and low responding cultivars - L. Cistué; A. Ramos; A.M. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Use of a Selective Medium and a Membrane Filter Method for Isolation of Campylobacter Species from Spanish Paediatric Patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Somatic embryogenesis and plant regeneration from barley cultivars grown in Spain - A. M. Castillo; B. Egaña; J. M. Sanz; L. Cistué (Plant Cell Reports, 1998)

Use of a selective medium and a membrane filter method for isolation ofCampylobacter species from Spanish paediatric patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Plasma membrane redox system activity in tumour cell lines of mammary origins with different proliferation rates - A. E. del Valle; A. del Castillo-Olivares; F. Sánchez-Jiménez; J. Márquez; I. Núñez de Castro; M. A. Medina (Protoplasma, 1998)

Plant regeneration from encapsulated somatic embryos of Carica papaya L. - B. Castillo; M. A. L. Smith; U. L. Yadava (Plant Cell Reports, 1998)

Protein changes associated with plant regeneration in embryogenic calli of sugarcane (Saccharum sp.). - María A. de los Blanco; Nadina Nieves; Margelys Sánchez; Carlos G. Borroto; Ramiro Castillo; Justo L. González; Maritza Escalona; Evelio Báez; Zulema Hernández (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Fusarium and Fumonisins in Corn at Harvest Time: Effect of Fertilization and Planting Area - M. L. Ramirez; A. Torres; M. Rodriguez; C. Castillo; S. Chulze (Cereal Research Communications, 1997)

A Planning Model for the Fuerte-Carrizo Irrigation System, Mexico - LAURA A. IBÁÑEZ-CASTILLO; JESÚS CHÁVEZ-MORALES; MIGUEL A. MARIÑO (Water Resources Management, 1997)

Direct somatic embryogenesis from Begonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)

Direct somatic embryogenesis fromBegonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)

A preliminary study of the behaviour and vitality of reseeded juvenile great scallops, of three sizes in three seasons - P. G. Fleury; C. Mingant; A. Castillo (Aquaculture International, 1996)